Retraction Note: Exploring the molecular mechanisms of rice blast resistance and advances in breeding for disease tolerance - Muhammad Usama Younas; Muhammad Qasim; Irshad Ahmad; Zhiming Feng; Rashid Iqbal; Xiaohong Jiang; Shimin Zuo (Molecular Biology Reports, 2026)

High frequency and prognostic significance of TP53 promoter methylation in Pakistani glioblastoma patients - Ahad Naveed; Noor Muhammad; Afshan Khanum; Asif Loya; Muhammad Usman Rashid (Molecular Biology Reports, 2026)

Integrative QSAR-GaMD Approach Identifies Stable Repurposed Inhibitors Targeting Dengue Virus Proteins - Amna Shafqat; Muhammad Shahab; Alia Ashraf; Zakirullah; Rashid Ahmad; Shan Xu; Guojun zheng; Yigang Tong (Journal of Pharmaceutical Innovation, 2026)

Screening of bacteriophages for subsequent treatment of resistant Escherichia coli infections transmitted through poultry - Mobeen ur Rashid; Saeed Ahmed; Javed Muhammad; Muhammad Tariq Navid; Waseem Safdar; Aman Karim; Ijaz Ahmad; Haider Ali; Kashif Abdaal (Brazilian Journal of Microbiology, 2026)

Facile synthesis of cobalt-iron layered double hydroxide and its derived mixed metal oxide for Congo red and Pb(II) remediation - Ramzan Akhtar; Adil Khan; Maria Gul; Mohsin Ali Raza Anjum; Iqra Rafique; Muhammad Rehan; Rashid Nazir Qureshi; Sajid Iqbal; Muhammad Saifullah (Colloids and Surfaces C: Environmental Aspects, 2026)

Unveiling the insecticidal potential of indigenous host-crop associated Pseudomonas bacteria, potential candidate for effective control of Plutella xylostella(Lepidoptera: Plutellidae) - Muhammad Shehzad; Abdur Rashid Khan; Muhammad Tariq (Crop Protection, 2026)

Phytochemical-rich extract of Psidium guajava ameliorates letrozole-induced PCOS in female rats by modulating the NF-κB inflammatory pathway - Hao Xu; Palwasha Haider; Majid Manzoor; Rida Siddique; Hina Manzoor; Muhammad Yasir Ali; Rizwan Rashid Bazmi; Liaqat Hussain; Ping Wang (Tissue and Cell, 2026)

Identification and characterization of loess deposits along the Indus River in Pakistan - Xuegang Mao; Xiuming Liu; Zahir Muhammad; Mingming Ma; Ali Rashid Tabrez; Yuechen Lian; Lingshan He; Xinyao Qi (Quaternary International, 2026)

Finite element-based investigation and explainable machine learning prediction of moment resistance of steel flush end-plate connections - Md. Ibrahim Kholil; Muhammad Harunur Rashid; Aziz Ahmed; Md. Waliul Islam (Next Research, 2026)

Synthesis and application of NiFe2O4/Nb2C-MXene composites for enhanced microbial fuel cell performance in wastewater treatment: Advancing sustainable bioelectricity generation - Muhammad Waseem Mumtaz; Haseeb Ashraf; Hamid Mukhtar; Memona Sadiqa; Uroosa Saeed; Waheed Miran; Tahir Iqbal; Aashir Waleed; Umer Rashid (Biomass and Bioenergy, 2026)

Retraction Note: Impact of elevated temperatures on the genetic and morpho-physiological traits of cotton genotypes cultivation - Aamir Ali Abro; Muhammad Qasim; Muhammad Usama Younas; Ijaz Ali; Mubashir Abbas; Noor Muhammad; Shiguftah Khalid; Junaid Ahmed; Umbreen Bibi; Muhammad Waqas; Sezai Ercisli; Fahad Al-Asmari; et al. (Genetic Resources and Crop Evolution, 2026)

Integrated optimization of Lantana camara-based biopesticide for Sitophilus granarius control: Chemical profiling, residual efficacy, and machine-learning-driven decision support - Pervin Erdogan; Muhammad Aasim; Zemran Mustafa; Amjad Ali; Seyid Amjad Ali; Rashid Abbas Khan; Abdul Waheed (Journal of Stored Products Research, 2026)

Retraction notice to ‘Hydrogeochemical properties, source provenance, distribution, and health risk of high fluoride groundwater: Geochemical control, and source apportionment’ [Environ. Pollut. 362, (2024) 125000] - Muhammad Ayub; Hira Javed; Abdur Rashid; Wardah Hayat Khan; Asif Javed; Tariq Sardar; Ghulam Mujtaba Shah; Ajaz Ahmad; Jörg Rinklebe; Parvaiz Ahmad (Environmental Pollution, 2026)

Assessing meteorological influences and predicting PM2.5 using deep learning approach: A case of Asian metropolitan city, Lahore - Amna Rashid; Rana Muhammad Atif (Atmospheric Environment, 2026)

Correction to: Magnetic Bentonite for Efficient Phosphate Removal from Wastewater: A Sustainable Strategy to Combat Eutrophication - Khizar Hussain Shah; Muhammad Imtiaz Rashid; Javairia Zubair; Saba Zafar; Abdul Amir; Akhtar Iqbal; Khurram Shahzad; Arshid Mahmood Ali (Water, Air, & Soil Pollution, 2026)

Influence of Temperature and Hydrogen Peroxide Treatment on the Physiochemical and Adsorptive Characteristics of Rice Stalk Biochar for Cadmium Remediation: A Sustainable Solution - Ghulam Murtaza; Zeeshan Ahmed; Muhammad Usman; Awais Ahmad; Waed Alahmad; Mohammed S. Alotaibi; Saqer S. Alotaibi; Sajad Ali; Rashid Iqbal (Water, Air, & Soil Pollution, 2026)

Phase-specific effects of guar meal and β-mannanase on growth performance and nutrient digestibility in broilers - Haroon Ur Rashid; Taimoor Khan; Muhammad Tahir; Muhammad Daud; Damiano Cavallini; Giovanni Buonaiuto (Tropical Animal Health and Production, 2026)
This study evaluated the phase-specific effects of dietary guar meal (GM) inclusion, with or without β-mannanase supplementation, on growth performance, nutrient digestibility, and energy utilization in broiler chickens. A total of 300 male Ross 308 broilers were assigned to eight experimental diets in a 4 × 2 factorial arrangement, consisting of four GM inclusion levels (0%, 4%, 8%, and 12%) with or without β-mannanase supplementation (0.35 g/kg), and were evaluated during the starter (7–21 d) and grower (22–35 d) phases. During the starter phase, broilers fed 4% GM supplemented with β-mannanase achieved growth performance comparable to the control diet, whereas increasing GM inclusion significantly reduced body weight gain, crude protein digestibility, and apparent metabolizable energy (AME; P < 0.05). β-mannanase supplementation partially alleviated these negative effects and fully restored crude protein digestibility at 4% GM. During the grower phase, broilers tolerated up to 8% GM without major reductions in growth performance, whereas 12% GM consistently impaired productive responses. Enzyme supplementation further enhanced body weight gain and protein digestibility across GM inclusion levels; however, its efficacy declined at 12% GM, where performance and energy utilization remained significantly lower than the control diet ( P < 0.05). These findings demonstrate that broiler responses to GM are strongly age-dependent and identify phase-specific tolerance thresholds for dietary inclusion. Under the conditions of this study, 4% GM during the starter phase and up to 8% GM during the grower phase can be successfully incorporated when supported by β-mannanase supplementation. This strategy may facilitate the sustainable utilization of guar meal as an agro-industrial by-product while maintaining productive performance and nutrient efficiency in broiler production systems.

Towards Safer Antimicrobial Peptide Therapeutics: A Predictive–Generative Framework Targeting ESKAPE Pathogens - Zubia Rashid; Hania Ahmed; Kashif Saleem; Muhammad Razi Uddin Siddiqui (Probiotics and Antimicrobial Proteins, 2026)

Cadmium Nanoparticles Disrupt Root Exosomal Defense Signaling Across Fruit & Root Crops: Mechanisms and Postharvest Rot Susceptibility - Qudrat Ullah; Waqas Haider; Muhammad Waqar; Abdul Rehman; Rashid Abbas Khan; Zaki ul Zaman Asam; Muhammad Zubair; Mujahid Farid (Plant Molecular Biology Reporter, 2026)

Decarbonizing Pakistan′s cement industry: a review of emissions, mitigation levers, policy frameworks, and implementation challenges - Muhammad Sumair; Tanzeel-ur Rashid; Muhammad Idrees; Müslüm Arıcı; Zhijiang Wang; Muzaffar Ali (Clean Technologies and Environmental Policy, 2026)

Synergistic role of biochar, AMF, and PGPR in enhancing drought tolerance and productivity of wheat (Triticum aestivum L.) - Ghulam Murtaza; Zeeshan Ahmed; Muhammad Usman; Islem Abid; Awais Ahmad; Vusala Ismayilova; Manal Abdulaziz Binobead; Rashid Iqbal (Cereal Research Communications, 2026)

Multi-omics and precision breeding strategies for enhancing biotic and abiotic stress resilience in rice - Zameer Hussain Jamali; Muhammad Usama Younas; Muhammad Qasim; Sajad Ali; Rashid Iqbal; Saltanat Aghayeva; Petr Konvalina (Cereal Research Communications, 2026)

Adaptation of wild-type rabies virus on vaccine producing cell line and its quantification by peroxidase-based immunostaining - Muhammad Rehan Riaz; Syed Muhammad Kamran Ullah; Muhammad Rashid; Kaleem Ullah; Hamid Ahmad; Qari Muhammad Kaleem; Faiza Jamil; Saifullah Khan (Archives of Virology, 2026)

Daturaolone from Datura metel L. Inhibits acetylcholinesterase and monoamine oxidase B - Bilal Khan; Marryum; Abdur Rauf; Ayesha Tahir; Umer Rashid; Hira Naeem; Muhammad Saeed Jan; Muhammad Shafique; Saima Naz; Alessandra Gianoncelli; Giovanni Ribaudo (Natural Product Research, 2026)

Unveiling the plant growth-promoting and antifungal potential of Melissa officinalis endophytes: The integrative culture-dependent and metagenomic approaches - Vyacheslav Shurigin; Xiaoxuan Lu; Abdur Rashid Khan; Murad Muhammad; Ibad Ullah; Dilfuza Egamberdieva; Yang Yu; Li Li (Plant Science, 2026)

Numerical Analysis of Altitude Effects on Single-Cylinder Two-Stroke UAV Engine Performance - Muhammad Nouman Rashid; Faiq Said; Syed Ghafoor Shah; Muhammad Bilal; Hamza Sultan; Muhammad Qail (Next Research, 2026)

Diesel engine performance enhancement using MXene nano-additives: An experimental study on efficiency and Pollutant Suppression - Mohd Danish; Sajid Ali; Syed Mohd Yahya; Rashid Ali; Suhaib Umer Ilyas; Sami Mansour Ghazali; Muhammad Faisal Rathore; Saeed Rubaiee (Fuel, 2026)

POSS-integrated 3D polyimide COFs for gold recovery from E-waste via adsorption and photoreduction - Saddam Hussain; Mingkun Qi; Yongchi Long; Muhammad Rashid; Hongzhi Liu (Chemical Engineering Journal, 2026)

Optimizing Nitrogen Fertilization through Combined Sources and Split Humic Acid Application Improves Wheat Productivity and Stress Resilience in Semi-arid Soils - Tahir Fazal; Muhammad Aurangzaib; Umar Arshad; Rashid Iqbal; Muhammad Raheel; Allah Ditta; Mohamed Taha Yassin (Water, Air, & Soil Pollution, 2026)

Development and Performance Evaluation of an Indigenized Smart Field Lysimeter for Relative Crop Water-Use Assessment - Muhammad Faisal; Fiaz Hussain; Shoaib Rashid Saleem; Saliha Qamar (Water Conservation Science and Engineering, 2026)

Early winter precipitation variability over Pakistan and associated ENSO teleconnections - Romesa Najeeb; Irfan Ur Rashid; Rehan Ahmed; Muhammad Adnan Abid; Elham Ghasemifar; Ibrahim Alsafari (Theoretical and Applied Climatology, 2026)

Green-Synthesized Zinc Oxide Nanoparticles from Selenicereus grandiflorus Exhibit Potent Nematicidal Activity Against Meloidogyne incognita - Sidra Ahmad; Mian Afaq Ahmad; Nayab Ahmad; Fazal Umer; Iqbal Munir; Md. Shahinoor Islam; Gulzar Ahmad; Muhammad Ijaz; Allah Ditta; Rashid Iqbal; Badr Aldahmash; Ahmed Rady (Current Microbiology, 2026)

Harnessing the Potential of Nodule Endophytic Bacteria to Improve Soybean Growth Under Saline Conditions - Humaira Islam; Mohsin Tariq; Kashif Sattar; Tahira Yasmeen; Muhammad Abdul Rehman Rashid (Current Microbiology, 2026)

Valorization of rubber waste for the synthesis of an acidic heterogeneous catalyst for efficient palm fatty acid distillate esterification - Muhammad Aliyu; Junaid Ahmad; Chawalit Ngamcharussrivichai; Kamil Kayode Katibi; Syed Ahmar Ali Hashmi; Umer Rashid (Process Safety and Environmental Protection, 2026)

Zircon U-Pb, Hf isotope and trace element geochemistry from the newly found Neoproterozoic granitoids in Wadh-Khuzdar area, Balochistan, Pakistan: constraints on magma genesis and tectonic settings - Muhammad Hussain; Hafiz U. Rehman; Muhammad Ishaq Kakar; Hao-Yang Lee; Sun-Lin Chung; Kaushik Das; Mehboob ur Rashid; Nasir Ahmad; Tehseen Zafar; Hiroshi Yamamoto (Precambrian Research, 2026)

Phosphoric Acid Outperforms Diammonium Phosphate (DAP) in Cadmium Toxicity Alleviation by Decreasing Bioavailability and Optimizing Maize Physiology in Contaminated Alkaline Soil - Nadeem Sarwar; Mujahid; Muhammad Akhtar; Imtiaz Ahmed; Wajid Mahboob; Muhammad Imran Tipu; Muhammad Rashid Shaheen; Mashael Daghash Alqahtani; Usman Zulfiqar (Water, Air, & Soil Pollution, 2026)

Impact of insect pollinators on the yield and quality of cucumber (Cucumis sativus L.) - Muhammad Mamoon-ur-Rashid; Farheen Sayyam; Habib Ali; Modhi O. Alotaibi; Ammara Riaz; Xu Danping; Muhammad Umair Sardar; Aftab Ahmad; Zhuo Zhihang (International Journal of Tropical Insect Science, 2026)

Boredom Proneness, Sleep Quality, and Attention-Related Cognitive Errors: A Mediation Analysis - Muhammad Rashid; Shabnam Shabnam (Sleep and Vigilance, 2026)

Unlocking ketone dimerization efficiency with multifunctional Zr and Hf based UiO-66 and NUS-6 MOFs: A synergy of experiment and theory - Muhammad Kashif Majeed; Rashid Iqbal; M.Umar Majeed; Muhammad Akram; M.Zeeshan Ashfaq; Adil Saleem (Fuel, 2026)

The Methodological Evolution of the Water-Food-Energy Nexus Index in Agriculture: A Systematic Review - Nisar Muhammad; Rashid Farooq; Khan Zaib Jadoon; Ghufran Ahmed Pasha (Water Resources Management, 2026)
The Water-Food-Energy (WFE) nexus has become a central framework for addressing resource sustainability in agriculture, yet its operationalization increasingly relies on composite indices whose methodological foundations remain fragmented. This study presents the first systematic and critical review of the Water-Food-Energy Nexus Index (WFENI) applied in agricultural systems. Following a rigorous PRISMA-guided protocol, we analyzed 21 peer-reviewed studies to examine indicator selection, index construction, weighting schemes, and validation practices. The review reveals a clear methodological evolution from early resource-efficiency metrics toward expanded frameworks that integrate environmental, climate, and emission dimensions. While normalization approaches are largely standardized, substantial divergence exists in weighting and aggregation, marking a gradual shift from equal and expert-based weights toward data-driven and optimization-based methods. However, a critical “robustness gap” persists: the vast majority of studies lack formal sensitivity or uncertainty analysis, raising serious concerns about reliability. This review systematically maps these methodological trends and outlines a strategic agenda for future research, advocating for the institutionalization of robustness testing, dynamic modeling, and expanded system boundaries to enhance the rigor and policy relevance of agricultural sustainability assessments.

Arbuscular Mycorrhizal Fungi and Leonardite alter fatty acid and amino acid biosynthesis in sunflower grains - Ghulam Murtaza; Muhammad Usman; Muhammad Rizwan; Sajad Ali; Zeeshan Ahmed; Khairiah Mubarak Alwutayd; Rashid Iqbal (Plant Molecular Biology, 2026)

Flash flood susceptibility assessment using an integrated geomorphologic framework in data-scarce arid and semi-arid regions - Aftab Ullah; Rashid Farooq; Abdul Razzaq Ghumman; Muhammad Ejaz Tanveer; Muhammad Atiq Ur Rehman Tariq (Modeling Earth Systems and Environment, 2026)
Flash floods are among the most frequent natural hazards, posing serious environmental challenges, particularly in arid and semi-arid regions where steep topography and compact basin morphometry accelerate surface runoff. The ungauged hill torrents of southwestern Punjab, Pakistan, are particularly vulnerable to such events, experiencing recurrent, intense flash floods. This study develops an integrated GIS-based morphometric framework to assess flash flood susceptibility across 13 major hill torrents in DG Khan and Rajanpur, Punjab. Fifteen morphometric parameters were analyzed using three complementary approaches: Hazard Degree (HD), Principal Component Analysis (PCA), and Analytical Hierarchy Process (AHP). The HD method captured the cumulative influence of all parameters. At the same time, PCA reduced redundancy and identified four dominant controlling factors: length of overland flow (Lo), form factor (Ff), circulatory ratio (Rc), and ruggedness number (Rn). The AHP further incorporated expert judgment, identifying drainage density (Dd) and ruggedness number as the most influential parameters, followed by basin relief (Bh) and drainage frequency (Fs). The convergence of results across the three independent methods significantly improves classification reliability compared to single-method analyses. Three hill torrents (Vidore, Mithawan, and Kaha) were consistently classified as highly susceptible, one as moderately susceptible, and four as low susceptibility. Hence, the proposed integrated HD-PCA-AHP model reduces methodological uncertainty and provides a transferable, data-efficient tool for assessing flash flood susceptibility and managing watersheds in data-scarce arid and semi-arid regions.

Efficacy of Vachellia nilotica Extract-coated Urea in Maize: Field Performance and Phytochemical Basis of Urease Inhibition - Rashid Mahmood; Hina Jabeen; Muhammad Ajmal Rana; Faisal Nadeem; Ejaz Ahmed; Muhammad Bilal Chattha (Journal of Soil Science and Plant Nutrition, 2026)

A comparative study of YOLOv8 and Mask R-CNN for automated geological fracture detection in well-log images - Muhammad Rashid; Miao Luo; David A. Wood (Computational Geosciences, 2026)

Effects of strigolactone-modified biochars on wheat (Triticum aestivum L.) germination and soil nutrient dynamics in alkaline soil - Ghulam Murtaza; Muhammad Usman; Wael Elmenofy; Hanan M. Alharbi; Khairiah Mubarak Alwutayd; Mohammad K. Alharbi; Rashid Iqbal (Cereal Research Communications, 2026)

Enhancement of maize drought resilience using nano-buckminsterfullerenes and plant growth-promoting rhizobacteria: insights into pigment stability, oxidative stress reduction, and yield - Ghulam Murtaza; Muhammad Usman; Najmaldin Ezaldin Hassan; Zeeshan Ahmed; Awais Ahmad; Khairiah Mubarak Alwutayd; Wael Elmenofy; Hassan Mehmood; Rashid Iqbal (Cereal Research Communications, 2026)

Adaptive role of silicon in enhancing crop resilience and yield under stressful environments: A new window for stress management - Ghulam Murtaza; Muhammad Rizwan; Muhammad Usman; Qamar uz Zaman; Zeeshan Ahmed; Rashid Iqbal; Akash Tariq; Gang Deng (Plant Biosystems, 2026)

Multi-scale meteorological and hydrological drought severity in a high-altitude Himalayan basin: An intensity–duration–frequency approach using SPI and SSI (1970–2016) - Nuaman Ejaz; Muhammad Rashid; Muhammad Waqar Saleem; Amro Elfeki; Songhao Shang (Journal of Mountain Science, 2026)

Synergistic application of biochar and mercury-resistant Bacillus cereus enhances phytoremediation efficiency and stress tolerance in sorghum (Sorghum bicolor L.) grown in mercury-contaminated soil - Ghulam Murtaza; Muhammad Usman; Zeeshan Ahmed; Rashid Iqbal (Biodegradation, 2026)

Precision Agriculture Through Green Nanoparticles: Mechanistic Insights into Nutrient Delivery and Enzyme-Targeted Pest Control with Emerging Computational Perspectives - Muhammad Irfan; Hira Altaf; Mishal Naveed; Nadia Zeeshan; Umer Rashid; Amber Afroz (Journal of Soil Science and Plant Nutrition, 2026)

Bacillus subtilis enhances maize yield by restricting cadmium translocation and modulating ion homeostasis - Haseeb Ahmad; Jiu Yang Mao; Rayyan Khan; Muhammad Ali Shah; Kashif Khan; Muhammad Asad Naseer; Shahid Ali; Rida Rashid; Rui He; Xun Bo Zhou (Journal of Environmental Sciences, 2026)

Enhancing Soil and Atmospheric Carbon Regulation Through Bombax Ceiba-Based Agroforestry in Drylands - Ghulam Yasin; Muhammad Talha Bin Yousaf; Muhammad Atif Latif; Muhammad Azeem Sabir; Muhammad Azeem Akhter; Shafeeq Ur Rahman; Sajad Ali; Khairiah Mubarak Alwutayd; Rashid Iqbal (Water, Air, & Soil Pollution, 2026)

Biochemical and Yield Response of Rice (Oryza sativa L.) to Exogenous Application of Glutathione Under High Temperature Stress at Flowering Stage - Rania Baloch; Muhammad Farrukh Saleem; Muhammad Sarwar; Muhammad Awais Arshad; Muhammad Aown Sammar Raza; Aqsa Baloch; Amina Rashid (Journal of Plant Growth Regulation, 2026)

Valorization of recycled concrete fine aggregates in gypsum mortars for developing eco-friendly false ceiling plates - Rashid Latif; Muhammad Rizwan Riaz; Anam Fatima; Rizwan Azam; Muhammad Hassan Javed (Innovative Infrastructure Solutions, 2026)

Nature’s arsenal unleashed: Senegalia modesta derived thymol halts cancer progression by suppressing proangiogenic genes - Komal Khalid; Mehr Un Nissa Bashir; Muhammad Usman Rashid; Naila Malkani (Natural Product Research, 2026)

In-silico screening of anti-cancer natural compounds targeting NF-κB as identification of potential therapeutic inhibitor - Jarin Tasnim; Md. Mehedi Hasan; Qandeel Fatima; Laiba Rashid; Sarnop Sarker; Khan Rajib Hossain; Mamoona Nisar; Md. Tamzid Hossain Molla; Muhammad Imtiaz Shafiq; Mohammad Taufiq Alam (In Silico Pharmacology, 2026)

Unearthing potential of aluminum-modified biochar for saline-alkali soil rejuvenation and microbial diversity enhancement - Saba BABAR; Amanullah BALOCH; Muhammad QASIM; Jiyuan WANG; Xiangling WANG; Rashid IQBAL; Ali M. ABD-ELKADER; Khurram SHEHZAD; Xiaoyang XIA; Cuncang JIANG (Pedosphere, 2026)

Removal of hexavalent chromium from water using sulfidated nanoscale zero-valent iron: Regeneration and freeze–thaw stability, mechanism, and plant ecotoxicity - Wei Yuzhen; Cheng Aobo; Liu Bei; Ma Jushan; Muhammad Hamdan Rashid; Yu Jialu; Fasih Ullah Haider; Ma Shengyuan; Zhang Qinhu; Chu Run (Journal of Water Process Engineering, 2026)

Retraction notice to ‘Morpho-chemical characterization and source apportionment of potentially toxic metal(oid)s from school dust of second largest populous city of Pakistan’ [Environ. Res. 196 (2021) 110427] - Abdul Rehman; Guijian Liu; Balal Yousaf; Rafay Ahmed; Muhammad Saqib Rashid; Samina Irshad; Awais Shakoor; Muhammad Raza Farooq (Environmental Research, 2026)

Heat stress and thermal discomfort in construction: Implications for occupational safety and regulation - Md. Tushar Ali; Muhammad Harunur Rashid; Mohammad Khalid (Building and Environment, 2026)

Role of Nano-Silicon, Nano-Biochar, and Irrigation Strategies in Managing Tellurium Toxicity: Implications for Soil Microbiota, Wheat Yield, and Food Safety - Ghulam Murtaza; Muhammad Usman; Muhammad Azam; Muhammad Rizwan; Zeeshan Ahmed; Rehman Habib; Javed Iqbal; Gamal Awad El-Shaboury; Sajad Ali; Rashid Iqbal (Water, Air, & Soil Pollution, 2026)

Comprehensive genomic and haplotype analysis of the phytocyanin gene family reveals evolutionary expansion and functional diversification in Setaria italica - Muhammad Rashid; Muhammad Fahad; Liang Wu; Yuxin Shen (Plant Cell Reports, 2026)

Retraction Note: Optimizing callogenesis in five potential medicinal herbs for the bioactive constituents: a sustainable approach to pharmaceutical production - Muhammad Wasim Haider; Muhammad Nafees; Maryyam Bint-e-Tariq; Umar Farooq; Tanveer Hussain; Taki Demir; Asad Masood; Muhammad Samsam Raza; Abd El-Zaher M. A. Mustafa; Humaira Rizwana; Ozhan Simsek; Temoor Ahmed; et al. (Genetic Resources and Crop Evolution, 2026)

Retraction Note: Salinity effects on growth, biomass production, and genetic resources for phytoremediation potential of halophyte species in the desert - Muhammad Abid; Muhammad Rafay; Tanveer Hussain; Muhammad Azeem Sabir; Muneeb Khalid; Muhammad Madnee; Hussain Ahmed Makki; Muhammad Qasim; Ehab I. Taha; Mounir M. Bekhit; Rashid Iqbal (Genetic Resources and Crop Evolution, 2026)

Retraction Note: Unveiling the genetic diversity and host specificities of rust: morphological and molecular characterization of Berberis species - Siraj Uddin; Javed Iqbal; Banzeer Ahsan Abbasi; Shumaila Ijaz; Ghulam Murtaza; Muhammad Waseem; Umar Masood Quraishi; Atman Adiba; Reem M. Aljowaie; Saeedah Musaed Almutairi; Rashid Iqbal (Genetic Resources and Crop Evolution, 2026)

Retraction Note: Understanding rice blast: investigating biotechnological methods to speed up the development of robust rice cultivars - Nimra Rajput; Muhammad Usama Younas; Muhammad Qasim; Saima Parveen Memon; Shabana Memon; Magda Abd El-Rahman; Saltanat Aghayeva; Sezai Ercisli; Rashid Iqbal; Shimin Zuo (Genetic Resources and Crop Evolution, 2026)

Retraction Note: Study of variability, combining ability, genetics and association of different yield related traits in rice (Oryza sativa L.) genotypes - Zeeshan Ali; Muhammad Naeem; Iqra Rafiq; Rao Muhammad Ikram; M. Irfan Akram; Ehab I. Taha; Mounir M. Bekhit; Ozhan Simsek; Tolga Izgu; Temoor Ahmed; Javed Iqbal; Rashid Iqbal (Genetic Resources and Crop Evolution, 2026)

Retraction Note: Genetic characterization of selected species of family Solanaceae based on chloroplast rps14 gene - Sitara Bibi; Javed Iqbal; Banzeer Ahsan Abbasi; Sobia Kanwal; Tariq Mahmood; Muhammad Waseem; Dunia A. Al Farraj; Mohamed S. Elshikh; Rashid Iqbal (Genetic Resources and Crop Evolution, 2026)

Retraction Note: Assessment of genetic diversity in cotton genotypes using simple sequence repeat (SSR) markers: insights from interspecific and intraspecific variations - Muhammad Arslan; Akash Fatima; Fatima Javeria; Sehrish Ijaz; Umair Riaz; Gulnaz Saleem; Mounir M. Bekhit; Milad A. Mezher; Rashid Iqbal (Genetic Resources and Crop Evolution, 2026)

Retraction Note: Morphological and genetic diversity of barley (Hordeum vulgare L.) germplasm - Ayaz Ali; Rahman Ullah; Saeed Anwar; Ahmad Ali; Zahid Ullah; Hassan Sher; Javed Iqbal; Banzeer Ahsan Abbasi; Dunia A. Al Farraj; Mohamed S. Elshikh; Muhammad Qasim; Rashid Iqbal (Genetic Resources and Crop Evolution, 2026)

Synergistic effects of foliar selenium nanoparticles and aged cellulose-derived biochar on PAH immobilization and spinach health in contaminated soils - Ghulam Murtaza; Muhammad Usman; Muhammad Azam; Zeeshan Ahmed; Sajad Ali; Khairiah Mubarak Alwutayd; Rashid Iqbal (Environmental Geochemistry and Health, 2026)

Myoinositol-mediated regulation of leaf physiology, biochemistry, and water relations confers heat stress tolerance in Quinoa - Rashid Iqbal; Muhammad Sarwar; Basharat Ali; Muhammad Farrukh Saleem; Hassaan Ahmad; Muhammad Shahid; Javed Iqbal; Khairiah Mubarak Alwutayd; Dilfuza Jabborova; Sajad Ali; Ghulam Murtaza (Plant Biosystems, 2026)

Role of Acacia bark biochar in the growth of Ocimum basilicum L. under cadmium stress - Ghulam Murtaza; Muhammad Usman; Zeeshan Ahmed; Rashid Iqbal; Hossam S. El-Beltagi; Mashael Daghash Alqahtani; Usman Zulfiqar (Biodegradation, 2026)

Combined application of 5-ALA and nitric oxide improves lead detoxification and antioxidant defense in barley - Ghulam Murtaza; Muhammad Usman; Zeeshan Ahmed; Wael Elmenofy; Muhammad Aamir Manzoor; Rashid Iqbal (Biodegradation, 2026)

Molecular Characterization of Oculocutaneous Albinism in Consanguineous Pakistani Families: Unraveling Disease-Causing Pathogenic Variants in OCA2 and TYR Genes for Precision Diagnosis - Haiba Kaul; Shagufta Naz; Hafiz Ishfaq Ahmad; Nameerah Saleem; Muhammad Shakil; Sabika Firasat; Bilal Majeed; Saima Sharif; Farzana Rashid; Abdullah Etezaz; Muhammad Umer Khan (Biochemical Genetics, 2026)

Multifunctional Curcumin Nanoparticles: Oncolytic, Radical Scavenging, Regenerative, Hepatoprotective, and Bactericidal Effects - Huzaifa Hanif; Shahzad Hussain; Umer Rashid; Tafail Akbar Mughal; Muhammad Naeem Ahmad; Muhammad Waseem (Cell Biochemistry and Biophysics, 2026)

YOLOv8n-PFA: a parallel fusion attention network for enhanced target detection in challenging environments - Muhammad Rashid; Junfeng Wang; Faheem Ahmed; Naeem Ahmed; Syed Agha Hassnain Mohsan; Eatedal Alabdulkreem; Samih M. Mostafa (Frontiers in Marine Science, 2026)
Introduction Underwater target detection plays a crucial role in marine environmental monitoring and ocean exploration. However, accurate detection remains challenging due to low illumination, blurred small objects, and complex background interference. Although convolutional neural network-based detectors have improved detection performance, many existing approaches are computationally expensive, limiting their deployment on resource-constrained underwater platforms. Methods To address these challenges, we propose YOLOv8n-PFA, a lightweight and high-precision underwater object detection framework. The proposed method introduces a novel Parallel Fusion Attention (PFA) module that models channel and spatial attention in parallel using residual connections to enhance discriminative features while suppressing background noise. The Wise Intersection over Union (WIoUv3) loss is incorporated to stabilize training and improve localization accuracy. Additionally, depth-wise convolutions (DWConv) are strategically applied to reduce model parameters and computational complexity. To further validate generalization capability, the PFA module is also integrated into YOLOv11n. Results Experimental results show that YOLOv8n-PFA achieves 84.2% mean Average Precision (mAP) on the URPC2020 dataset with 2.68 M parameters and 7.7 GFLOPs, and 84.8% mAP on the RUOD dataset with 2.98 M parameters and 7.9 GFLOPs. When integrated into YOLOv11n, the model achieves 84.7% mAP on URPC2020 and 85.3% on RUOD with only 2.76 M parameters and 6.5 GFLOPs. Across both datasets, the proposed approach improves mAP by 2.8-4.1% over baseline models while maintaining a lightweight architecture. Discussion The results demonstrate that the proposed framework provides an effective and computationally efficient solution for real-time underwater target detection in challenging marine environments. The consistent performance gains across different YOLO generations further confirm the scalability and robustness of the proposed PFA module.

A comprehensive review on microplastics: Their presence in surface and ground water, environmental distribution, and impact on human and aquatic systems - Khashia Rashid; Shaukat Ali; Asif Hanif Chaudhry; Nosheen Sial; Muhammad Rizwan Akram; Muhammad Aslam (Science of The Total Environment, 2026)

Arbuscular mycorrhizal symbiosis Drives rhizosphere-regulated drought tolerance in maize - Ghulam Murtaza; Muhammad Usman; Khairiah Mubarak Alwutayd; Rashid Iqbal (Rhizosphere, 2026)

Combined effect of different calcination temperatures and non-equilibrium low-pressure plasma on photocatalytic activity of bi-phasic heterostructured CuMoO4-ZrO2/GO composite - Mahwish Iqbal; Tehmeena Ishaq; Muhammad Ahsan Rashid; Mahreen Iqbal; Haq Nawaz Bhatti (Journal of Water Process Engineering, 2026)

Transient mixed convection in coaxial pipes with temperature-dependent variable density - Bakhtawar Bibi; Ali B.M. Ali; Muhammad Ashraf; Ghulam Rasool; Muhammad Usman Rashid; Abduvali Sottarov (Dynamics of Atmospheres and Oceans, 2026)

Evaluation of Genetic Diversity, Yield, and Its Associated Traits in Rice (Oryza Sativa L.) Genotypes - Zeeshan Ali; Muhammad Naeem; Iqra Rafiq; Abdul Rehman; Shabir Ahmad; Khairiah Mubarak Alwutayd; Fatmah Ahmed Safhi; Javed Iqbal; Rashid Iqbal (Plant Molecular Biology Reporter, 2026)

Integrative analysis of rhizosphere metabolomics and root anatomical adaptations in wheat under drought stress: comparative insights from DH-11 and PK-13 - Sohail Ahmed; Muhammad Kaleem Samma; Faisal Mehdi; Kamran Yaqoub; Manzer H. Siddiqui; Amna Jabbar Siddiqui; Syed Ghulam Musharraf; Saddia Galani; Zubia Rashid; Hania Ahmed (Physiology and Molecular Biology of Plants, 2026)

Co-application Impacts of Silicon and Potassium Fertilizers on Wheat (Triticum Aestivum L.) Growth and Nutritional Attributes in Cadmium-contaminated Soil Under Two Irrigation Regimes - Ghulam Murtaza; Najmaldin Ezaldin Hassan; Muhammad Rizwan; Qamar uz Zaman; Gang Deng; Zeeshan Ahmed; Javed Iqbal; Mohamed S. Elshikh; Humaira Rizwana; Shabir Ahmad; Lala Gurbanova; Rashid Iqbal (Journal of Soil Science and Plant Nutrition, 2026)

Integrating phenotypic, antioxidant, and molecular analyses to identify drought-tolerant wheat genotypes for climate resilience and genetic improvement - Hafiz Ghulam Muhu Din Ahmed; Tao Yang; Mueen Alam Khan; Muhammad Irfan Akram; Rashid Iqbal; Sajid Hussain; Muhammad Danial Shafiq; Mohamed El-Zaidy; Islem Abid (Cereal Research Communications, 2026)

Glutathione role in improving leaf physiology, yield and quality of rice (Oryza sativa L.) under high temperature stress at flowering stage - Rania Baloch; Muhammad Farrukh Saleem; Muhammad Sarwar; Muhammad Awais Arshad; Muhammad Shahid; Amina Rashid (Cereal Research Communications, 2026)

Improving growth and physicobiochemical attributes of rice via PGR-based seed priming: a comparative study of establishment methods - Yousaf Saeed; Muhammad Aurangzaib; Hossam S. El-Beltagi; Khairiah Mubarak Alwutayd; Ghulam Murtaza; Lala Gurbanova; Rashid Iqbal (Cereal Research Communications, 2026)

Ligand modelling of Trachyspermum ammi phytocompounds for Aeromonas hydrophila cell wall synthesis enzyme in Labeo rohita - Muhammad Burhan Sabir; Aqeela Ashraf; Rashid Saif; Malaika Saeed; Muhammad Osama Zafar (Natural Product Research, 2026)

Species-driven variability in soil health and carbon storage across bamboo plantations - Ghulam Yasin; Syed Amir Manzoor; Muhammad Farooq Azhar; Muhammad Talha Imtiaz; Shafeeq Ur Rahman; Islem Abid; Manal Abdulaziz Binobead; Rashid Iqbal (Environmental Monitoring and Assessment, 2026)

Influence of environmental and climatic factors on AOD concentration: A model-based analysis - Md. Tushar Ali; Ashiqur Rahman; Muhammad Harunur Rashid; Quazi Hamidul Bari; Abu Reza Md. Towfiqul Islam (Urban Climate, 2026)

PFAS-driven modulation of algal organic matter enhances dissolved organic matter reactivity and disinfection by-product formation: Mechanistic elucidation via multi-spectroscopic analysis, and mitigation by coagulation and nanofiltration - Mian Jawaduddin; Zhaoyang Su; Sajid Rashid; Muhammad Saboor Siddique; Nigel Graham; Wenzheng Yu (Journal of Hazardous Materials, 2026)

Fe-and Mg-functionalized chicken manure biochar immobilized Cd, Cr, and Pb in aged soil and decreased their leaching into groundwater - Yasir Hamid; Qiang Lin; Muhammad Saqib Rashid; Muhammad Usman; Yonglong Chen; Esmat F. Ali; Hamada Abdelrahman; Temoor Ahmed; Sabry M. Shaheen; Sang Soo Lee; Xiaoe Yang (Groundwater for Sustainable Development, 2026)

The transformative role of artificial intelligence in water resources engineering: A comprehensive review - Muhammad Rashid; Adan Saeed; Mohiq Khalid; Aniqa Murtaza; Muhammad Waqar Saleem (Environmental Modelling & Software, 2026)

Multi-disciplinary reconstruction of debris flow events and dynamics in the Northern Apennines, Italy: A multi-scale approach linking ground evidence with climatic triggers - Muhammad Ahsan Rashid; Alessandro Chelli; Emma Petrella; Sara Pescio; Jacopo Melada; Veronica Manara; Bruno Arcuri; Maurizio Maugeri; Michele Brunetti; Luca Trombino; Anna Masseroli; Giovanni Leonelli (CATENA, 2026)

Remediation of Water Contaminated by Toxic Metals with Multi-metal/Co-doped Modified Biochars - Ghulam Murtaza; Muhammad Usman; Zeeshan Ahmed; Muhammad Qasim; Javed Iqbal; Shabir Ahmad; Rashid Iqbal; Lala Gurbanova; Mehdi Rahimi (Water, Air, & Soil Pollution, 2026)

Synergistic Role of Plant Growth-Promoting Rhizobacteria and Zinc Ferrite Nanoparticles in Mitigating Mercury Stress in Chickpea (Cicer arietinum L.) - Waqar Younas; Hina Khan; Humera Amin; Sami Ullah; Abd Ullah; Usman Ali; Muhammad Nafees; Fazal Amin; Iftikhar Ahmed; Tanveer Hussain; Mohamed Taha Yassin; Rashid Iqbal (Water, Air, & Soil Pollution, 2026)

Evaluation of climate change and land-use impacts on groundwater dynamics in the bari doab canal system - Saif Haider; Muhammad Rashid; Jawad Saleem (Theoretical and Applied Climatology, 2026)
Globally, groundwater depletion has grown to be a serious issue, as land and water resources have been gravely exhausted due to the rising population's desire for food and water. The current research evaluated the decline in groundwater caused by land use and climate change in the Bari Doab Canal, Pakistan, utilizing the latest Coupled Model Intercomparison Project (CMIP6) of the global climate model (GCM). Sixteen years of data (2005–2020) from the Punjab Irrigation Department were used to generate IDW interpolation maps within the ArcGIS environment. The Penman–Monteith equation in the CROPWAT model was used to calculate crop water requirements. Cellular Automata Markov Chain model was used to create LULC maps of 2030, 2060, and 2100 by analyzing the changes based on Landsat (7 and 8) satellite imagery gathered in 2000, 2010, and 2020. Groundwater extraction was estimated through the deficit of effective rainfall and net canal water use from evapotranspiration after compensating for soil moisture storage changes. GCM projected rainfall and temperature under two Shared Socioeconomic Pathways (SSPs), SSP2 and SSP5, were downscaled using the CMhyd model till the end of the twenty-first century. The precipitation, maximum and minimum temperatures, and crop water requirements were anticipated to increase by downscaled projections of a selected model (MPI-ESM1-2-HR) till the end of the twenty-first century (2015–2100) compared to the baseline period (1981–2020). The water table dropped by 0.62 m annually over 16 years (2005–2020). Urbanization increased steadily from 2000 to 2100, while all other categories, water, dense vegetation, vegetation, and barren land experienced a decline. The Visual MODFLOW model outcomes demonstrated the detrimental effects of the expected changes in land use and climate on the groundwater in Bari Doab. This study supports the development of appropriate adaptation measures by policymakers and stakeholders to mitigate the detrimental impacts of climate and land use change on groundwater dynamics.

Determination of the Chemical Profile of Hibiscus rosa-sinensis L. Leaves Using Different Solvents and Evaluation of their Antioxidant, Antimitotic, and Antiproliferative Potentials - Sehrish Sadia; Muhammad Waheed; Tahira Rashid; Murad Muhammad; Huma Bashir; Fahim Arshad; Muhammad Iqbal; Abeer Hashem; Khalid F. Almutairi; Elsayed Fathi Abd-Allah (Journal of Pharmaceutical Innovation, 2026)

The influence of community perceptions and practices on the sustainability of Pulau Kapas Marine Park - Muhammad Naqib Hasri; Nazli Aziz; Nurul Huda Sapehee; Nur Qamarina Mohmad Fuad; Ahmad Irsyad Ahmad; Tengku Balkis Tunku Shahar Tengku Abdul Rashid; Nurashiqin Sallih Udin; Abdul Rahman Abdul Latip (Journal of Coastal Conservation, 2026)

Novel insights into in-situ and ex-situ production of geological ammonia from rocks - Muhammad Imran Rashid (Next Research, 2026)

Tectono-magmatic evolution of the Ambela granitic complex, Northwest Himalayas, Pakistan: Insights from LA-ICP-MS U–Pb zircon geochronology, Lu–Hf isotope, and trace element geochemistry - Mehboob ur Rashid; Hafiz U. Rehman; Hao-Yang Lee; Sun-Lin Chung; Kaushik Das; Muhammad Jawad Zeb; Nasir Ahmad; Muhammad Hussain; Hiroshi Yamamoto (Journal of Asian Earth Sciences, 2026)

Macroscale spatiotemporal variability of Beryllium-7 and Lead-212 in surface air driven by meteorological factors - Faisal Izwan Abdul Rashid; Mohd Idzat Idris; Irman Abdul Rahman; Muhammad Rawi Mohamed Zin (Environmental Research, 2026)

Magnetic Bentonite for Efficient Phosphate Removal from Wastewater: A Sustainable Strategy to Combat Eutrophication - Khizar Hussain Shah; Muhammad Imtiaz Rashid; Javairia Zubair; Saba Zafar; Abdul Amir; Akhtar Iqbal; Khurram Shahzad; Arshid Mahmood Ali (Water, Air, & Soil Pollution, 2026)

Disease-resistant grape hybrid development through embryo rescue techniques - Qandeela Nigar; Mahmood ul Hassan; Rashid Mehmood Rana; Irfan Ali; Muhammad Usman Raja; Gamal Awad El-Shaboury; Sajad Ali; Rashid Iqbal (Plant Cell, Tissue and Organ Culture (PCTOC), 2026)

Mitigating cadmium-stressed spinach by the synergistic effect of vermicompost and selenium: associated heath risks assessment - Taiba Rauf; Kamran Ashraf; Zeeshan Ahmed; Rabiya Nasir; Muhammad Zeeshan Mansha; Qamar uz Zaman; Ghulam Murtaza; M. Ajmal Ali; Mohamed S. Elshikh; Rashid Iqbal; Lala Gurbanova; Nazim S. Gruda (Environmental Geochemistry and Health, 2026)

Cardiometabolic Dysregulation and PON1 Genetic Susceptibility in Chronic E-waste Recyclers Exposed to Potentially Toxic Elements - Aneela Shoukat; Syed Muhammad Nurulain; Rashid Nazir Qureshi; Amina Zafar; Sabir Hussain; Sosan Andleeb Khan; Sajid Mehmood; Sadia Asmat; Saqlain Raza; Syed Tahir Abbas Shah (Cardiovascular Toxicology, 2026)

Photocatalytic Degradation of Synozol Navy Blue Dye Using Ni-Ag Co-doped ZnO: Optimization, Mechanistic, Scavenging and Kinetics Studies - Zahid Mehmood; Muhammad Alamzeb; Tahseen Ghous; Sidra Rashid; Zulfiqar Ali; Muhammad Haseeb; Sabah Ansar; William N. Setzer (Journal of Fluorescence, 2025)

Pathogenic CDKN2A germline variants are rare in a cohort of unselected pancreatic cancer patients from Pakistan - Shumaila Arif; Noor Muhammad; Humaira Naeemi; Muhammad Usman Rashid (Familial Cancer, 2025)

Climate-responsive cropland dynamics in Indus Basin: A comprehensive SDM assessment with intra-seasonal variability - Fatima Ilyas; Muhammad Azmat; Swera Javed; Shakil Ahmad; Muhammad Arshad; Muhammad Usman Rashid; Saeed Ahmad Asad (Science of The Total Environment, 2025)

Synthesis of nano-ferrites-based materials: A new paradigm for electrochemical sensors - Sajjad Hussain; Imamdin Chandio; Md Abdur Rashid; Imran Sadiq; Jameel Ahmed Baig; Shakoor Ahmed Solangi; Muhammad Shahbaz; Khalid Hussain Thebo (Journal of Environmental Chemical Engineering, 2025)

Toxic Metals in the Workplace: Assessing Heavy Metal Contaminants in Indoor Dust of Auto Parts Stores and Their Impact on Health of Employees - Nadeem Ali; Sultan H. Alamri; Jahan Zeb; Mohammad Rehan; Nisreen Rajeh; Nabil Alhakamy; Mohamed I. Orif; Muhammad Imtiaz Rashid; Syed Ali Musstjab Akber Shah Eqani; Hani Z. Asfour (Water, Air, & Soil Pollution, 2025)

Synergistic Arsenic Adsorption by Nano Zero-Valent Iron and Biochar: Batch and Column Scale Performance - Muhammad Asif Naeem; Muhammad Imran; Muhammad Amjad; Ghulam Mustafa Shah; Ghulam Abbas; Behzad Murtaza; Muhammad Shafique Khalid; Hafiz Faiq Bakhat; Samina Khalid; Muhammad Imtiaz Rashid (Water, Air, & Soil Pollution, 2025)

Predicting rice yield and impact of climate change on rice production using machine learning models - Khawaja T. Tasneem; Muhammad Umair Shahzad; Javed Rashid; Kamal M. Othman; Tania Zafar; Muhammad Faheem (Theoretical and Applied Climatology, 2025)
Climate change poses a critical threat to agricultural sustainability, with direct implications for the global food supply. Rice, a staple crop throughout Asia, is particularly vulnerable to variations in temperature and rainfall, making it essential to understand how it responds to changing climatic conditions. This study integrates historical climate records, rice yield data, and projections from Global Climate Models (GCMs; CMIP3) to assess the potential effects of climate change on rice production in Punjab, Pakistan. We employed multiple machine learning approaches, including Multiple Linear Regression (MLR), Boosted Tree Regression (BTR), Probabilistic Neural Network (PNN), Generalized Feed-Forward (GFF) Neural Network, Linear Regression (LR), and a Multilayer Perceptron (MLP) Artificial Neural Network. The models were trained and validated using observed climate and yield data from 1990 to 2020. Future yields were projected under three IPCC emission scenarios (SR-A2, SR-A1B, SR-B1) through the year 2050. Model evaluation showed that the Multilayer Perceptron (MLP) achieved the highest predictive performance ( $$R^2$$ = 0.791, R = 0.868, MAE = 0.215, MSE = 0.0869, NMSE = 0.3681), followed by Boosted Tree Regression (BTR; $$R^2$$ = 0.779, R = 0.845, MAE = 0.334, MSE = 0.1308). The Probabilistic Neural Network (PNN) and Generalized Feed-Forward (GFF) model also performed respectably ( $$R^2$$ = 0.745, R = 0.811, MAE = 0.176, MSE = 0.380 and $$R^2$$ = 0.643, R = 0.825, MAE = 0.398, MSE = 0.178, respectively). In contrast, Multiple Linear Regression (MLR) and Linear Regression (LR) performed poorly, with low $$R^2$$ values (0.535), underscoring their inability to capture the non-linear relationships between climate variables and yield. Our analysis identifies maximum temperature as the primary climatic driver of yield loss. Based on the projections, we estimate an average yield decline of 0.12% by 2050. This study demonstrates that non-linear machine learning models, particularly the MLP, are essential for reliable agricultural forecasting under climate change. The results highlight the growing vulnerability of rice production to rising temperatures and provide a robust evidence base for designing adaptation strategies, such as developing heat-tolerant rice varieties, to enhance food security in vulnerable regions.

Morpho-Biochemical and SSR Marker-Based Genetic Diversity Assessment in Fig (Ficus carica) Genotypes - Muhammad Shahid Mumtaz; Muhammad Nafees; Ishtiaq Ahmad; Maryam; Adel A. Rezk; Jian Huang; Rashid Iqbal (Plant Molecular Biology Reporter, 2025)

Genetic Mechanisms and Improvement Strategies for Rice Sheath Blight Resistance - Muhammad Usama Younas; Bisma Rao; Muhammad Qasim; Irshad Ahmad; Zhiming Feng; Saima Parveen Memon; Rashid Iqbal; Shimin Zuo (Plant Molecular Biology Reporter, 2025)

Association of PD-1 immune checkpoint polymorphisms with oral cancer risk: results from a Pakistani case-control study - Iqra Mubeen; Arifa Shabbir; Ezzat M. Awad; Humaira Naeemi; Talin Barisani-Asenbauer; Muhammad Usman Rashid; Naila Malkani (Molecular Biology Reports, 2025)

Evaluation of Agronomic Traits and Bioactive Compounds in Five Mentha Species Under Soil-Based and Hydroponic System - Muhammad Azam Khan; Ismara Naseem; Muhammad Tahir Akram; Umer Habib; Rashid Mehmood Rana (Journal of Soil Science and Plant Nutrition, 2025)

Flavones-Fortified Biochar Enhances Barley (Hordeum Vulgare L.) Growth and Productivity by Ameliorating Cadmium and Copper Toxicity - Ghulam Murtaza; Muhammad Bilawal Junaid; Faisal Mahmood; Muhammad Usman; Muhammad Azam; Muhammad Rizwan; Alanoud T. Alfagham; Javed Iqbal; Gang Deng; Zeeshan Ahmed; Trobjon Makhkamov; Lala Gurbanova; et al. (Journal of Soil Science and Plant Nutrition, 2025)

Unveiling the Potential of Garcinia Atroviridis Root-Derived Phenolic Compounds Against Breast Cancer: Isolation, Network Pharmacology and In-Silico Approaches - Nur Salsabila Binti Ahmad Roslan; Miah Roney; Abdul Rashid Issahaku; Md. Nazim Uddin; Mohd Fadhlizil Fasihi Mohd Aluwi; Seema Zareen; Anke Wilhelm; Ahmad Mahfuz Gazali; Muhammad Nadeem Akhtar; Normaiza Binti Zamri (Journal of Pharmaceutical Innovation, 2025)

Assessment of tourist littering behavior using an innovative monitoring technique at No. 1 bathing Beach, Qingdao, China - Rashid Pervez; Chao Jia; Marium Sardar; Zafar Ullah Jattak; Jawad Ali; Muhammad Fahad Sardar; Zhongping Lai (Journal of Coastal Conservation, 2025)

Spatial Distribution, Characterization and Ecological Risk Assessment of Microplastic Pollution in Different Environmental Matrices of River Ravi, Pakistan - Sara Shamshad; Safdar Sidra; Asia Iqbal; Aamna Ishaq; Afzal Nimra; Muhammad Muddassir Ali; Syed Ghulam Mohayud Din Hashmi; Muhammad Rashid; Fariha Arooj; Abdul Qadir; Rida Ahmad; Zulfiqar Ali (International Journal of Environmental Research, 2025)

Improving Soil Fertility, Seed Yield, and Oil Quality of Sunflower Through Application of Processed Animal Manure Under Rainfed Conditions - Ghulam Abbas Shah; Mughees Mustafa; Zheli Ding; Zahid Mahmood; Faheem Khan; Shujaat Hussain Khan; Safdar Ali; Ghulam Mustafa Shah; Imran Mahmood; Muhammad Bilawal Junaid; Munirah Abdullah Al-Dosary; Muhammad Habib Ur Rehman; et al. (International Journal of Plant Production, 2025)

Mechanisms of S-phase arrest and mitochondrial dysfunction in complex III by DHODH inhibitors in tumorigenic TNBC cells - Muhammad Aiman Akmal Shahhiran; Mohamad Fairus Abdul Kadir; Nurshamimi Nor Rashid; Puteri Shafinaz Abdul-Rahman; Shatrah Othman (Histochemistry and Cell Biology, 2025)

Using taxonomic tools to investigate palynological record of fossil plants from Pakistan - Shabir Ahmad; Mushtaq Ahmad; Rozina; Ateef Ullah; Hussain Shah; Amir Shahzad; Muhammad Abdullah; Khushdil Khan; Shadab Khan; Rashid Iqbal; Saltanat Aghayeva (Genetic Resources and Crop Evolution, 2025)

Cutting edge: ferroptosis in metabolic dysfunction-associated steatotic liver disease (MASLD) pathogenesis and therapy - Amr Ali Mohamed Abdelgawwad El-Sehrawy; Teeba Ammar Rashid; Muhammad Ikram Ullah; Subasini Uthirapathy; Subbulakshmi Ganesan; Abhayveer Singh; Anita Devi; Kamal Kant Joshi; Ahmed Salman Jasim; Abed J. Kadhim (Functional & Integrative Genomics, 2025)

Energy-based fragility assessment of reinforced concrete bridges considering cumulative seismic demand under mainshock-aftershock sequences - Muhammad Rashid; Mayuko Nishio (Bulletin of Earthquake Engineering, 2025)

Physio-biochemical alterations and phytoremediation potential of hemp cultivated in ciprofloxacin (CIP)-contaminated soil: groundbreaking and enduring solution - Ghulam Murtaza; Muhammad Usman; Muhammad Rizwan; Javed Iqbal; Hassan Mehmood; Hossam S. El-Beltagi; Khairiah Mubarak Alwutayd; Gamal Awad El-Shaboury; Rashid Iqbal (Biodegradation, 2025)

Mitigating Fruit Drop Challenges: Unraveling the Role of Plant Growth Regulators and Micronutrients in Jujube (Ziziphus mauritiana L.) cvs. in the Cholistan Desert, Pakistan - Abdul Haseeb Ahmed; Rashad Qadri; Khalid Hussain; Muhammad Tahir Akram; Muhammad Azam; Muhammad Awais Ghani; Muhammad Mumtaz Khan; Muhammad Asif Rai; Basharat Ali; Abd El-Zaher M. A. Mustafa; Mohamed S Elshikh; Ghulam Murtaza; et al. (Applied Fruit Science, 2025)

Phytoremediation potential of native tree species for lead removal under domestic wastewater irrigation: a nature-based solution for urban water pollution - Amina Kanwal; Muhammad Farhan; Mehmooda Munazir; Hossam S. El-Beltagi; Qaiser Farid Khan; Qamar uz Zaman; Huma Qureshi; Tauseef Anwar; Wajid Zaman; Dilbar Bazarbayeva; Khairiah Mubarak Alwutayd; Muneera A. Saleh; et al. (Environmental Monitoring and Assessment, 2025)

Turn-off Fluorimetric Detection of Fe3+ Metal Ions by a Schiff Base Probe (E)-2-(((2-hydroxy-4-sulfonaphthalen-1-yl) imino) methyl) Benzoic Acid: A Combined Experimental and Theoretical Study - Muhammad Shahbaz; Muhammad Aqib Khurshid; Muhammad Ejaz; Mazhar Amjad Gilani; Maham Saeed; Ayesha Shahzad; Sundas Shahzad; Rashid Masih; Shahzad Sharif (Journal of Fluorescence, 2025)

Simulation-based assessment of the impact of conservation tillage and strip intercropping on soil microbial biomass carbon - Sana ur Rehman; Xiaoping Xin; Shahzada Sohail Ijaz; Shroz Fatima; Ayesha Siddiqa; Hayder Bin Khalid; Imran Haider; Rashid Iqbal; Aqib Mahmood; Sajad Hussain; Atta Mohi Ud Din; Taqi Raza; et al. (CATENA, 2025)

High-performance clay and K2CO3-Modified sludge biochar for efficient reactive black-5 Removal: Mechanistic insights and alleviation of phytotoxicity - Muhammad Arif; Guijian Liu; Muhammad Zia-ur-Rehman; Qumber Abbas; Aniqa Ashraf; Muhammad Saqib Rashid; Krzysztof Pikon; Balal Yousaf (Biomass and Bioenergy, 2025)

Distinct impact of oxidation reactions on the evolution of pore structures during H3PO4 activation of aliphatic-rich poplar and aromatic-rich lignin - Qurshia Choudhry; Mengjiao Fan; Zahra Essa Khan; Baihong Li; Shu Zhang; Zanib Anwar; Muhammad Rashid; Xun Hu (Biomass and Bioenergy, 2025)

Development of starch-based composite electrodes for sustainable energy applications in bio-electrochemical systems - Sobia Naseem; Muhammad Rizwan; Ayesha Sadiqa; Muhammad Rashid Zulfiqar (Biomass and Bioenergy, 2025)

Bacillus species compatibility enhances VOC-mediated systemic resistance against Botrytis cinerea - Abdur Rashid Khan; Qurban Ali; Xuxiang Wu; Sheng Chen; Muhammad Ayaz; Hamza Tariq; Muhammad Saqib Bilal; Li Li; Sunil Mundra; Qin Gu; Huijun Wu; Xiaobo Li; et al. (World Journal of Microbiology and Biotechnology, 2025)

Retraction Note: Integrated agri-aquaculture of Lactuca sativa and Cyprinus carpio improve yield and economic benefits of small-scale farmers - Sanaullah Sattar; Muhammad Muneeb; Abdul Majeed Saim; Wali Muhammad Mangrio; Farhan Nabi; Muhammad Bilawal Junaid; Atta Mohi Ud Din; Munirah Abdullah Al-Dosary; Imran Haider; Rashid Iqbal (Aquaculture International, 2025)

Corrigendum to ‘Metal ferrites-based nanocomposites and nanohybrids for photocatalytic water treatment and electrocatalytic water splitting’ [Chemosphere 310 (2023) 136835] - Ahmad Farhan; Javeria Arshad; Ehsan Ullah Rashid; Haroon Ahmad; Shahid Nawaz; Junaid Munawar; Jakub Zdarta; Teofil Jesionowski; Muhammad Bilal (Chemosphere, 2025)

Design and development of industrial prototype of spot specific orchard sprayer using ultrasonic sensing system and advanced pressure control mechanism - Arshed Ahmed; Shoaib Rashid Saleem; Muhammad Naveed Tahir; Shahram Hamza Manzoor; Qamar Zaman; Zhao Zhang; Rashed Ahmed (Computers and Electronics in Agriculture, 2025)

Distinct gonadotropin receptor profiles across follicle sizes reveal potential mechanism for follicular co-dominance in goats - Waqas Ahmad; Muhammad Suleman; Jawad Akhtar; Amjad Riaz; Khalid Javed; Muhammad Imran Rashid; Muhammad Irfan-ur-Rehman Khan (Theriogenology, 2025)

Corrigendum to “Elucidating arsenic-induced stress responses in maize genotypes: Unravelling biochemical, physiological, and nutrient homeostasis for enhanced resilience” [Sci. Total Environ. 998 (2025) 180305] - Muhammad Ali Shah; Jiu Yang Mao; Rayyan Khan; Haseeb Ahmad; Shahid Ali; Kashif Khan; Muhammad Asad Naseer; Rida Rashid; Li Yang; Xun Bo Zhou (Science of The Total Environment, 2025)

Elucidating arsenic-induced stress responses in maize genotypes: Unravelling biochemical, physiological, and nutrient homeostasis for enhanced resilience - Muhammad Ali Shah; Jiu Yang Mao; Rayyan Khan; Haseeb Ahmad; Shahid Ali; Kashif Khan; Muhammad Asad Naseer; Rida Rashid; Li Yang; Xun Bo Zhou (Science of The Total Environment, 2025)

Genome-wide identification, characterization and expression analysis of CsC3H gene family in cucumber (Cucumis sativus L) under various abiotic stresses - Saleem Uddin; Sadia Gull; Hafiz Athar Hussain; Umer Mahmood; Muhammad Qasim; Farah Kamal; Abdel-Rhman Z. Gaafar; Saltanat Aghayeva; Rashid Iqbal; Xiaohong Yang (Plant Science, 2025)

Comprehensive investigation of the smouldering characteristics of hemic peat under varying moisture conditions and the combined influence of wind velocity and direction - Nor Azizah Che Azmi; Ahmad Safuan A Rashid; Nazirah Mohd Apandi; Abd Wahid Rasib; Mohd Nazri Mohd Nasir; Adnan Zainorabidin; Mohamad Sofi Mohamed; Muhammad Amir Mat Shah; Diana Che Lat; Afiqah Ismail (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

Magnetic biochar for the remediation of arsenic contaminated water: A complete guide of science, synthesis, and solutions - Yasir Hamid; Yonglong Chen; Muhammad Haris; Muhammad Usman; Bilal Hussain; Muhammad Saqib Rashid; Temoor Ahmed; Muhammad Noman; Xiaoe Yang (Journal of Environmental Chemical Engineering, 2025)

Mechanistic insights of facile synthesized-solar driven TiO2 intercalated 2D molybdenum disulfide evaporator for one-pot clean water production - Nurul Syazana Fuzil; Nur Hashimah Alias; Nur Hidayati Othman; Muhammad Shafiq Mat Shayuti; Norazah Abd Rahman; Zulkifli Abdul Rashid; Ahmad Fauzi Ismail; Anwar Ul-Hamid; Izumi Ichinose (Desalination, 2025)

Enhancing rice crop resistance against brown plant hopper infestation through the foliar application of sodium nitroprusside - Muhammad Farooq; Dan-Dan Zhao; Saleem Asif; Jae-Ryoung Park; Mohamed H. Helal; Rashid Iqbal; Zakirullah Khan; Kyung-Min Kim (Plant Molecular Biology, 2025)

Effect of pollen sources on biochemical indices and hybrid authentication in date palm (Phoenix dactylifera L.) cv. Khadrawy - Maryam; Ishtiaq Ahmad; Muhammad Nafees; Muhammad Saqib; Mona S. Alwhibi; Mohamed S. Elshikh; Mehmet Ramazan Bozhuyuk; Javed Iqbal; Shabir Ahmad; Trobjon Makhkamov; Ghulam Murtaza; Rashid Iqbal (Genetic Resources and Crop Evolution, 2025)

Propolis enhanced sodium alginate hydrogel enriched with copper doped mesoporous bioactive glass nanoparticles for advanced burn care applications - Aqsa Aizaz; Muhammad Haseeb Nawaz; Muhammad Sameet Ismat; Md Abdur Rashid; Muhammad Atiq Ur Rehman (Biotechnology Letters, 2025)

Recent advances in layered double hydroixdes@MXene (LDHs@MXene) composites: Synthesis, properties, and catalytic applications - Sundas Riaz; Sami Ullah; Sanam Bashir; Aziz ur Rehman; Rashid Iqbal; Tayyaba Najam; Mostafa A. Ismail; Md Rezaul Karim; Syed Shoaib Ahmad Shah; Muhammad Altaf Nazir (Applied Clay Science, 2025)

How do land use changes affect temperature and groundwater in urban areas? An integrated remote sensing, and machine learning approach - Sareer Ahmad; Rashid Farooq; Muhammad Waseem; Silvia Kohnová (Advances in Space Research, 2025)

Varietal and Geographic Influences on Fruit Quality Traits of Pomegranate (Punica granatum L.) - Muhammad Umair; Ishtiaq Ahmad Rajwana; Kashif Razzaq; Sami Ullah; Umair Riaz; Rashid Iqbal; Saltanat Aghayeva; Maximilian Lackner (Applied Fruit Science, 2025)

Evaluating the Impact of Triacontanol on Physiological, Enzymatic and Biochemical Responses of Psidium Guajava L. Under Salinity Stress - Khalid Hussain; Rashad Qadri; Rashid Iqbal Khan; Abdul Haseeb Ahmed; Muhammad Azam; Muhammad Tahir Akram; Muhammad Imran Khan; Aneeqa Arshad; Swati Shrestha (Applied Fruit Science, 2025)

Dinaphthodiospyrol H: a natural α-glucosidase inhibibitor extracted from Diospyros kaki L.f - Abdur Rauf; Taghrid S. AlOmar; Umer Rashid; Zubair Ahmad; Sofia Kanwal; Najla Almasoud; Naveed Muhammad; Margrate Anyanwu; Alessandra Gianoncelli; Giovanni Ribaudo (Natural Product Research, 2025)

Selenium mitigates boron toxicity in Nicotiana tabacum via altering root anatomy, accumulation of boron, biochemical and physiological aspects - Ghulam Murtaza; Zeeshan Ahmed; Gang Deng; Sohail Akhtar; Muhammad Rizwan; Muhammad Usman; Mona S. Alwahibi; Humaira Rizwana; Tolga İzgü; Özhan Şimşek; Rashid Iqbal; Faisal Zulfiqar (Plant Biosystems, 2025)

Cytotoxicity of Physalis minima Linn (Solanaceae) fruit against HCT116 and HT29 colorectal cancer cell lines - Wei Lun Ng; Jen Kit Tan; Charles Gnanaraj; Muhammad Dawood Shah; Nurshamimi Nor Rashid; Iskandar Abdullah; Yoong Soon Yong (Natural Product Research, 2025)

Biofumigation with carvacrol disrupts membrane integrity and metabolic homeostasis in yam leaf spot pathogen Alternaria alternata - Hamza Tariq; Wenwu Zou; Lanning Wang; Jingkun Lv; Abdur Rashid Khan; Muhammad Saqib Bilal; Danyu Shen; Daolong Dou (Pesticide Biochemistry and Physiology, 2025)

Dispersion stability of a water-based ternary hybrid nanofluid with Al2O3, CuO, and graphite: an experimental and RSM modeling approach - Md. Ramim-Ul Hasan; Tanjimur Rashid; Md. Emdadul Hoque; Muhammad Aziz; Md. Sanowar Hossain (Next Research, 2025)

The evolving role of biphasic solvents in CO2 capture: Recent developments, deployment challenges, and opportunities for AI-assisted screening - Ahmad Saeed; Muhammad Abdul Qyyum; DongYoung Lee; Rashid Al-Hajri (Chemical Engineering Journal, 2025)

Phycocyanin as a sustainable future resource: A review on recent advancements, fundamental challenges, opportunities and applications - Haider Ali; Rashid Iftikhar; Muhammad Ali Inam; Muhammad Umer Abbas; Sahar Saleem; Faras Ahmad Shahbaz; Humayun Nadeem; Aleena Tahir; M. Momin (Bioresource Technology Reports, 2025)

Correction: Multivariate and Association Analyses of Various Seed Yield Contributing Traits Divulge Genetic Diversity Among Pisum sativum L. Genotypes - Noshi Parveen; Shamim Umer; Changwei Tan; Abdul Jabbar; Bilqees Kanwal; Imran Haider; Waqas Raza; Anwer Usma; Aqib Mahmood; Muhammad Bilawal Junaid; Salman Haidar Abbasi; Alanoud T. Alfagham; et al. (Plant Molecular Biology Reporter, 2025)

Integrated Approaches for Enhancing Magnaporthe oryzae Resistance: Mechanisms and Breeding Strategies - Muhammad Usama Younas; Muhammad Qasim; Irshad Ahmad; Zhiming Feng; Rashid Iqbal; Tanweer Fatah Abro; Shabir Ahmad; Xiaohong Jiang; Nimra Rajput; Shimin Zuo (Plant Molecular Biology Reporter, 2025)

Multivariate and Association Analyses of Various Seed Yield Contributing Traits Divulge Genetic Diversity Among Pisum sativum L. Genotypes - Noshi Parveen; Shamim Umer; Changwei Tan; Abdul Jabbar; Bilqees Kanwal; Imran Haider; Waqas Raza; Anwer Usma; Aqib Mahmood; Muhammad Bilawal Junaid; Salman Haidar Abbasi; Alanoud T. Alfagham; et al. (Plant Molecular Biology Reporter, 2025)

Multi-centric clinical implementation of the remote and automated quality control programme for digital imaging in Malaysia: challenges and pitfalls - Vinoshah S. Ravichandran; Nur Ammi Hamzah; Li Kuo Tan; Virginia Tsapaki; Olivera Ciraj Bjelac; Noramaliza Mohd Noor; Nur Syahiirah Mohamad Mokhtar; Nur Hasyimah Abd Rashid; Adiela Saiful Fazad; Nur Hafizah Zakaria; Siti Norsyafiqah Mohd Mystafa; Wan Nur Ain Wan Ghazali; et al. (Physical and Engineering Sciences in Medicine, 2025)

Maize/Legume Intercropping Increases Nutrient Uptake, Crop Yields, Land Productivity, and Economic Profits in Resource-intensive Arid-irrigated Areas - Muhammad Ali Raza; Atta Mohi Ud Din; Hassan Shehryar Yasin; Hina Gul; Ghulam Abbas Shah; Wang Zhiqi; Muhammad Jawad Hassan; Muhammad Bilal; Harun Gitari; Rashid Iqbal; Noorah Al Kubaisi; Mohamed S. Elshikh; et al. (Journal of Soil Science and Plant Nutrition, 2025)

Comparative Efficacy of Different Rice (Oryza sativa L.) Genotypes for Improved Zinc and Iron Uptake and Relevant Yield Efficiency under their Foliar Application - Shafiq ur Rahman Memon; Saima Parveen Memon; Muhammad Qasim; Huagang Huang; Abd El-Zaher M. A. Mustafa; Mohamed S. Elshikh; Rashid Iqbal; Zicheng Zheng (Journal of Soil Science and Plant Nutrition, 2025)

Modulation of inflammatory and oxidative stress pathways by polyphenol-rich Pleurospermum candollei extract in carrageenan-induced paw edema in rats - Mehreen Fatima; Muhammad Rashid Khan; Motrih Al-Mutiry; Mitesh Patel; Nawaf Alshammari; Mohd Adnan (Inflammopharmacology, 2025)

Managing water deficit in wheat through mulches and irrigation techniques in semi-arid regions - Salman Ahmad; Muhammad Aown Sammar Raza; Muhammad Ali; Rashid Iqbal; Muhammad Usman Aslam; Monika Toleikiene; Abd El-Zaher M. A. Mustafa; Humaira Rizwana; Imran Haider; Muhammad Zain; Saltanat Aghayeva; Ozhan Simsek; et al. (Cereal Research Communications, 2025)

Life cycle greenhouse gas emission reduction potential of alternate wetting and drying in rice cultivation under Malaysian major granary areas - Nurul Ain Abu Bakar; Mohd Saufi Bastami; Muhammad Hariz Abdul Rahman; Rozimah Mohd Rasdi; Mohd Aziz Rashid; Shahida Hashim; Mohd Najib Mohd Yusof; Fauzi Jumat; Mohd Fairuz Md Suptian (Journal of Cleaner Production, 2025)

Recent advances in nanocatalysis for clean energy and carbon neutral applications - Jamshaid Rashid; Ayesha Arif; Pir Muhammad; Ming Xu; Rajeev Kumar (Fuel, 2025)

Enhanced catalytic stability for L-Dopa synthesis through cross-linking of Al₂O₃ nanocrystals with Bacillus subtilis tyrosine hydroxylase - Areesha Batool; Sikander Ali; Aneeba Rashid; Muhammad Usman Ahmad; Saba Sana; Luiza C. Campos (World Journal of Microbiology and Biotechnology, 2025)
This study focuses on enhancing L-Dopa synthesis by producing tyrosine hydroxylase from Bacillus subtilis SDSC-Env-i6 and its conjugation with aluminium oxide (Al₂O₃) nanoparticles. The free enzyme exhibited moderate activity, which was significantly improved through nanoparticle conjugation. Structural characterisation confirmed successful binding, with Al₂O₃ nanoparticles showing a crystalline nature and sizes ranging from 124 to 130 nm. Compared to the free enzyme, the Al₂O₃-conjugated tyrosine hydroxylase demonstrated markedly enhanced catalytic activity, reaching up to 15.3 ± 0.05 U/mL under optimised conditions. In contrast, maximum activities for the free enzyme were 5.5 ± 0.05 U/mL and 6.3 ± 0.11 U/mL in the presence of CuCl₂ and CaCl₂, respectively. The cross-linked enzyme also showed superior stability and efficiency across varying conditions. L-Dopa production was significantly higher with the conjugated enzyme, yielding between 0.531 and 1.105 mg/mL under optimised incubation conditions. These values were notably greater than those achieved using the free enzyme across different pH levels, volumes, and incubation times. Spectroscopic and microscopic analyses confirmed the integrity and functionality of the enzyme-nanoparticle complex. The observed improvements in both enzyme activity and L-Dopa yield were statistically significant ( p ≤ 0.05), underscoring the potential of Al₂O₃ nanoparticle-conjugated tyrosine hydroxylase as an efficient and scalable biocatalyst for commercial L-Dopa production. Determination of kinetic parameters showed maximum V max /K m (1.25 × 10 6 ) was observed when immobilized tyrosinase activity was characterized with tyrosine as substrate, with significant K cat value of 1.48 × 10 18 s − 1 .

Effect of MXenes, nZVI and Acacia-wood Biochar Treatments on Bioavailability Pb and Fractions in Calcareous-polluted Soils - Ghulam Murtaza; Najmaldin Ezaldin Hassan; Muhammad Usman; Gang Deng; Zeeshan Ahmed; Javed Iqbal; Mohamed S. Elshikh; Humaira Rizwana; Rashid Iqbal (Water, Air, & Soil Pollution, 2025)

Investigation of the genesis and intensification of simultaneous cyclones in the Arabian sea and Bay of Bengal in November 2020 - Abhishek Kumar; Arun Chakraborty; Mansour Almazroui; Muhammad Mubashar Dogar; Irfan Ur Rashid; Muhammad Adnan Abid; Moetasim Ashfaq (Theoretical and Applied Climatology, 2025)

Impact of Silicon-Based Treatments On the Demographic Traits of Spodoptera frugiperda in Maize - Muhammad Adeel Ghafar; Qin Feng; Inzamam Ul Haq; Moazam Hyder; Muhammad Sufian; Dilawar Abbas; Kamran Haider; Muhammad Lubaid Khalid; Muhammad Rahan Akhtar; Liande Wang; Rashid Iqbal; Noorah AlKubaisi; et al. (Journal of Crop Health, 2025)

Cyto-genotoxic assessment of bisphenol P through expression of DNA damage/repair genes in MDBK cell line - Muhammad Muddassir Ali; Samra Afzal; Maryam Javed; Imran Rashid; Furqan Awan; Asad Ullah; Tanveer Majeed; Hadeer Darwish; Ahmed Noureldeen; Jawaher Albaqami; Khalid Mehmood (In Vitro Cellular & Developmental Biology - Animal, 2025)

Palynological research and taxonomic implications of selected bee forage plants using microscopic techniques for accurate taxa identifications - Ateef Ullah; Mushtaq Ahmad; Naila Mukhtar; Shabir Ahmad; Hussain Shah; Faran Durrani; Huma Gul; Muhammad Abdullah; Nasira Bibi; Nabeel Ur Rehman; Reem M. Aljowaie; Abd El-Zaher M. A. Mustafa; et al. (Genetic Resources and Crop Evolution, 2025)

Pollen micromorphology and its taxonomic significance in the selected melliferous taxa of Upper Dir, Khyber Pakhtunkhwa: insights for honeybee-plant interactions - Tariq Ullah; Muhammad Zafar; Mushtaq Ahmad; Hussain Shah; Shabir Ahmad; Hossam M. Aljawdah; Humaira Rizwana; Rashid Iqbal; Muhammad Aizaz; Muhammad Abdullah (Genetic Resources and Crop Evolution, 2025)

Protein sparing by dietary lipids in the diets of Pangasianodon hypophthalmus: an appraisal of growth, body composition, digestive enzymes, and metabolic responses - Sadaf Khadim; Mahroze Fatima; Syed Zakir Hussain Shah; Hamda Azmat; Muhammad Afzal Rashid (Fish Physiology and Biochemistry, 2025)

Investigation of geoenvironmental contamination and risks of municipal solid waste disposal sites in urban Khyber Pakhtunkhwa, Pakistan - Muhammad Ayaz Khan; Abdullah Khan; Zia ur Rahman; Azhar Rashid; Khalid Latif (Environmental Geochemistry and Health, 2025)

Impact of Climatic Variables on Fruit Bearing Behavior and Disease Incidence in Commercial Mango Cultivars in a Semi-arid Region - Hafiz Mohkum Hammad; Talal Tariq; Shafqat Saeed; Muhammad Tariq Malik; Hafiz Faiq Siddique; Rashid Jawad; Shah Fahad; Ifrah Kanwal; Aitazaz A. Farooque (Applied Fruit Science, 2025)

New insights on the potentiality of deep learning techniques in supporting the assessment of some biotic diseases on maize - Sajjad Hussain Qureshi; Sohail Raza Chohan; Muhammad Usman; Muhammad Luqman; Mueen Alam Khan; Baber Ali; Reem M. Aljowaie; Mohamed S. Elshikh; Rashid Iqbal (Journal of Plant Pathology, 2025)

Magnetic exploration for geothermal power: a case study of Tattapani thermal spring - Mehboob Ur Rashid; Waqas Ahmed; Said Muhammad; Mohammad Arsalan Khan; Adham E. Ragab; Mohammad Mursaleen; Manzoore Elahi M. Soudagar (Acta Geophysica, 2025)

Emulsifier-free B50 biodiesel-water-ethanol emulsion fuel: A study on combustion characteristics, fuel performance, and emissions - Muhammad Adib Abdul Rashid; Ahmad Muhsin Ithnin; Wira Jazair Yahya; Wan Nur Izzati Wan Mahdi; Nurul Aiyshah Mazlan; Abdullah Aiman Zulmajdi; Dhani Avianto Sugeng; Kinoshita Eiji (Fuel, 2025)

A critical review of opportunities and challenges of solid waste management in an emerging economy- evidence from Pakistan - Sajid Rashid; Hameeda Sultan; Wajid Rashid; Bushra Danish Talpur; Roberto Xavier Supe Tulcan; Muhammad Tariq Khan; Eve Bohnett; Muhammad Safar Korai; Lixiao Zhang (Environmental Development, 2025)

Health risks associated with occupational contaminants of heavy metals across different professions - Sosan Andleeb Khan; Syed Muhammad Nurulain; Baseet Haroon Khan; Aneela Shoukat; Sajid Mehmood; Rabeet Haroon Khan; Rashid Nazir Qureshi; Amina Zafar; Ammara Younas; Syed Tahir Abbas Shah (Environmental Geochemistry and Health, 2025)

Synergistic Effects of 5-Ureidohydantoin, Rhizobacteria and Non-wood-Based Biochar on Barley Productivity Under Drought and Multiple Toxic Metals Stress - Ghulam Murtaza; Muhammad Usman; Muhammad Azam; Abdul Razzaq; Iram Saba; Gang Deng; Zeeshan Ahmed; Abdel-Rhman Z. Gaafar; Trobjon Makhkamov; Lala Gurbanova; Rashid Iqbal (Current Microbiology, 2025)

Bioaccumulation of different heavy metals and toxicity assessment using different indices in grape plants and soil around power generators in Erbil province - Zhian Rashid Salih; Nashmeel Saeed Khudhur; Maqsuda Qadir Muhammad (Environmental Monitoring and Assessment, 2025)

Fermented spent coffee ground in African catfish (Clarias gariepinus) diets: Effects on growth performance, digestive enzyme, protein digestibility, amino acid profile, and immune-related gene - Nurdiyana Aqilah Roslan; Zulhisyam Abdul Kari; Suniza Anis Mohamad Sukri; Martina Irwan Khoo; Nani Izreen Mohd Sani; Roslina Rashid; Muhammad Anamul Kabir; Shishir Kumar Nandi; Nik Nur Azwanida Zakaria; Koushik Ghosh; Hasnita Che Harun; El-Sayed Hemdan Eissa (Aquaculture, 2025)

Molecular insights into Rickettsiales in blood and ticks of two-humped camels at Gansu Province, China: With an accidental detection of Colpodella sp. - Muhammad Kashif Obaid; Xinting Lan; Qiaoyun Ren; Jehan Zeb; Jin Luo; Jifei Yang; Wenyu Jia; Xiaoqing Zan; Hong Yin; Muhammad Rashid; Guiquan Guan (Veterinary Microbiology, 2025)

Techno-economic analysis and life cycle assessment of green hydrogen production: A case study of Sur Industrial City in Oman - Noman Raza Sial; Malik Sajawal Akhtar; Muhammad Islam; Muhammad Abdul Qyyum; Rashid Al-Abri; Ahmed Al-Hatrooshi; Ala’a H. Al Muhtaseb (Sustainable Cities and Society, 2025)

Advanced characterization of hemp biomass pyrolysis: Bioenergy recovery and environmental implications - Rashid Minhas; Asif Hussain Khoja; Hajirah Kanwal; Muhammad Hassan; Arslan Khan; Syed Sheraz Daood; Israf Ud din; Ali Bahadar (Sustainable Chemistry and Pharmacy, 2025)

Machine learning-based detection and quantification of red blood cells in Cholistani cattle: A pilot study - Sami Ul Rehman; Sania Fayyaz; Muhammad Usman; Mehreen Saleem; Umer Farooq; Asjad Amin; Mushtaq Hussain Lashari; Musadiq Idris; Haroon Rashid; Maryam Chaudhary (Research in Veterinary Science, 2025)

Epidemiology and genetic characterization of Alternaria alternata causing leaf spot in Fragaria × ananassa - Nasir Mehmood; Abid Riaz; Salman Ghuffar; Sadaf Anwaar; Nyla Jabeen; Isha Shaheen; Muhammad Qasim; Salma Saeed Khan; Muhammad Rauf; Tauseef Anwar; Huma Qureshi; Ghadah Salim Abusalim; et al. (Fungal Biology, 2025)

Spatio-temporal distribution, diet and human conflict of snow leopard (Panthera uncia) in the Khunjerab National Park, Gilgit Baltistan - Saira Akber; Tariq Mahmood; Tahir Mehmood; Amjad Rashid Kayani; Muhammad Sajid Nadeem; Faraz Akrim (Food Webs, 2025)

Spatial and temporal vegetation dynamics from 2000 to 2023 in the Western Himalayan regions - Kaleem Mehmood; Shoaib Ahmad Anees; Sultan Muhammad; Gadah Albasher; Fahad Shahzad; Khadim Hussain; Qijing Liu; Rashid Ayub; Waseem Razzaq Khan (Stochastic Environmental Research and Risk Assessment, 2025)

Combined Impact of Waste Water and Farm Yard Manure on Growth of Tomato (Solanum lycopersicum L.) and Soil Health: A Sustainable Agriculture Approach - Arsalan Saghir; Muhammad Sohail Akram; Shahzad Ali; Shahla Rashid; Muhammad Ajmal Farhad; Hafiz Muhammad Tayyab Khan; Syed Ayyaz javed; Mohammad Raish; Muhammad Khubaib (Journal of Soil Science and Plant Nutrition, 2025)

Fe-Modified Biochar Improves Tobacco Productivity by Promoting Root Growth, Plant Biochemical Traits and Nicotine Level: A Three Years Field Study - Ghulam Murtaza; Muhammad Usman; Qamar uz Zaman; Zeeshan Ahmed; Mona S Alwahibi; Humaira Rizwana; Javed Iqbal; Muhammad Qasim; Rashid Iqbal; Gang Deng (Journal of Soil Science and Plant Nutrition, 2025)

Combined Application of Compost and Biogas Residues Reduces Soil and Pore Water Metal Concentration and Their Residual Toxicity to Wheat Seedlings - Iftikhar Ahmad; Ghulam Mustafa Shah; Hafiz Muhammad Shahbaz; Aftab Jamal; Muhammad Imtiaz Rashid; Muhammad Farhan Saeed; Amjad Farooq; Qasim Ali; Domenico Ronga (Journal of Soil Science and Plant Nutrition, 2025)

Inheritance of Cell Membrane Stability and Yield Components Under Drought and Salinity Stress in Bread Wheat (Triticum aestivum L.) - Sameena Naqi; Aamir Hamid Khan; Rashid Mehmood Rana; Muhammad Imran Hamza; Marcin Kiedrzyński; Muhammad Naveed Tahir; Munir Ahmad; Shah Saud; Shah Hassan; Shah Fahad (Journal of Plant Growth Regulation, 2025)

Comprehensive Genomic, Mutation, Phylogenetic, and Statistical Analysis of the Monkeypox Virus Across Multiple Countries - Imran Zafar; Faheem kanwal; Muhammad Azmat; Ahsanullah Unar; Ijaz Ali; Waqas Yousaf; Qurat ul Ain; Mohd Ashraf Rather; Nemat Ali; Mohammad Rashid Khan; Amandeep Singh Dhanju; Rohit Sharma (Indian Journal of Microbiology, 2025)

Correction: Microscopic investigations of pollen morphological research of selected melliferous taxa; honeybees pollinators-plant interactions - Ateef Ullah; Mushtaq Ahmad; Shabir Ahmad; Hussain Shah; Tehsin Ullah; Muhammad Abdullah; Khalid Mashay Al-Anazi; Mohammad Abul Farah; Rozina; Syed Nohman Gilani; Amir Shahzad; Syed Waseem Gillani; et al. (Genetic Resources and Crop Evolution, 2025)

Molecular marker based analysis of allelic variation in the spring wheat genome - Hafiz Ghulam Muhu Din Ahmed; Tao Yang; Muhammad Irfan Akram; Rashid Iqbal; Abdullah Ahmed Al-Ghamdi; Dunia A. Al Farraj (Genetic Resources and Crop Evolution, 2025)

RETRACTED ARTICLE: Genetic characterization of selected species of family Solanaceae based on chloroplast rps14 gene - Sitara Bibi; Javed Iqbal; Banzeer Ahsan Abbasi; Sobia Kanwal; Tariq Mahmood; Muhammad Waseem; Dunia A. Al Farraj; Mohamed S. Elshikh; Rashid Iqbal (Genetic Resources and Crop Evolution, 2025)

Geochemical and mineralogical characterization of Carboniferous-Triassic shales in Peninsular Malaysia: implications for hydrocarbon potential and depositional model - Alidu Rashid; Numair Ahmed Siddiqui; Abdul Halim Abdul Latiff; Nisar Ahmed; Maqsood Ahmad; Muhammad Jamil; Sohag Ali; Md. Mahmodul Islam (Carbonates and Evaporites, 2025)

Optimizing modified ecological compositions enables eco-friendly control of Tribolium castaneum in grain storage - Muhammad Mohsan; Zahid Mahmood Sarwar; Habib Ali; Inzamam Ul Haq; Ammara Riaz; Rashid Iqbal; Gadah Albasher; Mohammad Javed Ansari (International Journal of Tropical Insect Science, 2025)

Transgenerational Impact of nicotiana tabacum extract on musca domestica (diptera: muscidae) - Muhammad Jamshed Iqbal; Zhihang Zhuo; Inzamam Ul Haq; Yasir Niaz; Basharat Ali; Ammara Riaz; Habib Ali; Rashid Iqbal; Gadah Albasher; Mohammad Javed Ansari (International Journal of Tropical Insect Science, 2025)

Impact of brick dust addition on the physical and mechanical performance of pervious concrete - Md. Tushar Ali; Muhammad Harunur Rashid (Innovative Infrastructure Solutions, 2025)

The stability and in vitro digestion of resveratrol-loaded emulsion stabilized with peanut protein hydrolysate and dextran conjugate - Meiyue Wang; Guanhao Bu; Songye Shi; Ying Xin; Tingwei Zhu; Chenxian Yang; Xiaojie Duan; Muhammad Tayyab Rashid (Food Research International, 2025)

Layer-by-layer concurrent encapsulation of probiotics and bioactive compounds with supplementation in intermediary layers: An establishing instrument for microbiome recharge, core safety, and targeted delivery - Muhammad Safiullah Virk; Muhammad Abdulrehman Virk; Mehak Gul; Muhammad Awais; Qiufang Liang; Tabussam Tufail; Mingming Zhong; Yufan Sun; Abdul Qayum; Ekram Abd El-Salam; John-Nelson Ekumah; Abdur Rehman; et al. (Food Hydrocolloids, 2025)

Yield gains and resource use advantages driven by legume choice and row ratio in cotton/legume intercropping under arid-irrigated conditions - Muhammad Ali Raza; Atta Mohi Ud Din; Hassan Shehryar Yasin; Hina Gul; Amjad Saeed; Aqib Mehmood; Sana Ur Rehman; Zafar Iqbal; Rashid Iqbal; Noorah Al Kubaisi; Mohamed S. Elshikh; Ghulam Abbas Shah; et al. (Field Crops Research, 2025)

ENSO teleconnections and predictability of the boreal summer temperature over the Arabian Peninsula in C3S and Saudi-KAU seasonal forecast systems - Mansour Almazroui; M. Salman Khalid; Muhammad Adnan Abid; Irfan Ur Rashid; Shahzad Kamil; Haroon Siddiqui; M. Nazrul Islam; Muhammad Ismail; Muhammad Azhar Ehsan; Enda O'Brien; Mazen Asiri; Rayees Ahmed; et al. (Atmospheric Research, 2025)

Retraction Note: Development and evaluation of methotrexate-loaded nanoemulsion formulation for topical treatment of psoriasis - Sheikh Abdur Rashid; Faiza Naseem; Pervaiz Akhtar Shah; Hamna Batool Hashmi; Mudassar Mazher; Mohammad S. Mubarak; Javad Sharifi-Rad; Muhammad Badar (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Improving flood hazard susceptibility assessment by integrating hydrodynamic modeling with remote sensing and ensemble machine learning - Izhar Ahmad; Rashid Farooq; Muhammad Ashraf; Muhammad Waseem; Donghui Shangguan (Natural Hazards, 2025)
Floods are natural disasters with significant economic and infrastructural impacts. Assessing flood susceptibility in mountainous urban regions is particularly challenging due to the complicated interaction in which urban structures and mountainous terrain affect flood behavior. This study employs two ensemble machine learning algorithms, Extreme Gradient Boosting (XGBoost) and Random Forest (RF), to develop flood susceptibility maps for the Hunza-Nagar region, which has been experiencing frequent flooding for the past three decades. An unsteady flow simulation is carried out in HEC-RAS utilizing a 100-year return period flood hydrograph as an input boundary condition, the output of which provided the spatial inundation extents necessary for developing the flood inventory. Ten explanatory factors, including climatic, geological, and geomorphological features namely elevation, slope, curvature, topographic wetness index (TWI), normalized difference vegetation index (NDVI), land use land cover (LULC), rainfall, lithology, distance to roads and distance to rivers are considered for the flood susceptibility mapping. For developing flood inventory, random sampling technique is adopted to create a spatial repository of flood and non-flood points, incorporating the ten geo-environmental flood conditioning factors. The models’ accuracy is assessed using the area under the curve (AUC) of receiver operating characteristics (ROC). The prediction rate AUC values are 0.912 for RF and 0.893 for XGBoost, with RF also demonstrating superior performance in accuracy, precision, recall, F1-score, and kappa evaluation metrics. Consequently, the RF model is selected to represent the flood susceptibility map for the study area. The resulting flood susceptibility maps will assist national disaster management and infrastructure development authorities in identifying high flood susceptible zones and carrying out early mitigation actions for future floods.

Protective Effects of Multiple-Chemical Engineered Biochar On Hormonal Signalling, Antioxidant Pathways and Secondary Metabolites in Lavender Exposed to Chromium and Fluoride Toxicity - Ghulam Murtaza; Zeeshan Ahmed; Muhammad Usman; Qamar uz Zaman; Gang Deng; Suiyun Chen; Mona S. Alwahibi; Humaira Rizwana; Javed Iqbal; Shabir Ahmad; Rashid Iqbal (Journal of Crop Health, 2025)

Jasminum humile extract mitigates carrageenan-induced paw oedema in rats by modulating inflammatory and antioxidant signalling pathways - Mehreen Fatima; Lamya Ahmed Al-Keridis; Mohd Adnan; Nawaf Alshammari; Abdel Moneim Elhadi Sulieman; Muhammad Rashid Khan (Inflammopharmacology, 2025)

Microscopic investigations of pollen morphological research of selected melliferous taxa; honeybees pollinators-plant interactions - Ateef Ullah; Mushtaq Ahmad; Shabir Ahmad; Hussain Shah; Tehsin Ullah; Muhammad Abdullah; Khalid Mashay Al-Anazi; Mohammad Abul Farah; Rozina; Syed Nohman Gilani; Amir Shahzad; Syed Waseem Gillani; et al. (Genetic Resources and Crop Evolution, 2025)

Palynological diversity in the Rosaceae flora of Northern Khyber Pakhtunkhwa, Pakistan - Muhammad Abdullah; Mushtaq Ahmad; Zahid Ullah; Amjad Khan; Shabir Ahmad; Hussain Shah; Ateef Ullah; Mohammad Abul Farah; Okezie Emmanuel; Rashid Iqbal; Abduraimov Ozodbek; Maxmudov Azizbek; et al. (Genetic Resources and Crop Evolution, 2025)

Synthesis, Characterization, Phytochemistry, and Therapeutic Potential of Azadirachta indica Conjugated Silver Nanoparticles: A Comprehensive Study on Antidiabetic and Antioxidant Properties - Hunaiza Tahir; Farzana Rashid; Shaukat Ali; Muhammad Summer; Misha Afzal (Biological Trace Element Research, 2025)

Optimal intensity measure-based seismic fragility surfaces for curved bridges considering their sensitivity to seismic excitation direction - Muhammad Rashid; Mayuko Nishio (Earthquake Engineering and Engineering Vibration, 2025)
The effect of seismic directionality is crucial for curved bridges, a subject generally overlooked in seismic vulnerability analysis. This paper focuses on seismic fragility development as a function of seismic incidence directions for a geometrically curved bridge. A series of non-linear time history analyses were carried out for a representative finite element model of the bridge by considering actual ground motions. For reliable seismic demand models, a total of eleven intensity measures ( IM ) were analyzed based on optimality metrics. To quantify the sensitivity of fragility functions to input incidence directions, fragility surfaces were developed throughout the horizontal plane by considering spectral acceleration at one second ( Sa 1.0 ) as the optimal IM . Results show that the optimal IM ranking is insignificantly influenced by seismic directionality. However, seismic orientation influences fragility, which intensifies in higher damage states, particularly for piers. For a bridge system, the differences in median demand corresponding to the least and most vulnerable direction for slight, moderate, extensive, and collapse states are about 9.0%, 7.31%, 10.32%, and 11.60%, respectively. These results imply that while evaluating the vulnerability of curved bridges, the optimality of IM in demand estimation and the impact of seismic directionality should not be disregarded.

The potential of hydrolyzed chicken feather meal as a partial replacement for fish meal and its effects on the growth and health status of African catfish (Clarias gariepinus) fingerlings - Nik Nur Akmal ‘Aliah Abdul Rashid; Zulhisyam Abdul Kari; Parashuram Kallem; Suniza Anis Mohamad Sukri; Syed Muhammad Al-Amsyar; Noor Khalidah Abdul Hamid; Muhammad Anamul Kabir; El-Sayed Hemdan Eissa; Martina Irwan Khoo; Krishnakumar Velayudhannair; Ajay Guru (Aquaculture International, 2025)

Highly efficient phosphate extraction from water using bio-composites of nano zero valent iron supported on orange peel powder (nZVI@OPP): performance evaluation and mechanistic insights - Fahad Nadeem; Muhammad Ali Inam; Rashid Iftikhar; Safi Ullah Gill; Hira Amjad (Environmental Science and Pollution Research, 2025)

Exploring Green Practices: a Review of Carbon Dot-Based Sustainable Sensing Approaches - Kawan F. Kayani; Sewara J. Mohammed; Nian N. Mohammad; Mohammed K. Rahim; Muhammad S. Mustafa; Harez Rashid Ahmed; Wrya O. Karim; Mohammed K. Sidiq; Shujahadeen B. Aziz (Journal of Fluorescence, 2025)

Effect of soil types and moisture contents on the pupation behavior and adult emergence of Oriental fruit fly, Bactrocera dorsalis (Hendel) (Diptera: Tephritidae) - Muhammad Bilal; Muhammad Mamoon-ur-Rashid; Shabana Wazir; Muhammad Naeem; Asif Ishaq; Rana Muhammad Kaleem Ullah; Abdulrahman Saad Aldawood (International Journal of Tropical Insect Science, 2025)

Correction to: Use of methanolic plant extracts against maize weevil (Sitophilus zeamais) (Curculionidae: Coleoptera) - Muhammad Mamoon-Ur-Rashid; Riaz-ud Din; Muhammad Naeem; Mohamed Farouk Elsadek; Khalid S. Al-Numair; Mohamed S. Sheteiwy; Muhammad Muzammal; Muhammad Yasin (International Journal of Tropical Insect Science, 2025)

Exploring the impact of cold plasma-induced surface oxygen vacancies on charge carrier dynamics in Z-scheme CoMoO6/ZrO2/GO heterojunction for efficiency improvement in photocatalysis - Mahwish Iqbal; Muhammad Ahsan Rashid; Rida Fatima; Mahreen Iqbal; Haq Nawaz Bhatti (Journal of Water Process Engineering, 2025)

Enhanced microwave absorption and improved broadband with synergistic effect of nest like self-assembly of CoFe2O4/Co3O4 heterostructured composites - M. Zeeshan Ashfaq; Aamna Ashfaq; Xingxing Cheng; Hongyu Gong; Adil Saleem; Rashid Iqbal; Muhammad Sajjad; Junbin Lu; M. Mamoor; Muhammad K. Majeed (Chemical Engineering Journal, 2025)

Fish waste biorefinery: A novel approach to promote industrial sustainability - Javaeria Maqsood Gill; Syed Makhdoom Hussain; Shafaqat Ali; Abdul Ghafoor; Muhammad Adrees; Nadia Nazish; Adan Naeem; Eman Naeem; Mohammed Ali Alshehri; Eram Rashid (Bioresource Technology, 2025)

Impact of urea-molasses treated wheat straw levels in total mixed rations on growth and nutrient digestibility in Azikheli buffalo calves - Haroon Ur Rashid; Taimoor Khan; Anwar Ali Turi; Muhammad Abbas; Kalim Ullah; Isa Fusaro; Giovanni Buonaiuto; Damiano Cavallini (Tropical Animal Health and Production, 2025)
This study investigates the impact of urea molasses-treated wheat straw on growth performance and nutrient digestibility in Azikheli buffalo male calves. A longitudinal experiment was conducted on sixteen calves, randomly assigned to four experimental dietary treatments ( n = 4 per group). The experimental diets included a control group (U0) with untreated wheat straw and three groups where urea molasses-treated wheat straw replaced 33% (U33), 66% (U66), or 100% (U100) of the straw in the total mixed ration. Results indicated that increasing the proportion of urea-treated wheat straw from 0 to 100% led to significant improvements in dry matter intake (from 2931 to 4034 g/day) and organic matter intake (from 2596 to 3623 g/day). Digestibility of dry matter, organic matter, crude protein, and crude fiber also followed an increasing trend, reaching 77.42%, 81.21%, 87.10%, and 60.22%, respectively, at the highest urea-treated wheat straw level. Furthermore, weight gain was significantly greater in calves fed 100% urea-treated wheat straw, followed by those in the U66, U33, and U0 groups. Feed conversion efficiency improved substantially in the U100 and U66 groups than U33 and U0. These findings suggest that incorporating higher levels of UMTWS in total mixed rations enhances nutrient digestibility, promoting superior growth performance and feed efficiency in Azikheli buffalo calves.

Expression and characterization of the immunogenicity of rec-gp45 of Babesia bigemina using cattle - Zia-Ul-Rehman; Sarfraz-ur-Rahman; Kamran Ashraf; Muhammad Suleman; Sikandar Ali; Muhammad Imran Rashid (Tropical Animal Health and Production, 2025)

Significance of Selenium in Improving the Yield and Quality of Quinoa Under Drought - Muhammad Usman Aslam; Muhammad Aown Sammar Raza; Rashid Iqbal; Salman Ahmad; Imran Haider; Abd El-Zaher M. A. Mustafa; Humaira Rizwana; Saltanat Aghayeva; Nazim S. Gruda (Journal of Soil Science and Plant Nutrition, 2025)

RETRACTED ARTICLE: Assessment of genetic diversity in cotton genotypes using simple sequence repeat (SSR) markers: insights from interspecific and intraspecific variations - Muhammad Arslan; Akash Fatima; Fatima Javeria; Sehrish Ijaz; Umair Riaz; Gulnaz Saleem; Mounir M. Bekhit; Milad A. Mezher; Rashid Iqbal (Genetic Resources and Crop Evolution, 2025)

RETRACTED ARTICLE: ArticleNoteMorphological and genetic diversity of barley (Hordeum vulgare L.) germplasm - Ayaz Ali; Rahman Ullah; Saeed Anwar; Ahmad Ali; Zahid Ullah; Hassan Sher; Javed Iqbal; Banzeer Ahsan Abbasi; Dunia A. Al Farraj; Mohamed S. Elshikh; Muhammad Qasim; Rashid Iqbal (Genetic Resources and Crop Evolution, 2025)

RETRACTED ARTICLE: Unveiling the genetic diversity and host specificities of rust: morphological and molecular characterization of Berberis species - Siraj Uddin; Javed Iqbal; Banzeer Ahsan Abbasi; Shumaila Ijaz; Ghulam Murtaza; Muhammad Waseem; Umar Masood Quraishi; Atman Adiba; Reem M. Aljowaie; Saeedah Musaed Almutairi; Rashid Iqbal (Genetic Resources and Crop Evolution, 2025)

RETRACTED ARTICLE: Salinity effects on growth, biomass production, and genetic resources for phytoremediation potential of halophyte species in the desert - Muhammad Abid; Muhammad Rafay; Tanveer Hussain; Muhammad Azeem Sabir; Muneeb Khalid; Muhammad Madnee; Hussain Ahmed Makki; Muhammad Qasim; Ehab I. Taha; Mounir M. Bekhit; Rashid Iqbal (Genetic Resources and Crop Evolution, 2025)

Integrating physiological and molecular insights in cotton under cold stress conditions - Aamir Ali Abro; Muhammad Qasim; Mubashir Abbas; Noor Muhammad; Ijaz Ali; Shiguftah Khalid; Junaid Ahmed; Muhammad Waqas; Sezai Ercisli; Rashid Iqbal; Fang Liu (Genetic Resources and Crop Evolution, 2025)

Morphological profiling and DNA barcoding revealed genetic diversity and phylogeny of Mentha species cultivated in Pakistan - Ismara Naseem; Muhammad Azam Khan; Umer Habib; Rashid Mehmood Rana; Muhammad Qasim; Mona S. Alwahibi; Rizwana Khanum; Muhammad Shafiq; Rashid Iqbal (Genetic Resources and Crop Evolution, 2025)

RETRACTED ARTICLE: Study of variability, combining ability, genetics and association of different yield related traits in rice (Oryza sativa L.) genotypes - Zeeshan Ali; Muhammad Naeem; Iqra Rafiq; Rao Muhammad Ikram; M. Irfan Akram; Ehab I. Taha; Mounir M. Bekhit; Ozhan Simsek; Tolga Izgu; Temoor Ahmed; Javed Iqbal; Rashid Iqbal (Genetic Resources and Crop Evolution, 2025)

RETRACTED ARTICLE: Impact of elevated temperatures on the genetic and morpho-physiological traits of cotton genotypes cultivation - Aamir Ali Abro; Muhammad Qasim; Muhammad Usama Younas; Ijaz Ali; Mubashir Abbas; Noor Muhammad; Shiguftah Khalid; Junaid Ahmed; Umbreen Bibi; Muhammad Waqas; Sezai Ercisli; Fahad Al-Asmari; et al. (Genetic Resources and Crop Evolution, 2025)

RETRACTED ARTICLE: Optimizing callogenesis in five potential medicinal herbs for the bioactive constituents: a sustainable approach to pharmaceutical production - Muhammad Wasim Haider; Muhammad Nafees; Maryyam Bint-e-Tariq; Umar Farooq; Tanveer Hussain; Taki Demir; Asad Masood; Muhammad Samsam Raza; Abd El-Zaher M. A. Mustafa; Humaira Rizwana; Ozhan Simsek; Temoor Ahmed; et al. (Genetic Resources and Crop Evolution, 2025)

Physicochemical profiling and health risk evaluation of effluents from textile industries: insights from Faisalabad, Pakistan - Hina Sattar; Muhammad Anwar-ul-Haq; Humera Aziz; Umair Riaz; Ahmad Mahmood; Muhammad Rizwan; Munaza Naseem; Mona S. Alwahibi; Mohamed S. Elshikh; Muhammad Qasim; Rashid Iqbal (Toxicology and Environmental Health Sciences, 2025)

Evaluation of fipronil efficacy and first molecular report of gamma-aminobutyric acid (GABA) gated chloride channel gene of Rhipicephalus microplus ticks in China and Pakistan - Muhammad Kashif Obaid; Qiaoyun Ren; Jin Luo; Jinming Wang; Muhammad Rashid; Jehan Zeb; Xiaoqing Zan; Xinting Lan; Guangyuan Liu; Jianxun Luo; Hong Yin; Ze Chen; et al. (Veterinary Parasitology, 2025)

Impact of forage levels and physical forms on feed sorting behavior, rumen morphometry, and selected blood parameters in fattening male goats - Muhammad Irfan Malik; Muhammad Afzal Rashid; Maria Teresa Capucchio; Muhammad Bilal; Muhammad Shahbaz Yousaf; Habib Ur Rehman; Amlan Kumar Patra (Small Ruminant Research, 2025)

Comprehensive analysis of leak impacts on liquid-gas multiphase flow using statistical, wavelet transform, and machine learning approaches - Hicham Ferroudji; Muhammad Saad Khan; Abinash Barooah; Wahib A. Al-Ammari; Ibrahim Hassan; Rashid Hassan; Ahmad K. Sleiti; Sina Rezaei Gomari; Matthew Hamilton; Mohammad Azizur Rahman (Process Safety and Environmental Protection, 2025)

Magnetically recyclable Mn and Co doped r-GO based LaFeO3 nano-composite for tuning the optical and solar light driven photo-catalytic applications - Shahid Iqbal; Muhammad Jamshaid; Firdous Bibi; Najla AlMasoud; Taghrid S. Alomar; Rashid Iqbal; Qasim Raza; Ambreen Kalsoom (Journal of Water Process Engineering, 2025)

Biomitigation of noxious metal ions using engineered lignin-based nanocomposites for sustainable environment - Zaeem Bin Babar; Rashid Iftikhar; Komal Rizwan; Shahid Munir; Mashhood Urfi; Fawad Ashraf; Muhammad Ali Inam; Shahid Iqbal; Muhammad Saad; Sajid Mahmood; Nasser S. Awwad; Hala A. Ibrahium (Journal of Water Process Engineering, 2025)

Breaking barriers in energy storage: 3D printed SiOC/Bi2O3 nanocomposites for high-performance asymmetric supercapacitors - Ali Asghar; Muhammad Shahid Rashid; Muhammad Saqib; Karim Khan; Zhiyuan Liu; Changyong Liu; Zhangwei Chen (Chemical Engineering Journal, 2025)

Integration of physio-biological methods for remediation of dyes and toxic metals from textile wastewater - Muhammad Ayaz; Aqib Hassan Ali Khan; Kang Song; Asmat Ali; Sohail Yousaf; Abeer Kazmi; Abdur Rashid (Bioresource Technology Reports, 2025)

Impacts of microplastic accumulation in aquatic environment: Physiological, eco-toxicological, immunological, and neurotoxic effects - Eram Rashid; Syed Makhdoom Hussain; Shafaqat Ali; Muhammad Munir; Abdul Ghafoor; Ebru Yilmaz; Mohammed Ali Alshehri; Danish Riaz; Adan Naeem; Eman Naeem (Aquatic Toxicology, 2025)

Attributing rainfall and drought variability across climate vulnerable area of Pakistan: Perspective from different satellite and ground-based datasets - Mohammad Ilyas Abro; Ehsan Elahi; Murad Ali Khaskheli; Rashid Mustafa Korai; Mahdi Hassan; Asghar Ali Majidano; Bhai Khan Solangi; Faiz Muhammad Khokhar (Theoretical and Applied Climatology, 2025)

Development and evaluation of methotrexate-loaded nanoemulsion formulation for topical treatment of psoriasis - Sheikh Abdur Rashid; Faiza Naseem; Pervaiz Akhtar Shah; Hamna Batool Hashmi; Mudassar Mazher; Mohammad S. Mubarak; Javad Sharifi-Rad; Muhammad Badar (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Moringa Biopriming with Zn Spray Improved Nutrients Rich Biofortified Chickpea Grains and Drought Tolerance at Reproductive Stages Under Arid Environment - Hamid Nawaz; Malik Muhammad Yousaf; Nazim Hussain; Tanveer Hussain; Malik Waqar Yousaf; Malik Ibrar Yousaf; Mona S. Alwahibi; Mohamed S. Elshikh; Baber Ali; Rashid Iqbal (Journal of Crop Health, 2025)

Evaluation of genetic diversity and population structure of the Chinese chestnut (Castanea mollissima) by using NR-SSR markers - Saman Zulfiqar; Muhammad Mahran Aslam; Allah Ditta; Rashid Iqbal; Abd El-Zaher M. A. Mustafa; Mohamed S. Elshikh; Muhammad Uzair; Saltanat Aghayeva; Muhammad Qasim; Sezai Ercisli; Ozhan Simsek; Tolga Izgu; et al. (Genetic Resources and Crop Evolution, 2025)

RETRACTED ARTICLE: Understanding rice blast: investigating biotechnological methods to speed up the development of robust rice cultivars - Nimra Rajput; Muhammad Usama Younas; Muhammad Qasim; Saima Parveen Memon; Shabana Memon; Magda Abd El-Rahman; Saltanat Aghayeva; Sezai Ercisli; Rashid Iqbal; Shimin Zuo (Genetic Resources and Crop Evolution, 2025)

Exploring environmentally stable and novel genetic factors influencing rice grain shape and yield attributes - Sadia Gull; Zulqarnain Haider; Houwen Gu; Saleem Uddin; Muhammad Qasim; Rana Ahsan Raza Khan; Adil Altaf; Sajid Fiaz; Mona S. Alwahibi; Mohamed S. Elshikh; Rashid Iqbal; Jun Miao; et al. (Euphytica, 2025)

RETRACTED ARTICLE: Integrated agri-aquaculture of Lactuca sativa and Cyprinus carpio improve yield and economic benefits of small-scale farmers - Sanaullah Sattar; Muhammad Muneeb; Abdul Majeed Saim; Wali Muhammad Mangrio; Farhan Nabi; Muhammad Bilawal Junaid; Atta Mohi Ud Din; Munirah Abdullah Al-Dosary; Imran Haider; Rashid Iqbal (Aquaculture International, 2025)

Use of methanolic plant extracts against maize weevil (Sitophilus zeamais) (Curculionidae: Coleoptera) - Muhammad Mamoon-ur-Rashid; Riaz-ud Din; Muhammad Naeem; Mohamed Farouk Elsadek; Khalid S. Al-Numair; Mohamed S. Sheteiwy; Iram Ijaz; Muhammad Muzammal; Muhammad Yasin (International Journal of Tropical Insect Science, 2025)

Influence of physical forms of non-forage diet on growth performance, feeding behavior, rumen and blood indices, and nutrient digestibility in fattening goats - Muhammad Bilal; Muhammad Irfan Malik; Muhammad Afzal Rashid; Muhammad Awais Khurshid; Muhammad Shahbaz Yousaf; Habib Ur Rehman (Small Ruminant Research, 2025)

Advancements in MXene-based 3D printing-based technologies - Ali Asghar; Muhammad Shahid Rashid; Muhammad Hanif; Imed Boukhris; Zhangwei Chen; Muhammad Saqib; Qumail Arshad; P. Rosaiah; Saood Ali; Iftikhar Hussain (Chemical Engineering Journal, 2025)

Characterization of meningitis-causing bacteria, with focus on genomic and pangenomic study of multi-drug resistant Streptococcus pneumoniae from cerebrospinal fluid - Rehan Ali; Kashif Ali; Muhammad Aurongzeb; Khalid Al-Regaiey; Junaid Ahmed Kori; Muhammad Irfan; Yasmeen Rashid; Danah Al Abduljabbar; Imdad Kaleem; Shahid Bashir (Antonie van Leeuwenhoek, 2025)

Climate change projections for Diamer Division in lesser Himalayas using multi-global climate model ensemble - Didar Ahmad; Faridullah Faridullah; Muhammad Irshad; Aziz Ur Rahim Bacha; Farhan Hafeez; Akhtar Iqbal; Zahid Ullah; Muhammad Naveed Afridi; Abdulwahed Fahad Alrefaei; Rashid Nazir (Environmental Science and Pollution Research, 2024)

Fluorescence Analysis of Antibacterial Activity of ZnO/TiO2 Electrospun Nanofibers: A Molecular Approach to Reveals the Insights of Physiochemical Interactions of Materials with Bacteria - Ali Hassan; Shahzad Anwar; Rashad Rashid; Rafaqat Ali Khan; Saba Ibrahim; Bisma Khanam; Attaullah Shah; Muhammad Raffi (Journal of Fluorescence, 2024)

Hydrogeochemical characteristics, source distribution, and health risk of high-fluoride groundwater in Swabi, Pakistan - Muhammad Tariq; Abdur Rashid; Seema Anjum Khattak; Liaqat Ali; Mohammad Tahir Shah (Environmental Monitoring and Assessment, 2024)

Systematic review on buparvaquone resistance associated with non-synonymous mutation in drug binding genes site of Theileria annulate - Muhammad Rashid; Muhammad Hassan Hayat; Naveed Zahra; Mian Sayed Khan; Suleman; Muhammad Nadeem; Tauseef ur Rehman; Muhammad Ehsan; Muhammad Irfan Malik; Muhammad Kashif Obaid; Amir Bakhsh; Mohamed Aziz Darghouth; et al. (Veterinary Parasitology, 2024)

Unraveling the impact of high arsenic, fluoride and microbial population in community tubewell water around coal mines in a semiarid region: Insight from health hazards, and geographic information systems - Abdur Rashid; Muhammad Ayub; Xubo Gao; Yaoyang Xu; Zahid Ullah; Yong Guan Zhu; Liaqat Ali; Chengcheng Li; Ajaz Ahmad; Jörg Rinklebe; Sardar Khan; Parvaiz Ahmad (Journal of Hazardous Materials, 2024)

Triangular relation of food processing, nutrition, and osteoarthritis: A solution for the management and prevention of osteoarthritis? - Arashi Shahid; Ammar B. Altemimi; Iahtisham -Ul-Haq; Muhammad Inam-ur-Raheem; Roshina Rabail; Muhammad Hamdan Rashid; Sadia Kafeel; Muhammad Saad Akram; Amin Mousavi Khaneghah; Rana Muhammad Aadil (Food Bioscience, 2024)

RETRACTED: Hydrogeochemical properties, source provenance, distribution, and health risk of high fluoride groundwater: Geochemical control, and source apportionment - Muhammad Ayub; Hira Javed; Abdur Rashid; Wardah Hayat Khan; Asif Javed; Tariq Sardar; Ghulam Mujtaba Shah; Ajaz Ahmad; Jörg Rinklebe; Parvaiz Ahmad (Environmental Pollution, 2024)

Quality and yield of potato seed tubers as influenced by plant growth promoting rizobacteria - Muhammad Raqib Rasul; Tavga Sulaiman Rashid (Biocatalysis and Agricultural Biotechnology, 2024)

Unveiling the chemical profile, anti-proliferative, pro-apoptotic and anti-migratory effect of Indigofera linifolia in liver and breast cancer cells - Irum Naz; Muhammad Rashid Khan; Saima Ali; Riffat Batool (Biocatalysis and Agricultural Biotechnology, 2024)

Overexpression of Gossypium arboreum 3-ketoacyl-CoA synthase 6 (GaKCS6) gene enhanced leaf epicuticle wax in Gossypium hirsutum L. and improved tolerance against whitefly - Muhammad Umair Majid; Rabiah Ashraf; Basit Jabbar; Usman Arif; Fatima Batool; Sameera Hassan; Bushra Rashid (Biocatalysis and Agricultural Biotechnology, 2024)

Association between the variations in metabolic pathways and oral cancer risk: results from a Pakistani case-control study - Arifa Shabbir; Muhammad Usman Rashid; Ezzat M. Awad; Humaira Naeemi; Talin Barisani-Asenbauer; Naila Malkani (Molecular Biology Reports, 2024)

RETRACTED ARTICLE: Exploring the molecular mechanisms of rice blast resistance and advances in breeding for disease tolerance - Muhammad Usama Younas; Muhammad Qasim; Irshad Ahmad; Zhiming Feng; Rashid Iqbal; Xiaohong Jiang; Shimin Zuo (Molecular Biology Reports, 2024)

Allelic variation in rice blast resistance: a pathway to sustainable disease management - Muhammad Usama Younas; Muhammad Qasim; Irshad Ahmad; Zhiming Feng; Rashid Iqbal; Ashraf M.M. Abdelbacki; Nimra Rajput; Xiaohong Jiang; Bisma Rao; Shimin Zuo (Molecular Biology Reports, 2024)

Predominance of MGMT promoter methylation among Pakistani glioblastoma patients - Noor Muhammad; Samir Fasih; Bilal Malik; Shahid Hameed; Asif Loya; Muhammad Usman Rashid (Molecular Biology Reports, 2024)

Breeding for water-use efficiency in wheat: progress, challenges and prospects - Aqsa Hafeez; Shehzad Ali; Muhammad Ammar Javed; Rashid Iqbal; Muhammad Nauman Khan; Fatih ÇIĞ; Ayman EL Sabagh; Turki Abujamel; Steve Harakeh; Sezai Ercisli; Baber Ali (Molecular Biology Reports, 2024)

The association of ABCB1 gene polymorphism with clinical response to carbamazepine monotherapy in patients with epilepsy - Haroon Ur Rashid; Shakir Ullah; Daniel F. Carr; Muhammad Ijaz Khan Khattak; Muhammad Imran Asad; Mujeeb Ur Rehman; Muhammad Khalid Tipu (Molecular Biology Reports, 2024)

Nanobiochar-Coating Regulates N and P Release from DAP Fertilizer in Soil and Improves Maize Crop Productivity - Ghulam Abbas Shah; Mughees Mustafa; Hani Z. Asfour; Khubra Shoukat; Ahsan Yasin; Nadeem Ali; Muhammad Bilal Khan Niazi; Gabrijel Ondrasek; Muhammad Imtiaz Rashid (Journal of Soil Science and Plant Nutrition, 2024)

De novo assembly of sialotranscriptome of Hyalomma anatolicum and insights into expression dynamics in response to Theileria annulata infection - Adeel Mumtaz Abbasi; Shiza Nasir; Amna Arshad Bajwa; Haroon Akbar; Sara Artigas-Jerónimo; Clara Muñoz-Hernández; Marta Sánchez-Sánchez; Alberto Moraga-Fernández; Isabel G. Fernández de Mera; José de la Fuente; Muhammad Imran Rashid (Experimental and Applied Acarology, 2024)

Highly efficient adsorptive removal of phosphate using novel perovskite lanthanum ferrite/graphene oxide (LaFeO3-GO) hybrids from water - Jawad Rauf; Muhammad Ali Inam; Rashid Iftikhar; Hira Amjad; Deedar Nabi; Waleed Usmani (Journal of Water Process Engineering, 2024)

Preparation and functional characterization of pullulan-sodium alginate composite film enhanced with ultrasound-assisted clove essential oil Nanoemulsions for effective preservation of cherries and mushrooms - Arif Rashid; Abdul Qayum; Syed Asim Shah Bacha; Qiufang Liang; Yuxuan Liu; Lixin Kang; Zhuzhong Chi; Runhao Chi; Xu Han; John-Nelson Ekumah; Muhammad Safi Ullah Virk; Xiaofeng Ren; et al. (Food Chemistry, 2024)

Novel pullulan-sodium alginate film incorporated with anthocyanin-loaded casein-carboxy methyl cellulose nanocomplex for real-time fish and shrimp freshness monitoring - Arif Rashid; Abdul Qayum; Syed Asim Shah Bacha; Qiufang Liang; Yuxuan Liu; Lixin Kang; Zhuzhong Chi; Runhao Chi; Xu Han; John-Nelson Ekumah; Muhammad Safiullah Virk; Xiaofeng Ren; et al. (Food Hydrocolloids, 2024)

Retraction Note: Low-cost novel nano-constructed granite composites for removal of hazardous Terasil dye from wastewater - Maria Khalil; Muhammad Asif Hanif; Umer Rashid; Junaid Ahmad; Ali Alsalme; Toshiki Tsubota (Environmental Science and Pollution Research, 2024)

Looking into the thermostable archaeal l-asparaginases - Ayesha Sania; Muhammad Sajed; Naeem Rashid (Biologia, 2024)

Mix and manage: Cultivar mixtures can maintain yield under high wheat blast disease pressure - Timothy J. Krupnik; Md. Harun-Or-Rashid; Dinabandhu Pandit; Rabiul Islam; Md. Khaled Hossain; José Mauricio Cunha Fernandes; Krishna Kanta Roy; Muhammad Rezaul Kabir; Sabine Stuerz; Pawan Kumar Singh; Golam Faruq (Crop Protection, 2024)

Exploring the interface dynamics of emulsion gel via a novel non-destructive technique provides insights into the underlying mechanism of gel formation, water mobility, functionality and structural variations - Abdul Qayum; Arif Rashid; Asif Ali Khan; Mingming Zhong; Yuxuan Liu; Muhammad Hussain; Muhammad Safiullah Virk; Zahoor Ahmed; Abdur Rehman; Abid Hussain; Qiufang Liang; Xiaofeng Ren; et al. (Food Bioscience, 2024)

Production and optimization of biofuels from locally isolated algal biomass: Strategies for circular economy integration - Muhammad Uzair Javed; Iqra Nazeer; Hamid Mukhtar; Umer Rashid; Maria J. Sabater; Fahad A. Alharthi (Biocatalysis and Agricultural Biotechnology, 2024)

Exposure Levels, Health Risks, Spatially Distribution, Multivariate Statistics and Positive Matrix Factorization Model of Heavy Metals from Wild solid Waste Dumpsites - Predrag Ilić; Svetlana Ilić; Abdur Rashid; Zain Mushtaq; Sanja Mrazovac Kurilić; Ljiljana Stojanović Bjelić; Dragana Nešković Markić; Zia Ur Rahman Farooqi; Muhammad Yousuf Jat Baloch; Tariq Mehmood; Zahid Ullah; Sobia Riaz (Water, Air, & Soil Pollution, 2024)

The effects of coarser sand addition on thermal properties of pervious concrete - Md. Tushar Ali; Muhammad. Harunur Rashid (Innovative Infrastructure Solutions, 2024)

Understanding the spatiotemporal distribution of aerosols and their association with natural and anthropogenic factors over Saudi Arabia using multi-sensor remote sensing data - Muhammad Khan; Salman Tariq; Zia Ul Haq; Mehnaz Rashid (Air Quality, Atmosphere & Health, 2024)

Flavonoids from Pistacia chinensis subsp. integerrima with leishmanicidal activity: computational and experimental evidence - Abdur Rauf; Umer Rashid; Abdullah Muhammad Shbeer; Mohammed Al-Ghorbani; Naveed Muhammad; Anees Ahmed Khalil; Humaira Naz; Rohit Sharma; Giovanni Ribaudo (Natural Product Research, 2024)

Microplastic pollution in aquatic ecosystem: A review of existing policies and regulations - Muhammad Tariq Khan; Sajid Rashid; Unzile Yaman; Saeed Ahsan Khalid; Asif Kamal; Mushtaq Ahmad; Nasrin Akther; Md Abul Kashem; Md Faysal Hossain; Wajid Rashid (Chemosphere, 2024)

Comparative phosphate sorption and recovery potential of mono and bimetallic iron‑lanthanum impregnated biochar derived via co-pyrolysis of sewage sludge and wheat straw: Highly effective phosphatic fertilizer - Iqra Irfan; Muhammad Ali Inam; Rashid Iftikhar (Journal of Water Process Engineering, 2024)

Incorporating Halal Into Healthy and Equitable Dietary Patterns to Address Food and Nutrition Security Among K-12 and University Students: A Perspective - Amelia Keleher; Meira Neggaz; Christine M. Cliff; YaQutullah Ibraheem Muhammad; Anne Mathews; Habeeb Quadri; Ridwan Abdul Rashid; Nadeem Zafar; Asma Ahad (Journal of Nutrition Education and Behavior, 2024)

Effects of enzymatic hydrolysis combined with glycation on the emulsification characteristics and emulsion stability of peanut protein isolate - Meiyue Wang; Guanhao Bu; Tingwei Zhu; Jia Liu; Mengyao Li; Muhammad Tayyab Rashid; Mengqing Han (Food Research International, 2024)

Xylanase from Neobacillus sedimentimangrovi UE25: Characterization, purification and applications - Rozina Rashid; Uroosa Ejaz; Syed Faraz Moin; Muhammad Sohail (Biocatalysis and Agricultural Biotechnology, 2024)

Spectrophotometrically, Spectroscopically, Microscopically and Thermogravimetrically Optimized TiO2 and ZnO Nanoparticles and their Bactericidal, Antioxidant and Cytotoxic Potential: A Novel Comparative Approach - Hunaiza Tahir; Farzana Rashid; Shaukat Ali; Muhammad Summer; Rimsha Abaidullah (Journal of Fluorescence, 2024)

A potential toxicological risk assessment of heavy metals and pesticides in irrigated rice cultivars near industrial areas of Dhaka, Bangladesh - Muhammad Nurul Huda; Mohammad Harun-Ur-Rashid; Anowar Hosen; Mahafuga Akter; Md. Mominul Islam; Sharmin Zaman Emon; Asma Rahman; Zuairia Binte Jashim; Saif Shahrukh; Mohammad Ismail (Environmental Monitoring and Assessment, 2024)

Predictability of the early summer surface air temperature over Western South Asia - Irfan Ur Rashid; Muhammad Adnan Abid; Marisol Osman; Fred Kucharski; Moetasim Ashfaq; Antje Weisheimer; Mansour Almazroui; José Abraham Torres-Alavez; Muhammad Afzaal (Climate Dynamics, 2024)
Variability of the Surface Air Temperature (SAT) over the Western South Asia (WSA) region leads to frequent heatwaves during the early summer (May-June) season. The present study uses the European Centre for Medium-Range Weather Forecast’s fifth-generation seasonal prediction system, SEAS5, from 1981 to 2022 based on April initial conditions (1-month lead) to assess the SAT predictability during early summer season. The goal is to evaluate the SEAS5’s ability to predict the El Niño-Southern Oscillation (ENSO) related interannual variability and predictability of the SAT over WSA, which is mediated through upper-level (200-hPa) geopotential height anomalies. This teleconnection leads to anomalously warm surface conditions over the region during the negative ENSO phase, as observed in the reanalysis and SEAS5. We evaluate SEAS5 prediction skill against two observations and three reanalyses datasets. The SEAS5 SAT prediction skill is higher with high spatial resolution observations and reanalysis datasets compared to the ones with low-resolution. Overall, SEAS5 shows reasonable skill in predicting SAT and its variability over the WSA region. Moreover, the predictability of SAT during La Niña is comparable to El Niño years over the WSA region.

Zinc solubilizing bacteria synergize the effect of zinc sulfate on growth, yield and grain zinc content of rice (Oryza sativa) - Muhammad Shakeel; Fauzia Yusuf Hafeez; Imran Riaz Malik; Abdur Rauf; Farooq Jan; Ikramullah Khan; Iram Ijaz; Mohamed Farouk Elsadek; Muhammad Ajmal Ali; Kamran Rashid; Muhammad Muzammal; Muhammad Munir; et al. (Cereal Research Communications, 2024)
Zinc solubilizing bacteria inhabiting root endosphere possesses great potential to enhance plant yield by solubilizing the nutrients. The potential of Zn solubilizing bacteria Bacillus sp. SH-10 and Bacillus cereus SH-17 to improve yield and grain zinc content of rice was investigated under different regimes of individual and co-inoculation in the presence and absence of chemical fertilizer zinc sulfate (ZnSO 4 ). The strains were applied to the rice varieties basmati 385 and super basmati under field conditions for two consecutive years. A significantly improved growth of rice plants, such as plant height (102–118 cm), number of tillers per plant (8.5–11.5), chlorophyll content (29.5–35.1), zinc requiring enzymes, i.e., superoxide dismutase (396–570 per gram fresh weight (g −1 FW)), carbonic anhydrase activity (CA) (10–15.06 U g −1 FW) and grain yield (3.0–3.8 tons ha −1 ), was observed in the plants inoculated with Bacillus sp. in the presence of chemical fertilizer (ZnSO 4 ). Consortium of zinc solubilizing bacteria also caused higher grain Zn content (25.0–30.5 mg kg −1 ) of the rice varieties basmati 385 and super basmati as compared to that of un-inoculated plants. Hence, it can be concluded that Zn solubilizing bacteria has immense potential to be used as agricultural crop inoculants as they synergize the effect of chemical Zn, increase yield and improve the nutritional value of crops.

Analytical seismic assessment for reinforced concrete moment frame residential buildings constructed in the Soviet Union Era in Almaty, Kazakhstan - Muhammad Sajjad Rashid; Dichuan Zhang; Sung-Woo Moon; Yeraly Shokbarov; Jong Kim (Bulletin of Earthquake Engineering, 2024)

Waste Palm Leaves-Based Hydrochar Support Catalytic Esterification of Palm Fatty Acid Distillate - Muhammad Aliyu; Umer Rashid; Wan Azlina Wan Ab Karim Ghani; Mohamad Amran Mohd Salleh; Balkis Hazmi; Fahad A. Alharthi; Elsa Antunes; Jianglong Yu (BioEnergy Research, 2024)

Functionality of wheat straw-derived biochar enhanced its efficiency for actively capping Cd and Pb in contaminated water and soil matrices: Insights through batch adsorption and flow-through experiments - Yasir Hamid; Yonglong Chen; Qiang Lin; Muhammad Haris; Muhammad Usman; Muhammad Saqib Rashid; Ioannis Anastopoulos; Bilal Hussain; Hayssam M. Ali; Fakhir Hannan; Xianyuan Yin; Xiaoe Yang (Chemosphere, 2024)

Purifying surface water contaminated with azo dyes using nanofiltration: Interactions between dyes and dissolved organic matter - Mian Jawaduddin; Zhaoyang Su; Muhammad Saboor Siddique; Sajid Rashid; Wenzheng Yu (Chemosphere, 2024)

Bio-perfume guns: Antifungal volatile activity of Bacillus sp. LNXM12 against postharvest pathogen Botrytis cinerea in tomato and strawberry - Abdur Rashid Khan; Qurban Ali; Muhammad Ayaz; Muhammad Saqib Bilal; Hamza Tariq; Mahmoud H. El-Komy; Qin Gu; Huijun Wu; Joachim Vater; Xuewen Gao (Pesticide Biochemistry and Physiology, 2024)

Hydrothermal carbonization of fruit peels of varied origin forms hydrochar of distinct capability for adsorption of methylene blue - Sobia Kousar; Mengjiao Fan; Kanwal Javed; Muhammad Rashid; Shu Zhang; Xun Hu (Journal of Water Process Engineering, 2024)

Unveiling drastic influence of cross-interactions in hydrothermal carbonization of spirulina with cellulose, lignin or poplar on nature of hydrochar and activated carbon - Stelgen Inkoua; Chao Li; Muhammad Rashid; Muhammad Mahboob Naeem; Shu Zhang; Wenran Gao; Mortaza Gholizadeh; Xun Hu (Journal of Environmental Management, 2024)

Phenotypic and Molecular Profiling of Vitis Vinifera L. Genotypes Against Anthracnose Through SCAR Markers - Qandeela Nigar; Mahmood ul Hassan; Rashid Mehmood Rana; Sadia Mehmood Satti; Summaira Ali; Muhammad Farhan Khan Pasha; Irfan Ali; Hafiz Muhamamd Ahmad; Sami Al Obaid; Mohammad Javed Ansari; Sajid Fiaz (Journal of Crop Health, 2024)

Unveiling the unique potential of MXene with and without graphene nanoplatelet for thermal energy storage applications - Amirul Aminur Rashid; Muhammad Syahir Mansor; Nur Awanis Hashim; Sona R. Moharir; Norhuda Abdul Manaf (Environmental Science and Pollution Research, 2024)

Retraction Note: Impact of credit, liquidity, and systematic risk on financial structure: comparative investigation from sustainable production - Muhammad Sadiq; Sami Alajlani; Muhammed Sajjad Hussain; Rashid Ahmad; Furrukh Bashir; Supat Chupradit (Environmental Science and Pollution Research, 2024)

Exploring the variability of root system architecture under drought stress in heat-tolerant spring-wheat lines - Asadullah; Shahmir Ali Kalhoro; Wajid Farhad; Azhar Iqbal; Sultan; Abdul Waheed; Muhammad Rashid; Syed Rehmat Ullah Shah (Plant and Soil, 2024)
Background and aims Global wheat production is under threat due to climate change, specifically heat and drought and their combination. This study aims to address the root trait responses of heat-tolerant wheat genotypes to drought. Methods The variability in root traits of CIMMYT wheat lines, which were previously developed for heat stress tolerance (HTWL), was evaluated alongside 10 Pakistani-approved varieties under three cultivation conditions and soil moisture levels. Results Our findings revealed that the plasticity of the wheat root system is highly pronounced, with rhizosphere conditions exerting a more substantial influence (5–49%) than the genotypic response (1–14%). Furthermore, in the hydroponic and pot system, we noted higher maximum-root length (1.5–1.8 fold) and root-to-shoot ratio (3.4–10.6 fold) as compared to field condition, while the root biomass was substantially higher in the field trial (3-57 fold). Nonetheless, persistent drought conditions exerted contrasting impact with reduction in most of the traits except specific root length and harvest index which were increased under drought. Conclusions The variation in root traits against drought indicates the potential for the development of improved genotypes that can withstand multiple stresses. Furthermore, it is crucial to consider rhizosphere conditions when selecting genotypes, as the plasticity of wheat roots may lead to misinterpretations if rhizosphere conditions are disregarded. Root dry weight and root-to-shoot ratio are more stable traits as compared to maximum root length and specific root length. It is recommended to evaluate a broader range of rhizosphere conditions to select tolerant genotypes.

Synergistic adsorption of methylene blue using ternary composite of phosphoric acid geopolymer, calcium alginate, and sodium lauryl sulfate - Muhammad Irfan Khan; Suriati Sufian; Rashid Shamsuddin; Muhammad Farooq; Nabilah Saafie (Environmental Science and Pollution Research, 2024)

Physicochemical properties and performance of non-woody derived biochars for the sustainable removal of aquatic pollutants: A systematic review - Ghulam Murtaza; Zeeshan Ahmed; Muhammad Usman; Rashid Iqbal; Faisal Zulfiqar; Akash Tariq; Allah Ditta (Chemosphere, 2024)

Efficient production of biodiesel from palm fatty acid distillate using a novel hydrochar-based solid acid catalyst derived from palm leaf waste - Muhammad Aliyu; Bryan R. Moser; Fahad A. Alharthi; Umer Rashid (Process Safety and Environmental Protection, 2024)

Enhancing storage and gastroprotective viability of Lactiplantibacillus plantarum encapsulated by sodium caseinate-inulin-soy protein isolates composites carried within carboxymethyl cellulose hydrogel - Muhammad Safiullah Virk; Muhammad Abdulrehman Virk; Qiufang Liang; Yufan Sun; Mingming Zhong; Tabussam Tufail; Arif Rashid; Abdul Qayum; Abdur Rehman; John-Nelson Ekumah; Junxia Wang; Yongjun Zhao; et al. (Food Research International, 2024)

Response of cotton mealybug, Phenacoccus Solenopsis Tinsley (Sternorrhyncha: Pseudococcidae) to predators, neem oil, and synthetic insecticide under semi-field and field conditions - Muhammad Mamoon-ur-Rashid; Khalid Abdullah; Habib Ali; Muhammad Tariq; Adnan Noor Shah; Shahbaz Ali (International Journal of Tropical Insect Science, 2024)

Insights into the biogeochemical transformation, environmental impacts and biochar-based soil decontamination of antimony - Rabia Safeer; Guijian Liu; Balal Yousaf; Aniqa Ashraf; Muhammad Irtaza Sajjad Haider; Ayesha Imtiyaz Cheema; Samra Ijaz; Audil Rashid; Anila Sikandar; Krzysztof Pikoń (Environmental Research, 2024)

Spatial variation in iodine content with relation to soil physicochemical properties in lower Himalayan region - Jawad Ali; Muhammad Mohiuddin; Xinfeng Wang; Zahid Hussain; Muhammad Irshad; Munir Zia; Rashid Pervez; Mohammad K. Okla; Shakeel Ahmad (Environmental Research, 2024)

Exposure to heavy metals, antioxidant status, and the interaction of single nucleotide polymorphisms in the genes CAT rs7943316, GSTP1 rs1695, as well as GSTM1 and GSTT1 genes, among workers in occupational settings - Sosan Andleeb Khan; Syed Muhammad Nurulain; Rashid Nazir Qureshi; Amina Zafar; Zarish Riaz; Aneela Shoukat; Zahid Muneer; Nazia Bibi; Saqlain Raza; Sabir Hussain; Syed Tahir Abbas Shah (Environmental Toxicology and Pharmacology, 2024)

Insights into the involvement of male Hyalomma anatolicum ticks in transmitting Anaplasma marginale, lumpy skin disease virus and Theileria annulata - Sikandar Ali; Abdullah Saghir Ahmad; Kamran Ashraf; Jawaria Ali Khan; Muhammad Imran Rashid (Tropical Animal Health and Production, 2024)

Zinc Provisioned Enhancement of Manganese Use Efficiency Results in Differential Biomass and Grain Production in Two Rice Cultivars Grown in Clay Loam Soil - Faisal Nadeem; Rashid Mahmood; Muhammad Anwar-ul-Haq; Muhammad Sabir; Saifullah; Qingxu Ma; Chongwei Jin; Tayyaba Samreen; Muhammad Saleem Haider (Journal of Soil Science and Plant Nutrition, 2024)

Characterization of the tubby-like proteins (TLPs) gene family in Cucumis sativus L.: insights into the evolution, structure, and expression patterns under salt stress - Ikram Ullah; Muhammad Uzair; Obaid Ur Rehman; Safira Attacha; Kotb A. Attia; Sheraz Ahmad; Muhammad Salman; Hamid Ali; Muhammad Abdul Rehman Rashid; Asmaa M. Abushady; Sajid Fiaz; Syed Jehangir Shah; et al. (Genetic Resources and Crop Evolution, 2024)

Integrated sedimentary and diagenetic constraints for delineating the reservoir potential of Jurassic carbonate sequences in the autochthonous Samana Suk Formation, Attock-Cherat Nizampur Area, Pakistan - Muhammad Ibrar; Sajjad Khan; Mehboob Ur Rashid; George Kontakiotis; Ihtisham Islam; Hammad Tariq Janjuhah; Assimina Antonarakou (Carbonates and Evaporites, 2024)

A control rod worth prediction using Adaptive Neuro-Fuzzy Inference System for Pre-Calibration Method at TRIGA PUSPATI Reactor - Teh Zhi Hui; Nur Syazwani Mohd Ali; Mohd Sabri Minhat; Jasman Zainal; Muhammad Arif Sazali; Muhammad Syahir Sarkawi; Khairulnadzmi Jamaluddin; Nor Afifah Basri; Mohsin Mohd Sies; Nahrul Khair Alang Md Rashid (Annals of Nuclear Energy, 2024)

Correction to: Recent Progress in Folic Acid Detection Based on Fluorescent Carbon Dots as Sensors: A Review - Kawan F. Kayani; Mohammed K Rahim; Sewara J. Mohammed; Harez Rashid Ahmed; Muhammad S. Mustafa; Shujahadeen B. Aziz (Journal of Fluorescence, 2024)

In-silico functional and molecular phenotypic analysis of NFKBIE (V194A), and PADI4 (G55S, V82A,G112A) gene mutations in rheumatoid arthritis - Fazal Shan; Irshad Ahmad; Muhammad Ibrahim Rashid (Journal of Proteins and Proteomics, 2024)

First principle study of X2GaAgCl6 (X = Cs, Rb) double perovskites: structural, mechanical, vibrational, electronic, optical, SLME, thermoelectric, and thermodynamic properties for solar cell applications - Zia Ur Rehman; Muhammad Awais Rehman; Muhammad Rashid Khan; Bushra Rehman; Surajudeen Sikiru; Muhammad Rizwan; Mohammed Chafi; Muhammad Usman (Environmental Science and Pollution Research, 2024)

Integrated Approach to Hydrogeochemical Assessment of Groundwater Quality in Major Industrial Zone of Punjab, Pakistan - Asmat Ali; Zahid Ullah; Nayab Ismaeel; Abdur Rashid; Warda Khalid; Maria Siddique; Javed Iqbal; Anwarzeb Khan; Muhammad Waqas; Junaid Ghani (Environmental Science and Pollution Research, 2024)

Optimal environment control and fruits delivery tracking system using blockchain for greenhouse - Atif Rizwan; Anam Nawaz Khan; Muhammad Ibrahim; Rashid Ahmad; Naeem Iqbal; Do Hyeun Kim (Computers and Electronics in Agriculture, 2024)

RETRACTED: Hydrogeochemical characteristics, stable isotopes, positive matrix factorization, source apportionment, and health risk of high fluoride groundwater in semiarid region - Abdur Rashid; Muhammad Ayub; Xubo Gao; Seema Anjum Khattak; Liaqat Ali; Chengcheng Li; Ajaz Ahmad; Sardar Khan; Jörg Rinklebe; Parvaiz Ahmad (Journal of Hazardous Materials, 2024)

Occurrence of toxic elements in river areas along drains and groundwater resources: source of contamination and associated health risk - Zahid Ullah; Fazila Younas; Aziz Ur Rahim Bacha; Abdur Rashid; Wedad A. Al-onazi; Muhammad Fahad Sardar (Environmental Monitoring and Assessment, 2024)

Appraisal of the health hazards associated with the ingestion of vegetables contaminated with potentially toxic elements - Ali Afzal; Atif Muhmood; Syed Ayyaz Javed; Arslan Nazarat; Muhammad Rashid; Asrar Hussain Shah; Farhana Siddique (Arabian Journal of Geosciences, 2024)

Recent Progress in Folic Acid Detection Based on Fluorescent Carbon Dots as Sensors: A Review - Kawan F. Kayani; Mohammed K Rahim; Sewara J. Mohammed; Harez Rashid Ahmed; Muhammad S. Mustafa; Shujahadeen B. Aziz (Journal of Fluorescence, 2024)

Heavy metal sequestration from wastewater by metal-organic frameworks: a state-of-the-art review of recent progress - Ali Shaan Manzoor Ghumman; Rashid Shamsuddin; Lailatul Qomariyah; Jun Wei Lim; Abdul Sami; Muhammad Ayoub (Environmental Science and Pollution Research, 2024)

The development of plastic waste and sewage sludge co-pyrolyzed biochar composites with improved interfacial characteristics for the effective removal of ciprofloxacin - Aniqa Ashraf; Guijian Liu; Muhammad Arif; Balal Yousaf; Pervaiz Akhtar; Audil Rashid; Humaira Gulzaman; Rabia Safeer; Muhammad Saqib Rashid; Muhammad Irtaza Sajjad Haider (Process Safety and Environmental Protection, 2024)

A feasibility study of green hydrogen liquefaction for hydrogen refueling station: Multi-criteria based integrative assessment - Changgwon Choe; Jiwon Gu; Junaid Haider; Muhammad Abdul Qyyum; Ala'a H. Al-Muhtaseb; Rashid Al Abri; Hankwon Lim (Journal of Cleaner Production, 2024)

Brown macro-seaweeds derived agro-biostimulant for Zea mays farming in saline conditions: Growth enhancement and optimum biochemical and ion feedback - Sadaf Gul; Muhammad Farrakh Nawaz; Muhammad Talha Bin Yousaf; Muhammad Haroon U Rashid; Muhammad Yousuf Adnan; Shamama Tausif; Arooj Javed; Zainul Abideen; Ali El- Keblawy (Biocatalysis and Agricultural Biotechnology, 2024)

Geochemical Investigation of OCPs in the Rivers Along with Drains and Groundwater Sources of Eastern Punjab, Pakistan - Asmat Ali; Zahid Ullah; Maria Siddique; Junaid Ghani; Abdur Rashid; Warda Khalid; Muhammad Inayat Ullah Khan; Waqas Ashraf (Exposure and Health, 2024)

Assessment of historical and projected changes in extreme temperatures of Balochistan, Pakistan using extreme value theory - Darakshan Naeem; Rizwan Aziz; Muhammad Awais; Sajid Rashid Ahmad (Environmental Monitoring and Assessment, 2024)

Health, environment, and sustainable development: evidence from panel data from ASEAN countries - Muhammad Azam; Faridul Islam; Salim Rashid (Air Quality, Atmosphere & Health, 2024)

Zinc and amino acids improve the growth, physiological, and biochemical attributes of corn under different irrigation levels - Ayman M.S. Elshamly; Rashid Iqbal; Baber Ali; Iftikhar Ahmed; Muhammad Irfan Akram; Shehzad Ali; Allah Ditta; Fatih ÇIĞ; Mohamed S. Elshikh; Abd El-Zaher M.A. Mustafa; Mahdy H. Hamed (Rhizosphere, 2024)

Concentration and distribution patterns of rare earth elements (REEs) in stream sediments of Pakistan - Zhihua Wang; Jun Hong; Xin Lin; Huishan Zhang; Yasir Shaheen Khalil; Naghma Haider; Mehboob Ur Rashid; Muhammad Jawad Zeb; Asad Ali Narejo (Journal of Geochemical Exploration, 2024)

Vegetable Plant Canopy Inhibits Soil Urease Activity and Reduces NH3 Losses Under p-Phenylenediamine (PPD)-Coated Urea Application - Sarah Shakeel; Rashid Mahmood; Ammara Fatima; Faisal Nadeem; Sajid Ali; Muhammad Saleem Haider (Journal of Soil Science and Plant Nutrition, 2024)

Biological response of red palm weevil (Rhynchophorus ferrugineus, Olivier) (Coleoptera: Curculionidae) on six different varieties of date palm - Gul Rehman; Muhammad Mamoon-ur-Rashid; Habib Ali; Mirza Abdul Qayyum; Shahbaz Ali; Muhammad Ali; Obaid Ullah Sayal; Asif Latif; Asghar Ali Khan (International Journal of Tropical Insect Science, 2024)

Effects of BC on metal uptake by crops (availability) and the vertical migration behavior in soil: A 3-year field experiments of crop rotation - Shaojun Jiang; Guangling Dai; Muhammad Saqib Rashid; Junhao Zhang; Hai Lin; Yuehong Shu (Chemosphere, 2024)

Advancements in TiO2-based photocatalysis for environmental remediation: Strategies for enhancing visible-light-driven activity - Ruhma Rashid; Iqrash Shafiq; Muhammad Rehan Hasan Shah Gilani; Muhammad Maaz; Parveen Akhter; Murid Hussain; Kwang-Eun Jeong; Eilhann E. Kwon; Sungjun Bae; Young-Kwon Park (Chemosphere, 2024)

Risk surveillance with spatial distribution of Organochlorine Pesticides (OCPs) from sedimentary samples of Chenab River - Sidra Siddique; M. Nawaz Chaudhry; Sajid Rashid Ahmad; Rabia Nazir; Rimsha Javed; Muhammad Rashid Hafeez; Yasser Alraey; Lalita Ambigai Sivasamugham; Adeel Mahmood (Science of The Total Environment, 2024)

Assessing the impact of RCP4.5 and RCP8.5 scenarios on landslide susceptibility mapping using support vector machine: A case study of Penang Island, Malaysia - Mohamed Khatif Tawaf Mohamed Yusof; Ahmad Safuan A Rashid; Mohd Faisal Abdul Khanan; Muhammad Zulkarnain Abdul Rahman; Wardatun Ahmar Abdul Manan; Roohollah Kalatehjari; Ali Dehghanbanadaki (Physics and Chemistry of the Earth, Parts A/B/C, 2024)

Antioxidant and antimicrobial potential of compounds isolated from Carissa opaca - Bushra Ahmad; Muhammad Rashid Khan; Arshad Jamil; Muhammad Zulfiqar Ahmad; Sidra Pervez; Timothy D.W. Claridge; Barbara Odell; James S.O. McCullagh (Food Bioscience, 2024)

Multifunctional role of nanoparticles for the diagnosis and therapeutics of cardiovascular diseases - Ihtesham Arshad; Ayesha Kanwal; Imran Zafar; Ahsanullah Unar; Hanane Mouada; Iashia Tur Razia; Safina Arif; Muhammad Ahsan; Mohammad Amjad Kamal; Summya Rashid; Khalid Ali Khan; Rohit Sharma (Environmental Research, 2024)

Theoretical and experimental explored tailored hybrid H+/O2– ions conduction: Bridged for high performance fuel cell and water electrolysis - Zuhra Tayyab; Sajid Rauf; Muhammad Bilal Hanif; Hafiz Imran Ahmad Qazi; Naveed Mushtaq; Martin Motola; Sining Yun; Chen Xia; Dmitry A. Medvedev; Muhammad Imran Asghar; Abdullah N. Alodhayb; Arshad Hussain; et al. (Chemical Engineering Journal, 2024)

Kinetic & thermodynamic studies of green fuel additive solketal from crude glycerol over metakaolin clay catalyst - Imtisal Zahid; Muhammad Ayoub; Muhammad Hamza Nazir; Farooq Sher; Rashid Shamsuddin; Bawadi bin Abdullah; Mariam Ameen (Biomass and Bioenergy, 2024)

Using river restoration model to control riverbank erosion in the Old Brahmaputra river of Bengal Basin, Bangladesh - Muhammad Rezaul Rakib; Md Anarul Haque Mondol; Abu Reza Md. Towfiqul Islam; Md. Bazlar Rashid (Advances in Space Research, 2024)

Remote sensing and GIS based multi-criteria analysis approach with application of AHP and FAHP for structures suitability of rainwater harvesting structures in Lai Nullah, Rawalpindi, Pakistan - Rashid Ahmad; Hamza Farooq Gabriel; Farooq Alam; Riaz Zarin; Abdur Raziq; Muhammad Nouman; Hsu-Wen Vincent Young; Yuei-An Liou (Urban Climate, 2024)

Synthesis of novel metal silica nanoparticles exhibiting antimicrobial potential and applications to combat periodontitis - Muhammad Zohaib Nawaz; Huda Ahmed Alghamdi; Mehvish Zahoor; Fizzah Rashid; Atheer Ahmed Alshahrani; Nuha S. Alghamdi; Arivalagan Pugazhendhi; Daochen Zhu (Environmental Research, 2024)

Hydrogeochemistry and prediction of arsenic contamination in groundwater of Vehari, Pakistan: comparison of artificial neural network, random forest and logistic regression models - Javed Iqbal; Chunli Su; Maqsood Ahmad; Muhammad Yousuf Jat Baloch; Abdur Rashid; Zahid Ullah; Hasnain Abbas; Anam Nigar; Asmat Ali; Arif Ullah (Environmental Geochemistry and Health, 2024)

Influence of biochar produced from negative pressure-induced carbonization on transformation of potentially toxic metal(loid)s concerning plant physiological characteristics in industrially contaminated soil - Ayesha Imtiyaz Cheema; Guijian Liu; Balal Yousaf; Aniqa Ashraf; Muyuan Lu; Samina Irshad; Krzysztof Pikon; Mehr Ahmed Mujtaba Munir; Muhammad Saqib Rashid (Journal of Environmental Management, 2023)

Fabrication and Evaluation of Differential Release Bilayer Tablets of Clarithromycin and Levofloxacin by 3D Printing - Qazi Amir Ijaz; Sumera Latif; Sumaira Irum Khan; Memoona Rashid; Hafsa Afzal; Nasrullah Jan; Zeeshan Javaid; Muhammad Sarfraz; Amjad Hussain; Muhammad Sohail Arshad; Nadeem Irfan Bukhari; Nasir Abbas (Journal of Pharmaceutical Innovation, 2023)

Production, purification, and characterization of p-diphenol oxidase (PDO) enzyme from lignolytic fungal isolate Schizophyllum commune MF-O5 - Muhammad Faheem; Syed Ali Imran Bokhari; Muhammad Arshad Malik; Bashir Ahmad; Muhammad Riaz; Nafeesa Zahid; Adil Hussain; Abdul Ghani; Hanif Ullah; Waseem Shah; Rashid Mehmood; Khurshid Ahmad; et al. (Folia Microbiologica, 2023)

Correction: Modeling future urban network capacity and land use/land cover simulation using GEE and remote sensing data - Muhammad Nabeel Khalid; Muhammad Nasar Ahmad; Muhammad Asif Javed; Sajid Rashid Ahmad (Arabian Journal of Geosciences, 2023)

Systematic elucidation of the multi-target pharmacological mechanism of Terminalia arjuna against congestive cardiac failure via network pharmacology and molecular modelling approaches - Aqsa Asghar; Muhammad Qasim; Fatima Noor; Usman Ali Ashfaq; Muhammad Tahir ul Qamar; Muhammad Shareef Masoud; Rashid Bhatti; Ahmad Almatroudi; Faris Alrumaihi; Khaled S. Allemailem (Natural Product Research, 2023)

Assessment of rainwater harvesting potential for urban area under climate and land use changes using geo-informatics technology - Saif Haider; Muhammad Umer Masood; Muhammad Rashid; Tauqeer Ali; Chaitanya B. Pande; Fahad Alshehri; Ismail Elkhrachy (Urban Climate, 2023)

Towards achieving university sustainability! Linking social responsibility with knowledge sharing in Saudi universities - Afroze Nazneen; Islam Elgammal; Zubair Rashid Khan; Muhammad Haroon Shoukat; Ali Elsayed Shehata; Kareem M. Selem (Journal of Cleaner Production, 2023)

A renewable and sustainable framework for clean fuel towards circular economy for solid waste generation in leather tanneries - Arshid Mahmood Ali; Arslan Khan; Muhammad Shahbaz; Muhammad Imtiaz Rashid; Muhammad Imran; Khurram Shahzad; Aishah Binti Mahpudz (Fuel, 2023)

Utilisation of Sunflower Marble Waste Nanocomposites for Efficient Removal of Dyes from Wastewater: Synthesis, Adsorption Performance, and Characterisation - Tayaba Saeed; Muhammad Asif Hanif; Umer Rashid; Hafeez Anwar; Ijaz Ahmad Bhatti; Fahad A. Alharthi; Jeehoon Han; Jiyun Yoo (Water, Air, & Soil Pollution, 2023)

Unraveling the impact of human perturbation on nitrogen cycling in terrestrial ecosystems of lower Himalaya, Pakistan - Tahir Zaman; Saeed Ahmad Asad; Muhammad Irshad; Faridullah; Muhammad Shahzad; Rashid Nazir; Awais Arefeen; Akhtar Iqbal; Farhan Hafeez (Environmental Monitoring and Assessment, 2023)

Transcriptomic analysis of Ralstonia solanacearum in response to antibacterial volatiles of Bacillus velezensis FZB42 - Hafiz Abdul Samad Tahir; Qurban Ali; Faheem Uddin Rajer; Qaisar Shakeel; Waqqas Gillani; Rana Binyamin; Hafiz Muhammad Abdullah Tayyab; Abdur Rashid Khan; Qin Gu; Xuewen Gao; Huijun Wu (Archives of Microbiology, 2023)

Modeling future urban network capacity and land use/land cover simulation using GEE and remote sensing data - Muhammad Nabeel Khalid; Muhammad Nasar Ahmad; Muhammad Asif Javed; Sajid Rashid Ahmad (Arabian Journal of Geosciences, 2023)

Unraveling the effects of zinc sulfate nanoparticles and potassium fertilizers on quality of maize and associated health risks in Cd contaminated soils under different moisture regimes - Muhammad Umair; Sehrish Huma Zafar; Mumtaz Cheema; Rashid Minhas; Abdul Manan Saeed; Muhammad Saqib; Muhammad Aslam (Science of The Total Environment, 2023)

Efficient removal of hexavalent chromium Cr (VI) using magnesium-iron layered double hydroxide supported on orange peel (Mg-Fe LDH@OPP): A synthetic experimental and mechanism studies - Waleed Usmani; Muhammad Ali Inam; Rashid Iftikhar; Iqra Irfan; Rabia Adnan; Muhammad Bilal Khan Niazi; Rizwan Khan; Muhammad Hassan (Journal of Water Process Engineering, 2023)

Geochemical control, water quality indexing, source distribution, and potential health risk of fluoride and arsenic in groundwater: Occurrence, sources apportionment, and positive matrix factorization model - Abdur Rashid; Muhammad Ayub; Jochen Bundschuh; Xubo Gao; Zahid Ullah; Liaqat Ali; Chengcheng Li; Ajaz Ahmad; Sardar Khan; Jörg Rinklebe; Parvaiz Ahmad (Journal of Hazardous Materials, 2023)

Novel thiol-grafted composite of chitosan and rice straw biochar (TH@CT-BC): A two-step fabrication for highly selective adsorption of cadmium from contaminated water - Yasir Hamid; Lei Liu; Muhammad Haris; Muhammad Usman; Qiang Lin; Yonglong Chen; Muhammad Saqib Rashid; Zaid Ulhassan; M. Iftikhar Hussain; Xiaoe Yang (Journal of Environmental Chemical Engineering, 2023)

Analyzing the non-linear association between urbanization and ecological footprint: an empirical analysis - Muhammad Arif; Abid Rashid Gill; Minhaj Ali (Environmental Science and Pollution Research, 2023)

Methanol production and purification via membrane-based technology: Recent advancements, challenges and the way forward - Kinza Qadeer; Amer Al-Hinai; Lai Fatt Chuah; Noman Raza Sial; Ala'a H. Al-Muhtaseb; Rashid Al-Abri; Muhammad Abdul Qyyum; Moonyong Lee (Chemosphere, 2023)

Identification, characterization and expression profiling of salt-stress responsive proteinase inhibitor in Gossypium arboreum L. - Muhammad Naveed Shahid; Sarfraz Kiani; Bushra Rashid; Tayyab Husnain (South African Journal of Botany, 2023)

Effect of NDF levels of complete pelleted diet and dietary transition period on rumen pH, growth performance, digestibility, and blood indices in fattening male goats - Muhammad Awais Khurshid; Muhammad Afzal Rashid; Muhammad Shahbaz Yousaf; Saima Naveed; Muhammad Qamer Shahid; Habib Ur Rehman (Small Ruminant Research, 2023)

A game theory approach to land acquisition conflicts in Pakistan - Ahsan Shafi; Zhanqi Wang; Muhsan Ehsan; Faizan Ahmed Riaz; Muhammad Rashid Ali; Feng Xu (Land Use Policy, 2023)

Exploring the multifunctional roles of quantum dots for unlocking the future of biology and medicine - Muhammad Kashif Ali; Saher Javaid; Haseeb Afzal; Imran Zafar; Kompal Fayyaz; Qurat ul Ain; Mohd Ashraf Rather; Md. Jamal Hossain; Summya Rashid; Khalid Ali Khan; Rohit Sharma (Environmental Research, 2023)

Co-application of Biochar and Seed Priming with Nano-sized Chitosan-Proline Improves Salt Tolerance in Differentially Responding Bread Wheat Genotypes - Marwa Sulaiman Al Hinai; Aman Ullah; Al-Khaleel M. Al-Toubi; Ibtisam Rashid Al Harrasi; Ahlam Ali Alamri; Muhammad Farooq (Journal of Soil Science and Plant Nutrition, 2023)

Effect of green Fe2O3 nanoparticles in controlling Fusarium fruit rot disease of loquat in Pakistan - Faryal Niazi; Musrat Ali; Urooj Haroon; Farhana; Asif Kamal; Taskeen Rashid; Fareeha Anwar; Rabia Nawab; Hassan Javed Chaudhary; Muhammad Farooq Hussain Munis (Brazilian Journal of Microbiology, 2023)

Feed intake, feeding behavior, growth performance, nutrient digestibility, and carcass characteristics of goats fed pelleted total mixed rations with varying Rhodes hay levels - Muhammad Irfan Malik; Xuezhao Sun; Muhammad Afzal Rashid; Muhammad Amer Sohail; Muhammad Shahbaz Yousaf; Habib Ur Rehman; Imran Mohsin; Jianping Li (Small Ruminant Research, 2023)

Nanobiochar reduces ammonia emission, increases nutrient mineralization from vermicompost, and improves maize productivity - Muhammad Imtiaz Rashid; Ghulam Abbas Shah; Zahid Iqbal; Khurram Shahzad; Nadeem Ali; Mohammad Rehan; Nabil Abdulhafiz A. Alhakamy; Jiří Jaromír Klemeš (Journal of Cleaner Production, 2023)

Enhancement in anaerobic biogas conversion by visible light photocatalytic Pre-treatment of rice husk with indium vanadate decorated titanium dioxide nanocomposite - Jamshaid Rashid; Talha Tufail Bhatti; Muhammad Hassan; M.A. Barakat; Rajeev Kumar; Ming Xu (Fuel, 2023)

The perception and influencing factors of astringency, and health-promoting effects associated with phytochemicals: A comprehensive review - Fang Wei; Jie Wang; Liyong Luo; Muhammad Tayyab Rashid; Liang Zeng (Food Research International, 2023)

A modified experimental approach to determine formation porosity from rock cuttings - Semab Tariq; Zeeshan Khan; Allah Bakhsh; Syed Jamal ud Din; Azizullah Shaikh; Habib Ur Rehman; Rashid Sher Muhammad; Liang Zhang (Arabian Journal of Geosciences, 2023)

“Retraction notice to Carveol ameliorates mercury-induced oxidative stress, neuroinflammation, and neurodegeneration in a mouse brain” NeuroToxicology 92 (2022) 212–226 - Abdullah Alattar; Arooj Mohsin Alvi; Sajid Rashid; Nadia Hussain; Mehreen Gul; Muhammad Ikram; Atif Ali Khan Khalil; Reem Alshaman; Fawad Ali Shah; Shupeng Li; Jingbo Li (NeuroToxicology, 2023)

From forest floor to tree top: Partitioning of biomass and carbon stock in multiple strata of forest vegetation in Western Himalaya - Shiekh Marifatul Haq; Irfan Rashid; Muhammad Waheed; Anzar Ahmad Khuroo (Environmental Monitoring and Assessment, 2023)

Unveiling the genomic potential of a novel thermostable glycoside hydrolases producing Neobacillus sedimentimangrovi UE25 - Uroosa Ejaz; Faizan Saleem; Rozina Rashid; Khwaja Ali Hasan; Muhammad Noman Syed; Muhammad Sohail (Antonie van Leeuwenhoek, 2023)

Impregnation of biochar with montmorillonite and its activation for the removal of azithromycin from aqueous media - Muhammad Arif; Guijian Liu; Muhammad Zia ur Rehman; Md Manik Mian; Aniqa Ashraf; Balal Yousaf; Muhammad Saqib Rashid; Rafay Ahmed; Muhammad Imran; Mehr Ahmed Mujtaba Munir (Environmental Science and Pollution Research, 2023)

The presence of polycyclic aromatic hydrocarbons (PAHs) in air particles and estimation of the respiratory deposition flux - Nur Ain Nazirah Binti Najurudeen; Md Firoz Khan; Hamidah Suradi; Ummay Ayesha Mim; Israt Nur Janntul Raim; Sara Binte Rashid; Mohd Talib Latif; Muhammad Nurul Huda (Science of The Total Environment, 2023)

Replacing ground Rhodes grass hay with soyhulls in the pelleted diet: effects on ingestive behavior, nutrient digestibility, blood metabolites, growth performance, and economic viability of intensive fattening Lohi lambs - Muhammad Khan; Muhammad Afzal Rashid; Muhammad Shahbaz Yousaf; Saima Naveed; Imran Mohsin; Habib Ur Rehman (Tropical Animal Health and Production, 2023)

Silicon Supplement Improves Growth and Yield Under Salt Stress by Modulating Ionic Homeostasis and Some Physiological Indices in Hordeum vulgare L - Muhammad Salim Akhter; Sibgha Noreen; Seema Mahmood; Muhammad Aqeel; Zafar Ullah Zafar; Muhammad Rashid; Muhammad Naveed Arshad; Muhammad Owais; Javid Ahmad; Kausar Hussain Shah (Journal of Soil Science and Plant Nutrition, 2023)

Jasminum humile (Linn) ameliorates CCl4-induced oxidative stress by regulating ER stress, inflammatory, and fibrosis markers in rats - Mehreen Fatima; Muhammad Rashid Khan (Inflammopharmacology, 2023)

An overview of genome engineering in plants, including its scope, technologies, progress and grand challenges - Muhammad Sufyan; Umar Daraz; Sajjad Hyder; Usman Zulfiqar; Rashid Iqbal; Sayed M. Eldin; Farzana Rafiq; Naveed Mahmood; Khurram Shahzad; Muhammad Uzair; Sajid Fiaz; Iftikhar Ali (Functional & Integrative Genomics, 2023)

An assessment of rural household vulnerability and resilience in natural hazards: evidence from flood prone areas - Shah Fahad; Mohammad Shakhawat Hossain; Nguyen Thi Lan Huong; Abdelmohsen A. Nassani; Mohamed Haffar; Muhammad Rashid Naeem (Environment, Development and Sustainability, 2023)

Access to sustainable healthcare infrastructure: a review of industrial emissions, coal fires, and particulate matter - Muhammad Imran; Shiraz Khan; Abdelmohsen A. Nassani; Mohamed Haffar; Haroon ur Rashid Khan; Khalid Zaman (Environmental Science and Pollution Research, 2023)

Adaptation of coastal defence structure as a mechanism to alleviate coastal erosion in monsoon dominated coast of Peninsular Malaysia - Wan Shiao Dong; Effi Helmy Ariffin; Cherdvong Saengsupavanich; Muhammad Aizat Mohd Rashid; Mohamad Hakim Mohd Shukri; Muhammad Zahir Ramli; Mohd Fuad Miskon; Muhammad Hafeez Jeofry; Kamaruzzaman Yunus; Nor Hisham M. Ghazali; Md Nasir Md Noh (Journal of Environmental Management, 2023)

High prevalence of multiple antibiotic resistance in fermented food-associated lactic acid bacteria in Malaysia - Yuli Haryani; Nadrah Abdul Halid; Goh Sur Guat; Mahmud Ab Rashid Nor-Khaizura; Muhammad Asyraf Md Hatta; Suriana Sabri; Son Radu; Hanan Hasan (Food Control, 2023)

Genetic analysis of ACE2 peptidase domain in SARS-CoV-2-positive and SARS-CoV-2-negative individuals from Pakistan - Noor Muhammad; Humaira Naeemi; Ayesha Azeem; Rida Sadaqat; Umara Shehzad; Kashif Siddique; Usman Hassan; Aun Raza; Muhammad Usman Rashid (Molecular Biology Reports, 2023)

A critical analysis of sources, pollution, and remediation of selenium, an emerging contaminant - Habib Ullah; Lu Lun; Audil Rashid; Noor Zada; Baoliang Chen; Asfandyar Shahab; Ping Li; Muhammad Ubaid Ali; Siyi Lin; Ming Hung Wong (Environmental Geochemistry and Health, 2023)

Removal of Toxic Metals from Water by Nanocomposites through Advanced Remediation Processes and Photocatalytic Oxidation - Ahmad Farhan; Misbah Zulfiqar; Samiah; Ehsan Ullah Rashid; Shahid Nawaz; Hafiz M.N. Iqbal; Teofil Jesionowski; Muhammad Bilal; Jakub Zdarta (Current Pollution Reports, 2023)
Purpose of Review Heavy and toxic metals are becoming more prevalent in the water sources of the globe, which has detrimental repercussions for both human health and the health of ecosystems. The summary of recent findings on treatment possibilities of toxic metal species by nanomaterials should facilitate the development of more advanced techniques of their removal. Recent Findings The high concentrations of chromium, mercury, and arsenic identified in wastewater cause a hazard to human health. There is a wide variety of nanoadsorbents and nanophotocatalysts used for heavy/hazardous metal removal. Recent research has resulted in the production of advanced nanostructures that exhibit extraordinary heavy/hazardous metal adsorption effectiveness and photocatalytic diminution of metal ions. These nanostructures have physically and chemically tunable features. Summary In this review article, the use of carbon-based nanomaterials, polymer-based nanomaterials, and semiconductor-based nanomaterials are extensively discussed to remove mercury, chromium, and arsenic ions from wastewater by the adsorption process. Advanced nanomaterials involved in photocatalytic reduction are also comprehensively discussed.

A systematic and critical review on effective utilization of artificial intelligence for bio-diesel production techniques - Junaid Ahmad; Muhammad Awais; Umer Rashid; Chawalit Ngamcharussrivichai; Salman Raza Naqvi; Imtiaz Ali (Fuel, 2023)

The effect of different in-line mixers producing emulsifier-free bio-diesel emulsion on the diesel engine combustion performance and exhaust emission - Wan Nur Izzati Wan Mahdi; Ahmad Muhsin Ithnin; Wira Jazair Yahya; Muhammad Adib Abdul Rashid; Hasannuddin Abd Kadir; Dhani Avianto Sugeng; Kinoshita Eiji (Fuel, 2023)

CNN-based segmentation frameworks for structural component and earthquake damage determinations using UAV images - Taisei Saida; Muhammad Rashid; Yudai Nemoto; Shota Tsukamoto; Takehiko Asai; Mayuko Nishio (Earthquake Engineering and Engineering Vibration, 2023)

Poultry manure gleaned antibiotic residues in soil environment: A perspective of spatial variability and influencing factors - Azhar Rashid; Juma Muhammad; Sardar Khan; Aatika Kanwal; Qian Sun (Chemosphere, 2023)

Reconnoitering the capabilities of nodule endophytic Pantoea dispersa for improved nodulation and grain yield of chickpea (Cicer arietinum L.) - Mohsin Tariq; Nayab Hasnain; Ijaz Rasul; Muhammad Azeem Asad; Aqsa Javed; Kamran Rashid; Javeria Shafique; Wajeeha Iram; Amir Hameed; Marriam Zafar (World Journal of Microbiology and Biotechnology, 2023)

Biochar Amendment in Combination with Endophytic Bacteria Stimulates Photosynthetic Activity and Antioxidant Enzymes to Improve Soybean Yield Under Drought Stress - Fahim Nawaz; Rashid Rafeeq; Sadia Majeed; Muhammad Shoaib Ismail; Muhammad Ahsan; Khawaja Shafique Ahmad; Ahsan Akram; Ghulam Haider (Journal of Soil Science and Plant Nutrition, 2023)
The beneficial effects of biochar (BC) and plant growth-promoting bacteria (PGPR) to increase crop yields under harsh environments have been widely reported. However, the knowledge on the synergistic effects of BC and PGPR to induce drought tolerance in oilseeds is scant. In the present study, the effects of cotton sticks derived BC together with PGPR strains ( Paraburkholderia phytofirmans and Bacillus sp.) were examined in water-stressed soybean plants. Initially, the BC application rates (1% and 2%) for soybean were optimized in a pilot experiment (experiment I), and the most effective level (1%) was selected for further studies together with PGPR in the second experiment. The soybean plants were raised in pots under semi-controlled conditions and were subjected to drought stress (25–30% water holding capacity) at pod formation stage. In comparison with control, the drought-mediated decrease in photosynthetic pigments and gas exchange characteristics was markedly lower in BC and PGPR-treated plants. However, the maximum increase in photosynthetic (12–30%) and the enzymatic antioxidant activities (5–20%) was recorded in plants treated with BC + P. phytofirmans , whereas no further significant increase was observed in plants treated with combined BC and Bacillus sp. under water deficit conditions. Similarly, the combined BC and P. phytofirmans application considerably increased the grain yield (14%) under drought stress conditions. We conclude that the combined application of BC + P. phytofirmans could be utilized as an effective strategy to improve soybean yield in dry arid regions.

Experimental Characterization-Based Machine Learning Modeling for the Estimation of Geotechnical Properties of Clay Liners - Hafiz Muhammad Awais Rashid; Muhammad Sufyan; Atif Ismail; Umer Waqas (Geotechnical and Geological Engineering, 2023)

Urinary PAHs metabolites in Karakoram Highway’s heavy traffic vehicle (HTV) drivers: evidence of exposure and health risk - Maria Rafique; Audil Rashid; Shu Tao; Bin Wang; Aman Ullah; Lun Lu; Habib Ullah; Muhammad Ubaid Ali; Waqas Naseem (Environmental Geochemistry and Health, 2023)

Impacts of COVID-19 pandemic on environment, society, and food security - Hafiz Mohkum Hammad; Hafiz Muhammad Fasihuddin Nauman; Farhat Abbas; Rashid Jawad; Wajid Farhad; Muhammad Shahid; Hafiz Faiq Bakhat; Aitazaz A. Farooque; Muhammad Mubeen; Shah Fahad; Artemi Cerda (Environmental Science and Pollution Research, 2023)

Effect of straw particle size in high grain complete pelleted diet on growth performance, rumen pH, feeding behavior, nutrient digestibility, blood and carcass indices of fattening male goats - Muhammad Awais Khurshid; Muhammad Afzal Rashid; Muhammad Shahbaz Yousaf; Saima Naveed; Muhammad Qamer Shahid; Habib Ur Rehman (Small Ruminant Research, 2023)

Numerical investigation of fully confined RC column with carbon fiber reinforced polymer when expose to fire - Nur Aqilah Zakaria; Ruqayyah Ismail; Fariz Aswan Ahmad Zakwan; Hazrina Ahmad; Muhamad Firdaus Rosle; Mohd Hisbany Mohd Hashim; Raizal Saifulnaz Muhammad Rashid (Physics and Chemistry of the Earth, Parts A/B/C, 2023)

Polyetherimide membrane with tunable porous morphology for safe lithium metal-based batteries - Arshad Hussain; Andleeb Mehmood; Adil Saleem; Muhammad K. Majeed; Waseem Raza; Rashid Iqbal; Sajid Rauf; Ali Saad; Yonggui Deng; Geng Luo; Kai Zong; Liu Wei; et al. (Chemical Engineering Journal, 2023)

Zeolite amendment reduces lead accumulation and improves growth and yield in tomato plants irrigated with sewage water - Rashid Jawad; Aamir Nawaz; Shaghef Ejaz; Sajid Ali; Muhammad Shahzad Saleem; Hafiz Mohkum Hammad (Environmental Science and Pollution Research, 2023)

Metal ferrites-based nanocomposites and nanohybrids for photocatalytic water treatment and electrocatalytic water splitting - Ahmad Farhan; Javeria Arshad; Ehsan Ullah Rashid; Haroon Ahmad; Shahid Nawaz; Junaid Munawar; Jakub Zdarta; Teofil Jesionowski; Muhammad Bilal (Chemosphere, 2023)

Profiling of phthalates, brominated, and organophosphate flame retardants in COVID-19 lockdown house dust; implication on the human health - Nadeem Ali; Muhammad Imtiaz Rashid; Nabil A. Alhakamy; Sultan Hassan Alamri; Syed Ali Musstjab Akber Shah Eqani (Science of The Total Environment, 2023)

Implementing a novel deep learning technique for rainfall forecasting via climatic variables: An approach via hierarchical clustering analysis - Shah Fahad; Fang Su; Sufyan Ullah Khan; Muhammad Rashid Naeem; Kailei Wei (Science of The Total Environment, 2023)

Spatial and temporal analyses of land use changes with special focus on seasonal variation in snow cover in District Chitral; a Hindu Kush mountain region of Pakistan - Muhammad Qasim; Mudassir Khan; Wajid Rashid (Remote Sensing Applications: Society and Environment, 2023)

Role of biochar-based free radicals in immobilization and speciation of metals in the contaminated soil-plant environment - Muhammad Saqib Rashid; Guijian Liu; Balal Yousaf; Yasir Hamid; Abdul Rehman; Muhammad Arif; Rafay Ahmed; Yu Song; Aniqa Ashraf (Journal of Environmental Management, 2023)

A review of waste management approaches to maximise sustainable value of waste from the oil and gas industry and potential for the State of Qatar - Muhammad Shahbaz; Naim Rashid; Junaid Saleem; Hamish Mackey; Gordon McKay; Tareq Al-Ansari (Fuel, 2023)

Polygeneration syngas and power from date palm waste steam gasification through an Aspen Plus process modeling - Arshid Mahmood Ali; Muhammad Shahbaz; Khurram Shahzad; Muddasser Inayat; Salman Naqvi; Abdulrahim Ahmad Al-Zahrani; Muhammad Imtiaz Rashid; Mohammad Rehan; Aishah Binti Mahpudz (Fuel, 2023)

Electrically conductive Pt-MOFs for acidic oxygen reduction: Optimized performance via altering conjugated ligands - Rashid Iqbal; Sajjad Ali; Adil Saleem; Muhammad K. Majeed; Arshad Hussain; Sajid Rauf; Abdul Rehman Akbar; Hu Xu; Liang Qiao; Wei Zhao (Chemical Engineering Journal, 2023)

Graphene-based nanoarchitectures as ideal supporting materials to develop multifunctional nanobiocatalytic systems for strengthening the biotechnology industry - Muhammad Bilal; Ehsan Ullah Rashid; Jakub Zdarta; Teofil Jesionowski (Chemical Engineering Journal, 2023)

Global declarations on electric vehicles, carbon life cycle and Nash equilibrium - Baher Bakhtyar; Zhang Qi; Muhammad Azam; Salim Rashid (Clean Technologies and Environmental Policy, 2023)
Universal environmental policies adopt strategies that enhance and encourage the production and usage of electric vehicles (EVs). Universal cooperation is evident in the framework of agreements or protocols so as to successfully lead countries towards the predetermined goals. The question is whether this trend can reduce global warming or CO 2 emissions worldwide. By adopting game theory, this study analyses electricity carbon life cycle in leading EV countries. Results show that although the spread of EVs in Europe and the USA can mitigate carbon emissions, the production and use of electric vehicles in some countries, such as China and India, become a new source of such emissions. This reverse effect is due to the emission of greenhouse gases from electricity sources in these countries. Game theory also suggests that countries with unclean electricity sources should reconsider their plans to produce and use EVs. This study confirms that although carbon emission and global warming are global problems, regional and local policies can be substituted with a single comprehensive approach for an effective means of CO 2 emission reduction. Graphical abstract

Arsenic Contamination, Water Toxicity, Source Apportionment, and Potential Health Risk in Groundwater of Jhelum Basin, Punjab, Pakistan - Zahid Ullah; Abdur Rashid; Junaid Ghani; Muhammad Afnan Talib; Asfandyar Shahab; Lu Lun (Biological Trace Element Research, 2023)

Prevalence of FANCM germline variants in BRCA1/2 negative breast and/or ovarian cancer patients from Pakistan - Muhammad Usman Rashid; Noor Muhammad; Umara Shehzad; Faiz Ali Khan; Asif Loya; Ute Hamann (Familial Cancer, 2023)

Air quality index prediction via multi-task machine learning technique: spatial analysis for human capital and intensive air quality monitoring stations - Xin Xiang; Shah Fahad; Myat Su Han; Muhammad Rashid Naeem; Shah Room (Air Quality, Atmosphere & Health, 2023)

Molecular epidemiology and characterization of Babesia bovis in cattle of Khyber Pakhtunkhwa province, Pakistan - Muhammad Shoaib; Muhammad Imran Rashid; Haroon Akbar; Ali Ahmad Sheikh; Shahid Hussain Farooqi; Amel Ayari-Akkari; Habab M. Yassin; Rajwali Khan (Tropical Animal Health and Production, 2022)

Association mapping for abiotic stress tolerance using heat- and drought-related syntenic markers in okra - Ikhlaq Ahmad; Rashid Mehmood Rana; Mahmood Ul Hassan; Muhammad Azam Khan; Muhammad Sajjad (Molecular Biology Reports, 2022)

An integrated approach towards marble waste management: GIS, SFA, and recycling options - Muhammad Fawad; Farid Ullah; Wisal Shah; Muhammad Jawad; Kifayatullah Khan; Wajid Rashid (Environmental Science and Pollution Research, 2022)

A quantitative assessment of pollution from potentially toxic elements in groundwater and the accompanying health risks - Atif Muhmood; Abdul Majeed; Abid Niaz; Asrar Hussain Shah; Ali Afzal; Khaliq ur Rehman Arshad; Muhammad Rashid; Arslan Nazarat (Arabian Journal of Geosciences, 2022)

Impact of climate change on extreme floods under high-end warming scenario RCP8.5 for the Kabul River Basin in Pakistan - Asif Mehmood; Shaofeng Jia; Muhammad Masood; Aifeng Lv; Rashid Mahmood; Wenbin Zhu (Arabian Journal of Geosciences, 2022)

Biological and Photocatalytic Degradation of Congo Red, a Diazo Sulfonated Substituted Dye: a Review - Rana Rashad Mahmood Khan; Hoorish Qamar; Ayesha Hameed; Aqmar ur Rehman; Muhammad Pervaiz; Zohaib Saeed; Aqib Adnan; Ayoub Rashid Ch (Water, Air, & Soil Pollution, 2022)

Aqueous carbonation of peridotites for carbon utilisation: a critical review - Muhammad Imran Rashid; Emad Benhelal; Leo Anderberg; Faezeh Farhang; Timothy Oliver; Mark Stuart Rayson; Michael Stockenhuber (Environmental Science and Pollution Research, 2022)

Hydrogeochemical assessment of carcinogenic and non-carcinogenic health risks of potentially toxic elements in aquifers of the Hindukush ranges, Pakistan: insights from groundwater pollution indexing, GIS-based, and multivariate statistical approaches - Abdur Rashid; Muhammad Ayub; Sardar Khan; Zahid Ullah; Liaqat Ali; Xubo Gao; Chengcheng Li; Hamed A. El-Serehy; Prashant Kaushik; Atta Rasool (Environmental Science and Pollution Research, 2022)

A plant-type L-asparaginase from Pyrobaculum calidifontis undergoes temperature dependent autocleavage - Muhammad Sajed; Samia Falak; Majida Atta Muhammad; Nasir Ahmad; Naeem Rashid (Biologia, 2022)

Assessing Salt Tolerance Induction in Potato by Salicylic Acid Using Morpho-Physio-Biochemical, Ionic, and Yield Indices - Hafiz Nazar Faried; C. M. Ayyub; Fahad Masoud Wattoo; Mohsin Bashir; Kashif Razzaq; Gulzar Akhtar; Abid Hussain; Sami Ullah; Javed Iqbal Wattoo; Muhammad Amin; Shoaib Munir; Muhammad Rashid Shaheen; et al. (Potato Research, 2022)

Early summer surface air temperature variability over Pakistan and the role of El Niño–Southern Oscillation teleconnections - Irfan Ur Rashid; Muhammad Adnan Abid; Mansour Almazroui; Fred Kucharski; Muhammad Hanif; Shaukat Ali; Muhammad Ismail (International Journal of Climatology, 2022)
Early summer (May–June) is the season where the surface air temperature (SAT) variability is largest and may result in extreme temperature conditions over Pakistan. Therefore, we analysed the early summer interannual SAT variability over Pakistan for the period 1981–2018 using observational dataset and model simulations. We noted that upper‐level anticyclonic circulation anomalies over Pakistan, which are associated with upper to the middle tropospheric descending motion, favour clear skies with an increase in net shortwave radiation that leads to extreme surface warming over the region. Moreover, the El Niño–Southern Oscillation (ENSO) based on Niño3.4 SST index is negatively associated with SAT anomalies over Pakistan. The cold ENSO phase favours the positive geopotential height anomalies due to the strengthening of the Walker circulation that enhance the sinking motion and result in less cloudiness leading to the extreme higher surface temperature conditions over Pakistan, while the opposite happens in the warm ENSO phase. Moreover, the Saudi‐KAU Atmospheric Global Climate Model (AGCM) simulated large‐scale patterns that are in good agreement with the observations. Sensitivity experiments with the AGCM confirm that cold SST anomalies in the ENSO region significantly favour above‐normal SAT anomalies over Pakistan, while the opposite happens in the warm ENSO phase. These results are important to understand and potentially predict regional heatwaves over the South Asian region, particularly over Pakistan.

Pcal_2031, a RecA/Rad51 homologue from Pyrobaculum calidifontis, complements the ultraviolet light sensitivity of Escherichia coli - Syed Nasim Abbas; Mehwish Aslam; Amina Maqsood; Hafiza Zumra Fatima; Muhammad Arshad Javed; Naeem Rashid (Biologia, 2022)

Sustainable Conversion of Wastes into Green Bioproducts to Introduce Diversification and Green Economy in the Sugar Industry. A Review - Noé Aguilar-Rivera; Muhammad Tahir Khan; Imtiaz Ahmed Khan; Rashid Iqbal; Muhammad Mahran Aslam (Sugar Tech, 2022)

Plastics in the environment as potential threat to life: an overview - Imania Ghaffar; Muhammad Rashid; Muhammad Akmal; Ali Hussain (Environmental Science and Pollution Research, 2022)

Correction to: In-Silico analyses of Nonsynonymous Variants in the BRCA1 Gene - Sidra Arshad; Irfan Ishaque; Sidra Mumtaz; Muhammad Usman Rashid; Naila Malkani (Biochemical Genetics, 2022)

Resveratrol and neuroprotection: an insight into prospective therapeutic approaches against Alzheimer’s disease from bench to bedside - Fahadul Islam; Mohamed H. Nafady; Md. Rezaul Islam; Susmita Saha; Salma Rashid; Aklima Akter; Md. Harun- Or-Rashid; Muhammad Furqan Akhtar; Asma Perveen; Ghulam Md. Ashraf; Md. Habibur Rahman; Sherouk Hussein Sweilam (Molecular Neurobiology, 2022)

Decomposition analytics of carbon emissions by cement manufacturing – a way forward towards carbon neutrality in a developing country - Rizwan Rasheed; Fizza Tahir; Muhammad Afzaal; Sajid Rashid Ahmad (Environmental Science and Pollution Research, 2022)

Effect of slow release nitrogenous fertilizers and biochar on growth, physiology, yield, and nitrogen use efficiency of sunflower under arid climate - Muhammad Waqar; Muhammad Habib-ur-Rahman; Muhammad Usama Hasnain; Shahid Iqbal; Abdul Ghaffar; Rashid Iqbal; Muhammad Iftikhar Hussain; Ayman EL Sabagh (Environmental Science and Pollution Research, 2022)
Sunflower plants need nitrogen consistently and in higher amount for optimum growth and development. However, nitrogen use efficiency (NUE) of sunflower crop is low due to various nitrogen (N) losses. Therefore, it is necessary to evaluate the advanced strategies to minimize N losses and also improve sunflower productivity under arid climatic conditions. A field trial was conducted with four slow release nitrogenous fertilizers [SRNF (bacterial, neem, and sulfur-coated urea and N loaded biochar)] and three N levels (100% = 148 kg N ha −1 , 80% = 118 kg N ha −1 , and 60% = 89 kg N ha −1 ) of recommended application (100%) for sunflower crop under arid climatic conditions. Results showed that neem-coated urea at 148 kg N ha −1 significantly enhanced crop growth rate (CGR) (19.16 g m −2 d −1 ) at 60–75 days after sowing (DAS); leaf area index (2.12, 3.62, 5.97, and 3.00) at 45, 60, 75, and 90 DAS; and total dry matter (14.27, 26.29, 122.67, 410, and 604.33 g m −2 ) at 30, 45, 60, 75, and 90 DAS. Furthermore, higher values of net leaf photosynthetic rate (25.2 µmol m −2 s −1 ), transpiration rate (3.66 mmol s −1 ), and leaf stomatal conductance (0.39 mol m −2 s −1 ) were recorded for the same treatment. Similarly, neem-coated urea produced maximum achene yield (2322 kg ha −1 ), biological yield (9000 kg ha −1 ), and harvest index (25.8%) of the sunflower crop. Among various N fertilizers, neem-coated urea showed maximum NUE (20.20 kg achene yield kg −1 N applied) in comparison to other slow release N fertilizers. Similarly, nitrogen increment N 60 showed maximum NUE (22.40 kg grain yield kg −1 N applied) in comparison to N 80 and N 100 . In conclusion, neem-coated urea with 100% and 80% of recommended N would be recommended for farmers to get better sunflower productivity with sustainable production and to reduce the environmental nitrogen losses.

RETRACTED ARTICLE: Low-cost novel nano-constructed granite composites for removal of hazardous Terasil dye from wastewater - Maria Khalil; Muhammad Asif Hanif; Umer Rashid; Junaid Ahmad; Ali Alsalme; Toshiki Tsubota (Environmental Science and Pollution Research, 2022)

Bionomics and management of aphid, Brevicoryne brassicae (Homoptera: Aphididae) on canola (Brassica napus) using Chrysoperla carnea - Muhammad Mamoon-ur-Rashid; Syed Wajhi-ul-Abbas; Habib Ali; Hussan Ara Beghum; Waqar Islam; Madiha Zaynab; Mubasher Hussain; Obaid Ullah Sayal; Habib ur Rehman; Asif Latif (International Journal of Tropical Insect Science, 2022)

Interactive effect of amino acids balanced at ideal lysine ratio and exogenous protease supplemented to low CP diet on growth performance, carcass traits, gut morphology, and serum metabolites in broiler chicken - Muhammad Adeel Maqsood; Ehsaan Ullah Khan; Shafqat Nawaz Qaisrani; Muhammad Afzal Rashid; Muhammad Shabir Shaheen; Azhar Nazir; Hammad Talib; Sohail Ahmad (Tropical Animal Health and Production, 2022)

Genetic diversity and marker trait association for phytophthora resistance in chilli - Tazien Bukhari; Rashid Mehmood Rana; Mahmood Ul Hassan; Farah Naz; Muhammad Sajjad (Molecular Biology Reports, 2022)

Single nucleotide polymorphism based assessment of genetic diversity in local and exotic onion genotypes - Najma Tabussam; Rashid Mehmood Rana; Fahad Masoud Wattoo; Azeem Iqbal Khan; Rai Muhammad Amir; Talha Javed; Sunny Ahmar; Eldessoky S. Dessoky; Nader R. Abdelsalam (Molecular Biology Reports, 2022)

Phycoremediation of textile effluents with enhanced efficacy of biodiesel production by algae and potential use of remediated effluent for improving growth of wheat - Muhammad Rashid Waqas; Sajid Mahmood Nadeem; Muhammad Yahya Khan; Zeeshan Ahmad; Liaqat Ali; Hafiz Naeem Asghar; Azeem Khalid (Environmental Science and Pollution Research, 2022)

Influence of Endogenous Plant Hormones on Physiological and Growth Attributes of Kinnow Mandarin Grafted on Nine Rootstocks - Muhammad Ahsan Qureshi; Muhammad Jafar Jaskani; Ahmad Sattar Khan; Rashid Ahmad (Journal of Plant Growth Regulation, 2022)

Phyto-mediated photocatalysis: a critical review of in-depth base to reactive radical generation for erythromycin degradation - Aniqa Ashraf; Guijian Liu; Balal Yousaf; Muhammad Arif; Rafay Ahmed; Audil Rashid; Luqman Riaz; Muhammad Saqib Rashid (Environmental Science and Pollution Research, 2022)

Temporal variation in leachate composition of a newly constructed landfill site in Lahore in context to environmental pollution and risks - Mahsoon Ashraf; Muhammad Zeshan; Sadia Hafeez; Rahib Hussain; Abdul Qadir; Muzaffar Majid; Farman Ahmad; Sajid Rashid Ahmad (Environmental Science and Pollution Research, 2022)

Effects of replacement of wheat straw with corn stover-based TMR on growth performance, behavioral characteristics, selected blood metabolites, and nutrient digestibility in Beetal bucks - Faisal Majeed; Saeed Ahmed; Muhammad Afzal Rashid; Muhammad Qamar Shahid; Imran Mohsin (Tropical Animal Health and Production, 2022)

A modified approach to quantify aquifer vulnerability to pollution towards sustainable groundwater management in Irrigated Indus Basin - Muhammad Umar; Shahbaz Nasir Khan; Arfan Arshad; Rana Ammar Aslam; Hafiz Muhammad Safdar Khan; Haroon Rashid; Quoc Bao Pham; Abdul Nasir; Rabeea Noor; Khaled Mohamed Khedher; Duong Tran Anh (Environmental Science and Pollution Research, 2022)

Integration of multispectral and hyperspectral remote sensing data for lithological mapping in Zhob Ophiolite, Western Pakistan - Muhammad Qasim; Shuhab D. Khan; Rashid Haider; Mehboob ur Rasheed (Arabian Journal of Geosciences, 2022)

Application of Biofloc Technology for the culture of Heteropneustes fossilis (Bloch) in Bangladesh: stocking density, floc volume, growth performance, and profitability - Md Shamsuddin; M. Belal Hossain; Moshiur Rahman; Mst. Salamun Kawla; Md. Badiul Alam Shufol; Muhammad Mamunur Rashid; Md. Asadujjaman; Md. Refat Jahan Rakib (Aquaculture International, 2022)

Drought-tolerant Bacillus megaterium isolated from semi-arid conditions induces systemic tolerance of wheat under drought conditions - Urooj Rashid; Humaira Yasmin; Muhammad Nadeem Hassan; Rabia Naz; Asia Nosheen; Muhammad Sajjad; Noshin Ilyas; Rumana Keyani; Zahra Jabeen; Saqib Mumtaz; Mohammed Nasser Alyemeni; Parvaiz Ahmad (Plant Cell Reports, 2022)

RETRACTED ARTICLE: Impact of credit, liquidity, and systematic risk on financial structure: comparative investigation from sustainable production - Muhammad Sadiq; Sami Alajlani; Muhammed Sajjad Hussain; Rashid Ahmad; Furrukh Bashir; Supat Chupradit (Environmental Science and Pollution Research, 2022)

Strategies to enhance soluble production of heterologous proteins in Escherichia coli - Samia Falak; Muhammad Sajed; Naeem Rashid (Biologia, 2022)

Correction to: Molecular detection of Cryptosporidium: an emerging parasite in different water sources of 2010 flood‑affected district Nowshera, Pakistan - Shaukat Ali Khan; Imran Khan; Izaz Ali; Amir Muhammad Khan; Muhammad Anees; Khurshaid Ali Khan; Wajid Rashid; Noorul Akbar (Archives of Microbiology, 2022)

Economic study on biohydrogen production from liquid pineapple waste - Syaza I. Ahmad; Roslina Rashid; Zanariah Hashim; Chew Chee Meng; Chong Kar Lun; Den Muhammad Hamdi Jumaatuden; Norhidayah Ahmad Yasin; Ashella Jati; Mimi H. Hassim (Clean Technologies and Environmental Policy, 2022)

Pollution characteristics, mechanism of toxicity and health effects of the ultrafine particles in the indoor environment: Current status and future perspectives - Muhammad Ubaid Ali; Siyi Lin; Balal Yousaf; Qumber Abbas; Mehr Ahmed Mujtaba Munir; Audil Rashid; Chunmiao Zheng; Xingxing Kuang; Ming Hung Wong (Critical Reviews in Environmental Science and Technology, 2022)

Mining public opinion: a sentiment based forecasting for democratic elections of Pakistan - Asif Nawaz; Tariq Ali; Yaser Hafeez; Saif ur Rehman; Muhammad Rizwan Rashid (Spatial Information Research, 2022)

First report of Neopestalotiopsis clavispora causing postharvest fruit rot of loquat in Pakistan - Muhammad Fahim Abbas; Sana Batool; Tamoor Khan; Muhammad Rashid (Journal of Plant Pathology, 2022)

RNA interference-mediated knockdown of odorant-binding protein 2 and MP58 gene causes mortality in Myzus persicae - Iqra Mahmood; Amber Afroz; Muhammad Faheem Malik; Nadia Zeeshan; Muhammad Ramzan Khan; Umer Rashid; Muhammad Azmat Ullah Khan; Naeem Mehmood Ashraf; Sadia Alam (International Journal of Tropical Insect Science, 2022)

Comparative seismic performance assessment of RC and RC/ECC hybrid frame structures: a shake table study - Fasih Ahmed Khan; Muhammad Rashid; Sajjad Wali Khan; Muhammad Rizwan; Yasir Irfan Badrashi; Muhammad Fahim; Muhammad Ashraf Tanoli; Wasim Khaliq; Akhtar Gul (Innovative Infrastructure Solutions, 2022)

Biochar and slow-releasing nitrogen fertilizers improved growth, nitrogen use, yield, and fiber quality of cotton under arid climatic conditions - Sobia Manzoor; Muhammad Habib-ur-Rahman; Ghulam Haider; Iqra Ghafoor; Saeed Ahmad; Muhammad Afzal; Fahim Nawaz; Rashid Iqbal; Mubashra Yasin; Tanveer-ul-Haq; Subhan Danish; Abdul Ghaffar (Environmental Science and Pollution Research, 2022)
The efficiency of nitrogenous fertilizers in South Asia is on a declining trajectory due to increased losses. Biochar (BC) and slow-releasing nitrogen fertilizers (SRNF) have been found to improve nitrogen use efficiency (NUE) in certain cases. However, field-scale studies to explore the potential of BC and SRNF in south Asian arid climate are lacking. Here we conducted a field experiment in the arid environment to demonstrate the response of BC and SRNF on cotton growth and yield quality. The treatments were comprised of two factors, (A) nitrogen sources, (i) simple urea, (ii)neem-coated urea, (iii)sulfur-coated urea, (iv) bacterial coated urea, and cotton stalks biochar impregnated with simple urea, and (B) nitrogen application rates, N 1 =160 kg ha -1 , N 2 = 120 kg ha -1 , and N 3 = 80 kg ha -1 . Different SRNF differentially affected cotton growth, morphological and physiological attributes, and seed cotton yield (SCY). The bacterial coated urea at the highest rate of N application (160 kg ha -1 ) resulted in a higher net leaf photosynthetic rate (32.8 μmol m -2 s -1 ), leaf transpiration rate (8.10 mmol s -1 ), and stomatal conductance (0.502 mol m -2 s -1 ), while leaf area index (LAI), crop growth rate (CGR), and seed cotton yield (4513 kg ha -1 ) were increased by bacterial coated urea at 120 kg ha -1 than simple urea. However, low rate N application (80 kg ha -1 ) of bacterial coated urea showed higher nitrogen use efficiency (39.6 kg SCY kg -1 N). The fiber quality (fiber length, fiber strength, ginning outturn, fiber index, and seed index) was also increased with the high N application rates than N2 and N3 application. To summarize, the bacterial coated urea with recommended N (160 kg ha -1 ) and 75% of recommended N application (120 kg ha -1 ) may be recommended for farmers in the arid climatic conditions of Punjab to enhance the seed cotton yield, thereby reducing nitrogen losses.

Spatial distribution of carbon dynamics and nutrient enrichment capacity in different layers and tree tissues of Castanopsis eyeri natural forest ecosystem - Taimoor Hassan Farooq; Xen Xincheng; Awais Shakoor; Muhammad Haroon U. Rashid; Muhammad Farhan Bashir; Muhammad Farrakh Nawaz; Uttam Kumar; Sher Muhammad Shahzad; Wende Yan (Environmental Science and Pollution Research, 2022)

Consumer perceptions of hybrid electric vehicle adoption and the green automotive market: the Malaysian evidence - Muhammad Iskandar Hamzah; Nurul Syafiqah Tanwir; Siti Norida Wahab; Muhammad Hafiz Abd Rashid (Environment, Development and Sustainability, 2022)

Intron-containing hairpin RNA interference vector for OBP8 show promising mortality in peach potato aphid - Amber Afroz; Safeena Aslam; Umer Rashid; Muhammad Faheem Malik; Nadia Zeeshan; Muhammad Ramzan Khan; Muhammad Qasim Shahzad But; Sabaz Ali Khan (Plant Cell, Tissue and Organ Culture (PCTOC), 2022)

Biofertilizer microorganisms accompanying pathogenic attributes: a potential threat - Mohsin Tariq; Farwah Jameel; Usman Ijaz; Muhammad Abdullah; Kamran Rashid (Physiology and Molecular Biology of Plants, 2022)

Synthesis and evaluation of Ca-doped ferrihydrite as a novel adsorbent for the efficient removal of fluoride - Khalil Ahmad; Izaz Ali Shah; Sharafat Ali; Muhammad Tariq Khan; Muhammad Bilal Ahmed Qureshi; Syed Hassan Ali Shah; Asmat Ali; Wajid Rashid; Hifza Nayab Gul (Environmental Science and Pollution Research, 2022)

Annual Growth Progression, Nutrient Transformation, and Carbon Storage in Tissues of Cunninghamia lanceolata Monoculture in Relation to Soil Quality Indicators Influenced by Intraspecific Competition Intensity - Taimoor Hassan Farooq; Awais Shakoor; Muhammad Haroon U. Rashid; Saiyang Zhang; Pengfei Wu; Wende Yan (Journal of Soil Science and Plant Nutrition, 2021)

Analysis of food resources, host availability and insecticidal impacts on the fecundity, longevity and parasitism efficiency of Diaertiella rapae (M’intosh) - Ahmad Nawaz; Habib Ali; Sajid Fiaz; Muhammad Sufyan; Miza Abdul Qayyum; Rashid Azad; Yasir Niaz; Muhamamd Adnan Bodlah; Khalid Ali Khan (International Journal of Tropical Insect Science, 2021)

New records of Meschia pugnax (Heteroptera: Meschiidae) and stethoconus praefectus (Heteroptera: Miridae): predatory deraeocorinae plant bug associated with tingidae bugs, Pakistan - Zuhaib Ahmad; Muhammad Naeem; Tariq Mahmood; Rashid Azad (International Journal of Tropical Insect Science, 2021)

Quest for Novel Preventive and Therapeutic Options Against Multidrug-Resistant Pseudomonas aeruginosa - Sidra Irum; Saadia Andleeb; Amjad Ali; Muhammad Ibrahim Rashid; Mahnoor Majid (International Journal of Peptide Research and Therapeutics, 2021)

Assessing the potential of partial root zone drying and mulching for improving the productivity of cotton under arid climate - Rashid Iqbal; Muhammad Habib-ur-Rahman; Muhammad Aown Sammar Raza; Muhammad Waqas; Rao Muhammad Ikram; Muhammad Zeshan Ahmed; Monika Toleikiene; Muhammad Ayaz; Farhan Mustafa; Salman Ahmad; Muhammad Usman Aslam; Muhammad Mohsin Waqas; et al. (Environmental Science and Pollution Research, 2021)
Water scarcity constrains global cotton production. However, partial root-zone drying (PRD) and mulching can be used as good techniques to save water and enhance crop production, especially in arid regions. This study aimed to evaluate the effects of mulching for water conservation in an arid environment under PRD and to further assess the osmotic adjustment and enzymatic activities for sustainable cotton production. The study was carried out for 2 years in field conditions using mulches (NM = no mulch, BPM = black plastic mulch at 32 kg ha -1 , WSM = wheat straw mulch at 3 tons ha -1 , CSM = cotton sticks mulch at 10 tons ha -1 ) and two irrigation levels (FI = full irrigation and PRD (50% less water than FI). High seed cotton yield (SCY) achieved in FI+WSM (4457 and 4248 kg ha -1 in 2017 and 2018, respectively) and even in PRD+WSM followed by BPM>CSM>NM under FI and PRD for both years. The higher SCY and traits observed in FI+WSM and PRD+WSM compared with the others were attributed to the improved water use efficiency and gaseous exchange traits, increased hormone production (ABA), osmolyte accumulation, and enhanced antioxidants to scavenge the excess reactive oxygen. Furthermore, better cotton quality traits were also observed under WSM either with FI or PRD irrigation regimes. Mulches applications found effective to control the weeds in the order as BPM>WSM>CSM. In general, PRD can be used as an effective stratagem to save moisture along with WSM, which ultimately can improve cotton yield in the water-scarce regions under arid climatic regions. It may prove as a good adaptation strategy under current and future water shortage scenarios of climate change.

In-Silico Analyses of Nonsynonymous Variants in the BRCA1 Gene - Sidra Arshad; Irfan Ishaque; Sidra Mumtaz; Muhammad Usman Rashid; Naila Malkani (Biochemical Genetics, 2021)

Comparative analysis of chicken cecal microbial diversity and taxonomic composition in response to dietary variation using 16S rRNA amplicon sequencing - Zubia Rashid; Muhammad Zubair Yousaf; Syed Muddassar Hussain Gilani; Sitwat Zehra; Ashaq Ali; Abid Azhar; Saddia Galani (Molecular Biology Reports, 2021)

Preparation and Characterization of pH-Independent Sustained-Release Tablets Containing Hot Melt Extruded Solid Dispersions of Clarithromycin - Qazi Amir Ijaz; Sumera Latif; Qurat-ul-ain Shoaib; Memoona Rashid; Muhammad Sohail Arshad; Amjad Hussain; Nadeem Irfan Bukhari; Sohail Riaz; Nasir Abbas (AAPS PharmSciTech, 2021)

Effects of sodium bicarbonate and chromium propionate supplementation on growth performance, blood indices of Beetal bucks under heat stress - Ahsan Jamal; Muhammad Afzal Rashid; Muhammad Irfan Malik (Tropical Animal Health and Production, 2021)

Carbonated ground granulated blast furnace slag stabilising brown kaolin - Ahmed Mohammed Awad Mohammed; Nor Zurairahetty Mohd Yunus; Muhammad Azril Hezmi; Ahmad Safuan A. Rashid; Suksun Horpibulsuk (Environmental Science and Pollution Research, 2021)

Geochemical fractionation and spectroscopic fingerprinting for evaluation of the environmental transformation of potentially toxic metal(oid)s in surface–subsurface soils - Samina Irshad; Guijian Liu; Balal Yousaf; Muhammad Ubaid Ali; Rafay Ahmed; Abdul Rehman; Muhammad Saqib Rashid; Yusra Mahfooz (Environmental Geochemistry and Health, 2021)

Effects of different water percentages in non-surfactant water-in-diesel emulsion fuel on the performance and exhaust emissions of a small-scale industrial burner - Ili Fatimah Abd Razak; Wira Jazair Yahya; Ahmad Muhsin Ithnin; Mohd Rashid; Muhammad Ahmar Zuber; Hasannuddin Abd Kadir; Syahrullail Samion; Hirofumi Noge (Clean Technologies and Environmental Policy, 2021)

Assessment of plastic waste generation and its feasibility for establishment of plastic waste refinery - Muhammad Ziad; Sardar Khan; Rashid Miandad; Gohar Ali; Muhammad Zaffar Hashmi; Zulkifl Ahmed (Arabian Journal of Geosciences, 2021)

Wheat Genotypes with Higher Intercellular CO2 Concentration, Rate of Photosynthesis, and Antioxidant Potential Can Better Tolerate Drought Stress - Aman Ullah; Rashid Said Al-Rajhi; Abdullah M. Al-Sadi; Muhammad Farooq (Journal of Soil Science and Plant Nutrition, 2021)

Climatological and social fallacies about COVID-19 pandemic - Ambar Farooq; Uttam Kumar; Junaite Bin Gais Uddin; Muhammad Haroon U. Rashid; Matoor Mohsin Gilani; Taimoor Hassan Farooq; Awais Shakoor; Matloob Ahmad (Environmental Sustainability, 2021)

Molecular detection of Cryptosporidium: an emerging parasite in different water sources of 2010 flood-affected district Nowshera, Pakistan - Shaukat Ali Khan; Imran Khan; Izaz Ali; Amir Muhammad Khan; Muhammad Anees; Khurshaid Ali Khan; Wajid Rashid; Noorul Akbar (Archives of Microbiology, 2021)

The distribution and composition of litter on the Aoshan Beach Qingdao, China - Rashid Pervez; Yonghong Wang; Zafarullah Jattak; Muhammad Zahir; Qaisar Mahmood (Journal of Coastal Conservation, 2021)

Achieving pro-poor growth and environmental sustainability agenda through information technologies: as right as rain - Muhammad Imran; Khan Burhan Khan; Khalid Zaman; Mohammed Borhandden Musah; Elih Sudiapermana; Abdul Rashid Abdul Aziz; Rahimah Embong; Zainudin Bin Hassan; Mohd Khata Jabor; Siti Nisrin Mohd Anis (Environmental Science and Pollution Research, 2021)

Monitoring of field-evolved resistance to flonicamid, neonicotinoid, and conventional insecticides in the Oxycarenus hyalinipennis costa - Inam Ullah; Shabana Wazir; Naeem Abbas; Muhammad Naeem; Khalid Abdullah; Zahid Mahmood; Mamoon-ur Rashid; Abdulwahab M. Hafez (Environmental Monitoring and Assessment, 2021)

Geotechnical characterization of bentonite-fly ash mixtures for their application as landfill liner in Pakistan - Hafiz Muhammad Awais Rashid; Arsalan Sardar; Atif Ismail (Arabian Journal of Geosciences, 2021)

Heat shock protein gene identified from Agave sisalana (AsHSP70) confers heat stress tolerance in transgenic cotton (Gossypium hirsutum) - Anicet Agossa Batcho; Muhammad Bilal Sarwar; Bushra Rashid; Sameera Hassan; Tayyab Husnain (Theoretical and Experimental Plant Physiology, 2021)

Proteasomal degradation of p130 facilitate cell cycle deregulation and impairment of cellular differentiation in high-risk Human Papillomavirus 16 and 18 E7 transfected cells - Sivasangkary Gandhi; Nurshamimi Nor Rashid; Muhammad Fazril Mohamad Razif; Shatrah Othman (Molecular Biology Reports, 2021)

Carbon-Based Slow-Release Fertilizers for Efficient Nutrient Management: Synthesis, Applications, and Future Research Needs - Muhammad Rashid; Qaiser Hussain; Khalid Saifullah Khan; Mohammad I. Alwabel; Rifat Hayat; Muhammad Akmal; Shahzada Sohail Ijaz; Sarosh Alvi; Obaid-ur-Rehman (Journal of Soil Science and Plant Nutrition, 2021)

Immunoinformatics Driven Prediction of Multiepitopic Vaccine Against Klebsiella pneumoniae and Mycobacterium tuberculosis Coinfection and Its Validation via In Silico Expression - Sidra Rahmat Ullah; Mahnoor Majid; Muhammad Ibrahim Rashid; Khalid Mehmood; Saadia Andleeb (International Journal of Peptide Research and Therapeutics, 2021)

Correction to: Biomonitoring of Toxic Metals in Feathers of Birds from North-Eastern Pakistan - Bushra Rashid; Muhammad Zubair; Nausheen Irshad; Khawaja Shafique Ahmad; Majid Mahmood; Majid Mahmood Tahir; Khizar Hussain Shah; Aqeela Shaheen (Bulletin of Environmental Contamination and Toxicology, 2021)

Removal of N-terminal methionine of human interferon α-2b by co‐producing with Pyrococcus furiosus methionine aminopeptidase in Escherichia coli - Amina Arif; Naeem Rashid; Muhammad Akhtar (Biologia, 2021)

Empirical assessment of rockfall and debris flow risk along the Karakoram Highway, Pakistan - Sajid Ali; Rashid Haider; Wahid Abbas; Muhammad Basharat; Klaus Reicherter (Natural Hazards, 2021)
The Karakoram Highway links north Pakistan with southwest China. It passes through unique geomorphological, geological and tectonic setting. This study focused 200-km-long section of the highway starting from Besham until Chilas. Landslides are frequent and are mostly triggered by torrential rain during Monsoon and Westerlies, leading to highway blockade. Rockfall and debris flow are prime mode of slope failures. Regional to site-specific approach was implemented to assess risk associated with these two modes. Remote sensing-based techniques were used to identify potential hazardous sites, which were further investigated for risk assessment. Modified Pierson’s rockfall hazard rating system (RHRS) rated potential rockfalls, whereas semi-quantitative technique was employed to assess debris flows. Normalized scores of each site shaped the final map, further classified into four zones: very high, high, intermediate and low risk.

Growth and Physiology of Maize (Zea mays L.) in a Nickel-Contaminated Soil and Phytoremediation Efficiency Using EDTA - Muhammad Imran Tipu; Muhammad Yasin Ashraf; Nadeem Sarwar; Muhammad Akhtar; Muhammad Rashid Shaheen; Sajjad Ali; Christos A. Damalas (Journal of Plant Growth Regulation, 2021)

A case–control study of determinants for COVID-19 infection based on contact tracing in Dungun district, Terengganu state of Malaysia - Hafizuddin Awang; Effah Leiylena Yaacob; Sharifah Nadira Syed Aluawi; Muhammad Faris Mahmood; Fathul Hakim Hamzah; Azmani Wahab; Norafidah Abdul Rashid; Rosmaliza Razali; Goh Soo Ning; Kasemani Embong; Nor Azimi Yunus (Infectious Diseases, 2021)

Correction to: Ground improvement and its role in carbon dioxide reduction: a review - Ahmed Mohammed Awad Mohammed; Nor Zurairahetty Mohd Yunus; Muhammad Azril Hezmi; Dayang Zulaika Abang Hasbollah; Ahmad Safuan A Rashid (Environmental Science and Pollution Research, 2021)

Arsenic and lead in the indoor residential settings of different socio-economic status; assessment of human health risk via dust exposure - Nadeem Ali; Syed Ali Musstjab Akber Shah Eqani; Ehtisham Nazar; Nabil A. Alhakamy; Muhammad Imtiaz Rashid; Khurram Shahzad; Jahan Zeb; Heqing Shen; Iqbal Mohammad Ibrahim Ismail; Hussain Mohammed Salem Ali Albar (Environmental Science and Pollution Research, 2021)

Detection of Human Adenovirus, Rotavirus, and Enterovirus in Tap Water and Their Association with the Overall Quality of Water in Karachi, Pakistan - Muhammad Rashid; Muhammad Naseem Khan; Nusrat Jalbani (Food and Environmental Virology, 2021)

SARS-COV-2 infection and lung tumor microenvironment - Naila Malkani; Muhammad Usman Rashid (Molecular Biology Reports, 2021)

A state-of-the-art review on wastewater treatment techniques: the effectiveness of adsorption method - Ruhma Rashid; Iqrash Shafiq; Parveen Akhter; Muhammad Javid Iqbal; Murid Hussain (Environmental Science and Pollution Research, 2021)

Ground improvement and its role in carbon dioxide reduction: a review - Mohammed Awad Mohammed; Nor Zurairahetty Mohd Yunus; Muhammad Azril Hezmi; Dayang Zulaika Abang Hasbollah; Ahmad Safuan A Rashid (Environmental Science and Pollution Research, 2021)

Potential risk and source distribution of groundwater contamination by mercury in district Swabi, Pakistan: Application of multivariate study - Seema Anjum Khattak; Abdur Rashid; Muhammad Tariq; Liaqat Ali; Xubo Gao; Muhammad Ayub; Asif Javed (Environment, Development and Sustainability, 2021)

Molecular identification of sugarcane black bug (Cavelarius excavates) from Pakistan using cytochrome C oxidase I (COI) gene as DNA barcode - Khadim Hussain; Kamran Rashid; Faisal Hafeez; Ikrma Amad; Muhammad Ashraf (International Journal of Tropical Insect Science, 2020)

Methanolic extract of Ephedra ciliata promotes wound healing and arrests inflammatory cascade in vivo through downregulation of TNF-α - Hafiza Sidra Yaseen; Muhammad Asif; Malik Saadullah; Mahrukh; Sajid Asghar; Muhammad Usman Shams; Rizwan Rashid Bazmi; Mohammad Saleem; Hafiz Muhammad Yousaf; Maria Yaseen (Inflammopharmacology, 2020)

Novel loss-of-function mutations in COCH cause autosomal recessive nonsyndromic hearing loss - Kevin T. Booth; Amama Ghaffar; Muhammad Rashid; Luke T. Hovey; Mureed Hussain; Kathy Frees; Erika M. Renkes; Carla J. Nishimura; Mohsin Shahzad; Richard J. Smith; Zubair Ahmed; Hela Azaiez; et al. (Human Genetics, 2020)

Spatially analyzing food consumption inequalities using GIS with disaggregated data from Punjab, Pakistan. - Sana Khushi; Sajid Rashid Ahmad; Ather Ashraf; Muhammad Imran (Food Security, 2020)

Impact assessment of urban development patterns on land surface temperature by using remote sensing techniques: a case study of Lahore, Faisalabad and Multan district - Muhammad Sajid Saleem; Sajid Rashid Ahmad; Shafiq-Ur-Rehman; Muhammad Asif Javed (Environmental Science and Pollution Research, 2020)

Identification of irrigation potential areas, using multi-criteria analysis in Khyber District, Pakistan - Muhammad Waleed; Sajid Rashid Ahmad; Muhammad Asif Javed; Saifullah Samiullah (Environmental Science and Pollution Research, 2020)

Influence of metallic species for efficient photocatalytic water disinfection: bactericidal mechanism of in vitro results using docking simulation - Aaima Iftikhar; Muhammad Saqib Khan; Umer Rashid; Qaisar Mahmood; Habiba Zafar; Muhammad Bilal; Nadia Riaz (Environmental Science and Pollution Research, 2020)

Risk assessment of hazardous elements in wastewater irrigated soil and cultivated vegetables in Pakistan - Alia Naz; Sardar Khan; Said Muhammad; Rafiq Ahmad; Salma Khalid; Abdullah Khan; Rashid Nazir; Sadia Alam; Zia ur Rahman (Arabian Journal of Geosciences, 2020)

Single tube multiplex PCR assay for the identification of banned meat species - Memoona Iqbal; Muhammad Sulyman Saleem; Muhammad Imran; Waseem Ahmad Khan; Kamran Ashraf; M. Yasir Zahoor; Imran Rashid; Habib-Ur Rehman; Asif Nadeem; Saadat Ali; Sarwat Naz; Wasim Shehzad (Food Additives & Contaminants Part B-Surveillance, 2020)

Enhancement of salt tolerance in maize (Zea mays L.) using locally isolated Bacillus sp. SR-2-1/1 - Khadija Rafiq; Muhammad Sohail Akram; Muhammad Shahid; Uzma Qaisar; Naeem Rashid (Biologia, 2020)

Foliage applied proline induces salt tolerance in chili genotypes by regulating photosynthetic attributes, ionic homeostasis, and antioxidant defense mechanisms - Madiha Butt; Abdul Sattar; Tahira Abbas; Ahmad Sher; Muhammad Ijaz; Sami Ul-Allah; Muhammad Rashid Shaheen; Fawad Kaleem (Horticulture, Environment, and Biotechnology, 2020)

Study of sunspot cycles using fractal dimensions: wave-spectrum scaling - Asma Zaffar; Shaheen Abbas; Muhammad Rashid Kamal Ansari (Arabian Journal of Geosciences, 2020)

Calcium-mediated adaptive responses to low phosphorus stress in Chinese fir - Muhammad Haroon U. Rashid; Mulualem Tigabu; Haifeng Chen; Taimoor Hassan Farooq; Xiangqing Ma; Pengfei Wu (Trees, 2020)

Abundance, type, and origin of litter on No. 1 Bathing Beach of Qingdao, China - Rashid Pervez; Yonghong Wang; Qaisar Mahmood; Muhammad Zahir; Zafarullah Jattak (Journal of Coastal Conservation, 2020)

An unintended challenge of microplastic pollution in the urban surface water system of Lahore, Pakistan - Muhammad Irfan; Abdul Qadir; Mehvish Mumtaz; Sajid Rashid Ahmad (Environmental Science and Pollution Research, 2020)

Gene cloning and characterization of Tk1281, a flap endonuclease 1 from Thermococcus kodakarensis - Hira Muzzamal; Qurat ul Ain; Muhammad Sulaiman Saeed; Naeem Rashid (Folia Microbiologica, 2020)

Selective and simultaneous detection of cadmium, lead and copper by tapioca-derived carbon dot–modified electrode - Musa Yahaya Pudza; Zurina Zainal Abidin; Suraya Abdul-Rashid; Faizah Md Yasin; Ahmad Shukri Muhammad Noor; Jaafar Abdullah (Environmental Science and Pollution Research, 2020)

Oxidative stress risk assessment through heavy metal and arsenic exposure in terrestrial and aquatic bird species of Pakistan - Shamsa Kanwal; Naeem Akhtar Abbasi; Muhammad Jamshed Iqbal Chaudhry; Sajid Rashid Ahmad; Riffat Naseem Malik (Environmental Science and Pollution Research, 2020)

Transcriptomic analysis of root specific drought mediated response of G. arboreum and G. hirsutum - Zarnab Ahmad; Sajjad Sadique; Muhammad B. Sarwar; Bushra Rashid; Sameera Hassan; Sultana Rasheed; Khurram Bashir; Motoaki Seki; Tayyab Husnain (Biologia, 2020)

Identification and validation of superior housekeeping gene(s) for qRT-PCR data normalization in Agave sisalana (a CAM-plant) under abiotic stresses - Muhammad Bilal Sarwar; Zarnab Ahmad; Batcho Agossa Anicet; Moon Sajid; Bushra Rashid; Sameera Hassan; Mukhtar Ahmed; Tayyab Husnain (Physiology and Molecular Biology of Plants, 2020)

Organochlorine pesticides in the surrounding soils of POPs destruction facility: source fingerprinting, human health, and ecological risks assessment - Syeda Nazish Ali; Mujtaba Baqar; Mehvish Mumtaz; Uzma Ashraf; Muhammad Naveed Anwar; Abdul Qadir; Sajid Rashid Ahmad; Abdul-Sattar Nizami; Huang Jun (Environmental Science and Pollution Research, 2020)

Concomitant Treatment of Tannery and Paper Mill Effluents Using Extremely Metal-Tolerant Sulphate-Reducing Bacteria - Muhammad Muneeb; Muhammad Rashid; Arshad Javid; Syed Mohsin Bukhari; Waqas Ali; Ali Hasan; Muhammad Akmal; Ali Hussain (Environmental Processes, 2020)

Valorization of solid waste biomass by inoculation for the enhanced yield of biogas - Yasir Abbas; Farrukh Jamil; Sikander Rafiq; Moinuddin Ghauri; M. Shahzad Khurram; Muhammad Aslam; Awais Bokhari; Abrar Faisal; Umer Rashid; Sining Yun; Muhammad Mubeen (Clean Technologies and Environmental Policy, 2020)

Coagulation- and Adsorption-Based Environmental Impact Assessment and Textile Effluent Treatment - Muhammad Aleem; Jiashun Cao; Chao Li; Haroon Rashid; Yang Wu; Muhammad Imran Nawaz; Muhammad Abbas; Muhammad Waqar Akram (Water, Air, & Soil Pollution, 2020)

Correction to: Synthesis and Biodistribution Study of Biocompatible 198Au Nanoparticles by use of Arabinoxylan as Reducing and Stabilizing Agent - Fozia Iram; Mohammad S. Iqbal; Irfan U. Khan; Rashid Rasheed; Aqsa Khalid; Muhammad Khalid; Saira Aftab; Abdul R. Shakoori (Biological Trace Element Research, 2020)

Correlation of MLH1 polymorphisms, survival statistics, in silico assessment and gene downregulation with clinical outcomes among breast cancer cases - Saima Shakil Malik; Ayisha Zia; Sumaira Mubarik; Nosheen Masood; Sajid Rashid; Alice Sherrard; Muhammad Bilal Khan; Muhammad Tahir Khadim (Molecular Biology Reports, 2020)

Human health risks by potentially toxic metals in drinking water along the Hattar Industrial Estate, Pakistan - Shah Jehan; Seema Anjum Khattak; Said Muhammad; Liaqat Ali; Abdur Rashid; Mian Luqman Hussain (Environmental Science and Pollution Research, 2020)

Synthesis and Biodistribution Study of Biocompatible 198Au Nanoparticles by use of Arabinoxylan as Reducing and Stabilizing Agent - Fozia Iram; Mohammad S. Iqbal; Irfan U. Khan; Rashid Rasheed; Aqsa Khalid; Muhammad Khalid; Saira Aftab; Abdul R. Shakoori (Biological Trace Element Research, 2020)

Functional Annotation and Analysis of Dual Oxidase 1 (DUOX1): a Potential Anti-pyocyanin Immune Component - Muhammad Ibrahim Rashid; Amjad Ali; Saadia Andleeb (Interdisciplinary Sciences: Computational Life Sciences, 2019)

Comparative study of the genetic basis of nitrogen use efficiency in wild and cultivated barley - Jawad Munawar Shah; Sidra tul Muntaha; Essa Ali; Azhar Abbas Khan; Syed Hassan Raza Zaidi; Ahmad Naeem Shahzad; Zeshan Hassan; Ahmad Nawaz; Muhammad Rashid; Syed Asad Hussain Bukhari (Physiology and Molecular Biology of Plants, 2019)

Moderating role of financial development in environmental Kuznets: a case study of Malaysia - Abid Rashid Gill; Sallahuddin Hassan; Muhammad Haseeb (Environmental Science and Pollution Research, 2019)

Socio-political and ecological stresses on traditional pastoral systems: A review - Khurshid Muhammad; Nafees Mohammad; Khan Abdullah; Somuncu Mehmet; Ahmad Khan Ashfaq; Rashid Wajid (Journal of Geographical Sciences, 2019)

Exogenously applied proline induced changes in key anatomical features and physio-biochemical attributes in water stressed oat (Avena sativa L.) plants - Rehmana Ghafoor; Nudrat Aisha Akram; Muhammad Rashid; Muhammad Ashraf; Muhammad Iqbal; Zhang Lixin (Physiology and Molecular Biology of Plants, 2019)

Characterization of recombinant endo-1,4-β-xylanase of Bacillus halodurans C-125 and rational identification of hot spot amino acid residues responsible for enhancing thermostability by an in-silico approach - Malik Siddique Mahmood; Faiz Rasul; Mahjabeen Saleem; Amber Afroz; Muhammad Faheem Malik; Naeem Mehmood Ashraf; Umar Rashid; Shumaila Naz; Nadia Zeeshan (Molecular Biology Reports, 2019)

Assessment of nematodes in Punjab Urial (Ovis vignei punjabiensis) population in Kalabagh Game Reserve: development of a DNA barcode approach - Amna Arshad Bajwa; Jordan Patrick Cuff; Muhammad Imran; Saher Islam; Riffat Mansha; Kamran Ashraf; Arman Khan; Muhammad Imran Rashid; Muhammad Yasir Zahoor; Waseem Ahmad Khan; Habib Ur Rehman; Asif Nadeem; et al. (European Journal of Wildlife Research, 2019)

Recombinant Tk0522, a carbohydrate esterase homologue from Thermococcus kodakarensis, does not require a signal sequence for translocation to periplasmic space in Escherichia coli - Anam Tariq; Alina Gul; Majida A. Muhammad; Naeem Rashid; Masood A Siddiqui (Biologia, 2019)

Appraisal of Urban Heat Island Detection of Peshawar Using Land Surface Temperature and Its Impacts on Environment - Rashid Mehmood; Muhammad Atif Butt (Journal of the Indian Society of Remote Sensing, 2019)

Counting the beans: quantifying the adoption of improved mungbean varieties in South Asia and Myanmar - Pepijn Schreinemachers; Teresa Sequeros; Saima Rani; Md. Abdur Rashid; Nithya Vishwanath Gowdru; Muhammad Shahrukh Rahman; Mohammed Razu Ahmed; Ramakrishnan Madhavan Nair (Food Security, 2019)

Taxonomic significance of leaf epidermis in tribe Trifolieae L. (Leguminosae; Papilionoideae) in Pakistan - Neelam Rashid; Muhammad Zafar; Mushtaq Ahmad; Mir Ajab Khan; Khafsa Malik; Shazia Sultana; Syed Nasar Shah (Plant Biosystems, 2019)

Reporting effective extraction methodology and chemical characterization of bioactive components of under explored Platycladus orientalis (L.) Franco from semi-arid climate - Rafia Rehman; Muhammad Asif Hanif; Muhammad Zahid; Rashid Waseem Khan Qadri (Natural Product Research, 2019)

Different ambient management intervention techniques and their effect on milk production and physiological parameters of lactating NiliRavi buffaloes during hot dry summer of subtropical region - Mehtab Ahmad; Jalees Ahmed Bhatti; Muhammad Abdullah; Rahman Ullah; Qurat ul Ain; Muhammad Sajid Hasni; Mahboob Ali; Abdul Rashid; Imran Qaisar; Ghazunfar Rashid; Rafi Uddin (Tropical Animal Health and Production, 2019)

Pcal_0970: an extremely thermostable l-asparaginase from Pyrobaculum calidifontis with no detectable glutaminase activity - Shahid Mahmood Chohan; Naeem Rashid; Muhammad Sajed; Tadayuki Imanaka (Folia Microbiologica, 2019)

Severe infantile epileptic encephalopathy associated with D-glyceric aciduria: report of a novel case and review - Yoav Zehavi; Hanna Mandel; Ayelet Eran; Sarit Ravid; Muhammad Abu Rashid; Erwin E. W. Jansen; Mirjam M. C. Wamelink; Ann Saada; Avraham Shaag; Orly Elpeleg; Ronen Spiegel (Metabolic Brain Disease, 2019)

Assessment of flood-induced changes in soil heavy metal and nutrient status in Rajanpur, Pakistan - Farhan Hafeez; Noman Zafar; Rashid Nazir; Hafiz Muhammad Rashad Javeed; Muhammad Rizwan; Faridullah; Saeed Ahmad Asad; Akhtar Iqbal (Environmental Monitoring and Assessment, 2019)

Geochemical attributes of late Neoproterozoic Salt Range Formation, Pakistan: constraints on provenance, paleoclimate, depositional and tectonic settings - Muhammad Ahmed Farooqui; Muhammad Umar; Muhammad Amjad Sabir; Rashid Pervez; Tarib Jalees (Geosciences Journal, 2019)

Response of soil microbial biomass and enzymatic activity to biochar amendment in the organic carbon deficient arid soil: a 2-year field study - Muhammad Irfan; Qaiser Hussain; Khalid Saifullah Khan; Muhammad Akmal; Shahzada Sohail Ijaz; Rifat Hayat; Azeem Khalid; Muhammad Azeem; Muhammad Rashid (Arabian Journal of Geosciences, 2019)

Assessment of genetic diversity in round gourd (Praecitrullus fistulosus) germplasm of Pakistan considering morphological characters - Adeel Shahid; Chaudhary Muhammad Ayyub; Mazhar Abbas; Rashid Ahmad (Genetic Resources and Crop Evolution, 2019)

Genetic analysis of roots and shoots in rice seedling by association mapping - Yan Zhao; Cong-hui Jiang; Rashid Muhammad Abdul Rehman; Hong-liang Zhang; Jinjie Li; Zi-chao Li (Genes & Genomics, 2019)

Extremely stable indole-3-glycerol-phosphate synthase from hyperthermophilic archaeon Pyrococcus furiosus - Muhammad Arif; Naeem Rashid; Sumera Perveen; Qamar Bashir; Muhammad Akhtar (Extremophiles, 2019)

CO2 foam for enhanced oil recovery (EOR) applications using low adsorption surfactant structure - Muhammad Sagir; Muhammad Mushtaq; Muhammad Bilal Tahir; Muhammad Suleman Tahir; Sami Ullah; Khurum Shahzad; Umer Rashid (Arabian Journal of Geosciences, 2018)

Erosion potential assessment of watersheds through GIS-based hypsometric analysis: a case study of Kurram Tangi Dam - Wasif Yousaf; Syed Ghulam Mohayud-Din-Hashmi; Usman Akram; Urooj Saeed; Sajid Rashid Ahmad; Muhammad Umar; Ambreena Mubashir (Arabian Journal of Geosciences, 2018)

Molecular epidemiology of bovine anaplasmosis in Khyber Pakhtunkhwa, Pakistan - Shahid Hussain Farooqi; Muhammad Ijaz; Muhammad Imran Rashid; H. Nabi; S. Islam; Amjad Islam Aqib; Kashif Hussain; Amjad Khan; Syeda Nayab Batool Rizvi; Shakeel Mahmood; Khalid Mehmood; Hui Zhang (Tropical Animal Health and Production, 2018)

Evaluation of CMIP5 models for projection of future precipitation change in Bornean tropical rainforests - Mubasher Hussain; Khamaruzaman Wan Yusof; Muhammad Raza Ul Mustafa; Rashid Mahmood; Shaofeng Jia (Theoretical and Applied Climatology, 2018)

Diesel engine emission analysis using fuel from diverse emulsification methods - Dhani Avianto Sugeng; Wira Jazair Yahya; Ahmad Muhsin Ithnin; Muhammad Adib Abdul Rashid; Nur Salsabilla Mohd Syahril Amri; Hasannuddin Abd Kadir; Mohd Naim Abdul Halim (Environmental Science and Pollution Research, 2018)

Glutamic acid assisted phyto-management of silver-contaminated soils through sunflower; physiological and biochemical response - Mujahid Farid; Shafaqat Ali; Muhammad Zubair; Rashid Saeed; Muhammad Rizwan; Rasham Sallah-Ud-Din; Ahmad Azam; Rehman Ashraf; Wasim Ashraf (Environmental Science and Pollution Research, 2018)

Effect of gut bacteria on fitness of the Chinese citrus fly, Bactrocera minax (Diptera: Tephritidae) - Muhammad Adnan Rashid; Awawing Anjwengwo Andongma; Yong-Cheng Dong; Xue-Ming Ren; Chang-Ying Niu (Symbiosis, 2018)

Effect of ambient management interventions on the production and physiological performance of lactating Sahiwal cattle during hot dry summer - Mehtab Ahmad; Jalees Ahmed Bhatti; Muhammad Abdullah; Khalid Javed; Mehboob Ali; Ghazanfar Rashid; Rafi Uddin; Ali Hassan Badini; Mudassar Jehan (Tropical Animal Health and Production, 2018)

Effect of humic and fulvic acid transformation on cadmium availability to wheat cultivars in sewage sludge amended soil - Imran Rashid; Ghulam Murtaza; Zahir Ahmad Zahir; Muhammad Farooq (Environmental Science and Pollution Research, 2018)

Exhaust emission profiling of fatty acid methyl esters and NOx control studies using selective synthetic and natural additives - Saad Afzal; Muhammad Waseem Mumtaz; Umer Rashid; Muhammad Danish; Muhammad Asam Raza; Ahtasham Raza; Hamid Mukhtar; Saud Ibrahim Al-Resayes (Clean Technologies and Environmental Policy, 2018)

Optimizing Irrigation Deficit of Multipurpose Cascade Reservoirs - Muhammad Usman Rashid; Abid Latif; Muhammad Azmat (Water Resources Management, 2018)

Enhancement of gene expression in Escherichia coli and characterization of highly stable ATP-dependent glucokinase from Pyrobaculum calidifontis - Tahira Bibi; Musadiq Ali; Naeem Rashid; Majida Atta Muhammad; Muhammad Akhtar (Extremophiles, 2018)

Lead Concentrations in Soils and Some Wild Plant Species Along Two Busy Roads in Pakistan - Noreen Khalid; Mumtaz Hussain; Hillary S. Young; Muhammad Ashraf; Mansoor Hameed; Rashid Ahmad (Bulletin of Environmental Contamination and Toxicology, 2018)

The probability distributions and fractal dimension of sunspot cycles associated with ENSO phenomena - Asma Zaffar; Shaheen Abbas; Muhammad Rashid Kamal Ansari (Arabian Journal of Geosciences, 2018)

Pcal_0632, a phosphorylating glyceraldehyde-3-phosphate dehydrogenase from Pyrobaculum calidifontis - Iram Aziz; Naeem Rashid; Raza Ashraf; Masood Ahmed Siddiqui; Tadayuki Imanaka; Muhammad Akhtar (Extremophiles, 2018)

Rice bran nutraceutics: A comprehensive review - Muhammad Sohail; Allah Rakha; Masood Sadiq Butt; Muhammad Jawad Iqbal; Summer Rashid (Critical Reviews in Food Science and Nutrition, 2017)

Erratum to: Sub-chronic exposure to low concentration of dibutyl phthalate affects anthropometric parameters and markers of obesity in rats - Khalid Abdul Majeed; Habib ur Rehman; Muhammad Shahbaz Yousaf; Hafsa Zaneb; Imtiaz Rabbani; Sajid Khan Tahir; Muhammad Afzal Rashid (Environmental Science and Pollution Research, 2017)

Sub-chronic exposure to low concentration of dibutyl phthalate affects anthropometric parameters and markers of obesity in rats - Khalid Abdul Majeed; Habib ur Rehman; Muhammad Shahbaz Yousaf; Hafsa Zaneb; Imtiaz Rabbani; Sajid Khan Tahir; Muhammad Afzal Rashid (Environmental Science and Pollution Research, 2017)

Pcal_1311, an alcohol dehydrogenase homologue from Pyrobaculum calidifontis, displays NADH-dependent high aldehyde reductase activity - Raza Ashraf; Naeem Rashid; Tamotsu Kanai; Tadayuki Imanaka; Muhammad Akhtar (Extremophiles, 2017)

Microwave irradiation and citric acid assisted seed germination and phytoextraction of nickel (Ni) by Brassica napus L.: morpho-physiological and biochemical alterations under Ni stress - Mujahid Farid; Shafaqat Ali; Muhammad Rizwan; Rashid Saeed; Hafiz Muhammad Tauqeer; Rasham Sallah-Ud-Din; Ahmed Azam; Nighat Raza (Environmental Science and Pollution Research, 2017)

Currently used organophosphate and brominated flame retardants in the environment of China and other developing countries (2000–2016) - Nadeem Ali; Khurram Shahzad; Muhammad Imtiaz Rashid; Heqing Shen; Iqbal Mohammad Ibrahim Ismail; Syed Ali Musstjab Akber Shah Eqani (Environmental Science and Pollution Research, 2017)

Citric acid enhanced the antioxidant defense system and chromium uptake by Lemna minor L. grown in hydroponics under Cr stress - Rasham Sallah-Ud-Din; Mujahid Farid; Rashid Saeed; Shafaqat Ali; Muhammad Rizwan; Hafiz Muhammad Tauqeer; Syed Asad Hussain Bukhari (Environmental Science and Pollution Research, 2017)

Phyto-management of Cr-contaminated soils by sunflower hybrids: physiological and biochemical response and metal extractability under Cr stress - Mujahid Farid; Shafaqat Ali; Nudrat Aisha Akram; Muhammad Rizwan; Farhat Abbas; Syed Asad Hussain Bukhari; Rashid Saeed (Environmental Science and Pollution Research, 2017)

Identification of a novel copper-activated and halide-tolerant laccase in Geobacillus thermopakistaniensis - Saadia Basheer; Naeem Rashid; Raza Ashraf; Muhammad Sohail Akram; Masood Ahmed Siddiqui; Tadayuki Imanaka; Muhammad Akhtar (Extremophiles, 2017)

Pcal_0111, a highly thermostable bifunctional fructose-1,6-bisphosphate aldolase/phosphatase from Pyrobaculum calidifontis - Iram Aziz; Naeem Rashid; Raza Ashraf; Qamar Bashir; Tadayuki Imanaka; Muhammad Akhtar (Extremophiles, 2017)

Pathogenic diversity of Xanthomonas oryzae pv. oryzae isolates collected from Punjab Province of Pakistan - Hafiz Muhammad Imran Arshad; Kamran Saleem; Junaid Ahmed Khan; Muhammad Rashid; Muhammad Atiq; Syed Sarwar Alam; Shahbaz Talib Sahi (European Journal of Plant Pathology, 2017)

Influence of UV-A radiation on oxidative stress and antioxidant enzymes in Mythimna separata (Lepidoptera: Noctuidae) - Arif Ali; Muhammad Adnan Rashid; Qiu Ying Huang; Chao-Liang Lei (Environmental Science and Pollution Research, 2017)

A new irregular monoterpene acetate along with eight known compounds with antifungal potential from the aerial parts of Artemisia incisa Pamp (Asteraceae) - Mamoon Ur Rashid; Muhammad Alamzeb; Saqib Ali; Zafar Ali Shah; Ishrat Naz; Ashfaq Ahmad Khan; Dima Semaan; Mohammad Rafiullah Khan (Natural Product Research, 2017)

Prospective study of avian influenza H9 infection in commercial poultry farms of Punjab Province and Islamabad Capital Territory, Pakistan - Mamoona Chaudhry; Maqbool Ahmad; Hamad Bin Rashid; Bakhat Sultan; Haroon Rashid Chaudhry; Aayesha Riaz; Muhammad Shabir Shaheen (Tropical Animal Health and Production, 2017)

TK1656, an L-asparaginase from Thermococcus kodakarensis, a novel candidate for therapeutic applications - Shahid Mahmood Chohan; Muhammad Atif Nisar; Naeem Rashid; Ghazaleh Gharib; Qamar Bashir; Masood Ahmed Siddiqui (Biologia, 2016)

Pcal_1127, a highly stable and efficient ribose-5-phosphate pyrophosphokinase from Pyrobaculum calidifontis - Tahira Bibi; Sumera Perveen; Iram Aziz; Qamar Bashir; Naeem Rashid; Tadayuki Imanaka; Muhammad Akhtar (Extremophiles, 2016)

Synthesis, in vitro potential and computational studies on 2-amino-1, 4-dihydropyrimidines as multitarget antibacterial ligands - Muhammad Jawad Ahmad; Syed Fahad Hassan; Riffat Un Nisa; Khurshid Ayub; Muhammad Shahid Nadeem; Samina Nazir; Farzana Latif Ansari; Naveeda Akhtar Qureshi; Umer Rashid (Medicinal Chemistry Research, 2016)

Effect of UV-A radiation as an environmental stress on the development, longevity, and reproduction of the oriental armyworm, Mythimna separata (Lepidoptera: Noctuidae) - Arif Ali; Muhammad Adnan Rashid; Qiu Ying Huang; Chao-Liang Lei (Environmental Science and Pollution Research, 2016)

Erratum to: Pcal_0768, a hyperactive 4-α-glucanotransferase from Pyrobaculum calidifontis - Sumaira Mehboob; Nasir Ahmad; Naeem Rashid; Tadayuki Imanaka; Muhammad Akhtar (Extremophiles, 2016)

Pcal_0768, a hyperactive 4-α-glucanotransferase from Pyrobacculum calidifontis - Sumaira Mehboob; Nasir Ahmad; Naeem Rashid; Tadayuki Imanaka; Muhammad Akhtar (Extremophiles, 2016)

Escherichia coli as a fatty acid and biodiesel factory: current challenges and future directions - Ziaur Rahman; Naim Rashid; Javed Nawab; Muhammad Ilyas; Bong Hyun Sung; Sun Chang Kim (Environmental Science and Pollution Research, 2016)

Foliar NK application mitigates drought effects in sunflower (Helianthus annuus L.) - Rai Altaf Hussain; Rashid Ahmad; Fahim Nawaz; Muhammad Yasin Ashraf; Ejaz Ahmad Waraich (Acta Physiologiae Plantarum, 2016)

Pcal_1699, an extremely thermostable malate dehydrogenase from hyperthermophilic archaeon Pyrobaculum calidifontis - Ghazaleh Gharib; Naeem Rashid; Qamar Bashir; Qura-tul Ann Afza Gardner; Muhammad Akhtar; Tadayuki Imanaka (Extremophiles, 2016)

Use of statistical and GIS techniques to assess and predict concentrations of heavy metals in soils of Lahore City, Pakistan - Nayab Alam; Sajid Rashid Ahmad; Abdul Qadir; Muhammad Imran Ashraf; Calvin Lakhan; V. Chris Lakhan (Environmental Monitoring and Assessment, 2015)

Effect of pH on the static adsorption of foaming surfactants on Malaysian sandstone - Muhammad Mushtaq; Isa M. Tan; Umer Rashid; Muhammad Sagir; Mudassar Mumtaz (Arabian Journal of Geosciences, 2015)

Isolation, structure elucidation and enzyme inhibition studies of a new hydroxy ester and other compounds from Berberis jaeschkeana Schneid stem - Muhammad Alamzeb; M. Rafiullah Khan; Mamoon-Ur-Rashid; Saqib Ali; Ashfaq Ahmad Khan (Natural Product Research, 2015)

Genetic analysis suggests a shared origin of Punica granatum cultivars in Oman with cultivars from the center of origin, Iran - Abdullah M. Al-Sadi; Ahmed R. AL-Fahdi; Rashid A. Al-Yahyai; Aisha G. Al-Ghaithi; Fahad A. Al-Said; Muhammad J. Soleiman (Genetic Resources and Crop Evolution, 2015)

Production of human interferon alpha-2b in Escherichia coli and removal of N-terminal methionine utilizing archaeal methionine aminopeptidase - Amina Arif; Qura-Tul-Ann A. Gardner; Naeem Rashid; Muhammad Akhtar (Biologia, 2015)

Optimization of Multiple Reservoirs Operation with Consideration to Sediment Evacuation - Muhammad Usman Rashid; Abdul Sattar Shakir; Noor Muhammad Khan; Abid Latif; Muhammad Mubashir Qureshi (Water Resources Management, 2015)

Application of GIS for the identification and demarcation of selective heavy metal concentrations in the urban groundwater - Sobia Ashraf; Farhat Abbas; Muhammad Ibrahim; Umer Rashid; Shoaib Khalid; Hammad Raza Ahmad; Khalid Rehman Hakeem; Tahir Majeed (Journal of Geographical Sciences, 2015)

Synthesis, docking studies, and in silico ADMET predictions of some new derivatives of pyrimidine as potential KSP inhibitors - Umer Rashid; Syed Fahad Hassan; Samina Nazir; Abdul Wadood; Muhammad Waseem; Farzana Latif Ansari (Medicinal Chemistry Research, 2015)

Cattle egrets as a biosentinels of persistent organic pollutants exposure - Mudassar Khan; Ashiq Mohammad; Karam Ahad; Athanasios Katsoyiannis; Salman Akbar Malik; Muhammad Abdullaha; Azhar Rashid; Mauro Fasola; Alamdar Hussain; Habib Bokhari; Syed Ali Musstjab Akber Shah Eqani (Environmental Geochemistry and Health, 2014)

Synthesis, characterization antibacterial and antifungal activity of some transition metal complexes - Wajid Rehman; Zonera Hassan; Umer Rashid; Fazal Rahim; Obaid-Ur-Rahman Abid; Muhammad Waseem (Medicinal Chemistry Research, 2014)

Cloning and characterization of Na+/H+ antiporter (LfNHX1) gene from a halophyte grass Leptochloa fusca for drought and salt tolerance - Muhammad Rauf; Khurram Shahzad; Rashid Ali; Moddassir Ahmad; Imran Habib; Shahid Mansoor; Gerald A. Berkowitz; Nasir A. Saeed (Molecular Biology Reports, 2014)

Molecular phylogeny of Pakistani riverine buffalo based on genetic variability of mitochondrial cytochrome b gene - Rashid Saif; Muhammad Wasim; Masroor Ellahi Babar (Molecular Biology Reports, 2012)

Cloning, characterization and molecular docking of a highly thermostable β-1,4-glucosidase from Thermotoga petrophila - Ikram Ul Haq; Mahmood Ali Khan; Bushra Muneer; Zahid Hussain; Sumra Afzal; Sana Majeed; Naeem Rashid; Muhammad Mohsin Javed; Ishtiaq Ahmad (Biotechnology Letters, 2012)

Prevalence of TP53 germ line mutations in young Pakistani breast cancer patients - Muhammad U. Rashid; Sidra Gull; Kashif Asghar; Noor Muhammad; Asim Amin; Ute Hamann (Familial Cancer, 2012)

Environmental impact assessment (EIA): an overlooked instrument for sustainable development in Pakistan - Rashid Saeed; Ayesha Sattar; Zafar Iqbal; Muhammad Imran; Raziya Nadeem (Environmental Monitoring and Assessment, 2012)

Identification of the deleterious 2080insA BRCA1 mutation in a male renal cell carcinoma patient from a family with multiple cancer diagnoses from Pakistan - Muhammad U. Rashid; Sidra Gull; Saima Faisal; Saba Khaliq; Kashif Asghar; Neelam Siddiqui; Asim Amin; Ute Hamann (Familial Cancer, 2011)

First cloning and characterization of aspartate aminotransferase from river buffalo (Bubalus bubalis) - Muhammad Shahid Nadeem; Naeem Rashid; Muzaffar Iqbal; Qurra-tul-Ann Afza Gardner; Muhammad Akhtar (Biologia, 2011)

Enhanced resistance against bacterial wilt in transgenic tomato (Lycopersicon esculentum) lines expressing the Xa21 gene - Amber Afroz; Zubeda Chaudhry; Umer Rashid; Ghulam Muhammad Ali; Farhat Nazir; Javaid Iqbal; Muhammad Rashid Khan (Plant Cell, Tissue and Organ Culture (PCTOC), 2011)

Gene cloning and characterization of glycine oxidase from newly isolated Bacillus subtilis strain R5 - Farrukh Jamil; Naeem Rashid; Qurra-tul-Ann Afza Gardner; Muhammad Akhtar (Biologia, 2011)

Efficient regeneration and antioxidant potential in regenerated tissues of Piper nigrum L. - Nisar Ahmad; Hina Fazal; Bilal Haider Abbasi; Muhammad Rashid; Tariq Mahmood; Nighat Fatima (Plant Cell, Tissue and Organ Culture (PCTOC), 2010)

Functional analysis of cotton small heat shock protein promoter region in response to abiotic stresses in tobacco using Agrobacterium-mediated transient assay - Muzna Zahur; Asma Maqbool; Muhammad Irfan; Muhammad Younas Khan Barozai; Uzma Qaiser; Bushra Rashid; Tayyab Husnain; Shiekh Riazuddin (Molecular Biology Reports, 2009)

Insoluble but enzymatically active α-amylase from Bacillus licheniformis - Naeem Rashid; Alia Farooq; Ikram-ul-Haq; Muhammad Akhtar (Biologia, 2009)

A convenient synthesis of p -substituted 1-arylsulfonyl-pyrrolidin-2-ones - Muhammad Zareef; Rashid Iqbal; Khalid M. Khan; Javid H. Zaidi; Zia-Ullah; Muhammad Arfan (Natural Product Research, 2009)

Improvement of Aspergillus oryzae for hyperproduction of endoglucanase: expression cloning of cmc-1 gene of Aspergillus aculeatus - Muhammad Hamid Rashid; Muhammad Rizwan Javed; Takashi Kawaguchi; Jun-ichi Sumitani; Motoo Arai (Biotechnology Letters, 2008)

Comparative efficacy of diminazene diaceturate and diminazene aceturate for the treatment of babesiosis in horses - Hamad Bin Rashid; Mamoona Chaudhry; Haroon Rashid; Khalid Pervez; Muhammad Arif Khan; Asim Khalid Mahmood (Tropical Animal Health and Production, 2008)

‘On-farm’ seed priming with zinc in chickpea and wheat in Pakistan - David Harris; Abdul Rashid; Ghazal Miraj; Muhammad Arif; Muhammed Yunas (Plant and Soil, 2008)

New ceramides from Platytaenia multicaule - Viqar Uddin Ahmad; Muhammad Zubair; Muhammad Athar Abbasi; Farzana Kousar; Muhammad Abid Rashid; Nasir Rasool; Rasool Bukhsh Tareen (Natural Product Research, 2006)

High frequency shoot regeneration and Agrobacterium-mediated DNA transfer in Canola (Brassica napus) - Muhammad Ramzan Khan; Hamid Rashid; Muhammad Ansar; Zubeda Chaudry (Plant Cell, Tissue and Organ Culture (PCTOC), 2003)